Unlocking the phosphorus reservoir in wet waste: Speciation, circular recovery strategies, and inter-phase migration - Xiaojian Dong; Shuang Li; Xiaoxia Chen; Qian Ping; Ming Zheng; Lin Wang; Yongmei Li (Bioresource Technology, 2027)

Correction to: Sequence dynamics and plastome evolution: decoding the complete chloroplast genome of Oenothera drummondii and comparative analysis within Oenothera (Onagraceae) - Chang An; Wenbo Xu; Yixin Yao; Min Li; Yanxiang Lin; S. V. G. N. Priyadarshani; Aya Elderini; Yan Cheng; Site Luo; Yuan Qin; Ping Zheng (Functional & Integrative Genomics, 2026)

Sequence dynamics and plastome evolution: decoding the complete chloroplast genome of Oenothera drummondii and comparative analysis within Oenothera (Onagraceae) - Chang An; Wenbo Xu; Yixin Yao; Min Li; Yanxiang Lin; S. V. G. N. Priyadarshani; Aya Elderini; Yan Cheng; Site Luo; Yuan Qin; Ping Zheng (Functional & Integrative Genomics, 2026)

Seismic performance evaluation of bridge isolated by damping enhanced-friction pendulum system considering variable friction effect - Wenzhi Zheng; Zhongkai Yi; Wanchen Meng; Ping Tan; Jian Li; Xijun Ye; Yanhui Liu (Soil Dynamics and Earthquake Engineering, 2026)

Assessing present-day tectonic stability, sea-level change, and tsunami hazards from a coastal multi-hazard GNSS station in the southern South China Sea - Qiang Qiu; Linlin Li; Mai Ye; Hongqiang Yang; Xingyu Song; Jian Ping Yin; Tingting Zheng; Jinghe Cao; Peitao Wang; Zhanying Chen; Zhiwen Zhang; Kuilin Xiao; et al. (Engineering Geology, 2026)

Mechanistic insights into Cu impurity retention and its effective removal in direct recycling of lithium-ion batteries - Wenlin Yan; Wei Li; Qiushi Miao; Mengchen Liu; Ershuang Lu; Jiao Lin; Minji Lee; Haichen Lin; Shuangjie Tan; Varun Gupta; Zheng Chen; Ping Liu (Chemical Engineering Journal, 2026)

Inducing spin polarization in Cs2CuBr4 by Fe2+ doping for efficient photocatalytic aerobic toluene oxidation - Hao Zheng; Jinlin Yin; Ping Lu; Yi Lu; Xinyan Jiang; Shaoke Chen; Yifei Pan; Ning Zhang; Jin Wang; Zhengquan Li (Chemical Engineering Journal, 2026)

Deciphering the structural and stoichiometric regulation of anaerobic digestion: A cross-scale perspective from molecular thermodynamics to methanogenic pathways - Qian Ping; Xiaoxia Chen; Yiwei Jin; Yifeng Chen; Ming Zheng; Lin Wang; Yongmei Li (Bioresource Technology, 2026)

AIE-active photoresponsive Ir(III) complex as an oxidase mimic for ratiometric ascorbic acid detection - Qianghui Zheng; Ping Huang; Ying Peng; Mei-Jin Li; Fengfu Fu (Analytica Chimica Acta, 2026)

Two-stage illumination with various lights regulate microalgal metabolism for enhanced pollutant removal and eicosapentaenoic acid (EPA) production from high-salinity food-processing wastewater - Hao Hu; Si Wu; Wei-Di Song; Zheng-Hao Li; Yan-Yun Hu; Guo-Ping Sheng (Water Research, 2026)

Ultra-high Phosphogypsum road base: Mix proportion design, microscopic mechanism, heavy metal leaching law and carbon reduction - Si-fan Meng; Chao-qiang Wang; Nan Li; Li-ping Zheng (Sustainable Chemistry and Pharmacy, 2026)

CvbZIP81 contributes to selenium accumulation by regulating sulfate transports in Cardamine violifolia - Luxin Feng; Jiarui Zheng; Sirui Zeng; Ge Li; Sisi Wang; Ping Yun; Zexiong Chen; Renhua Huang; Qiangwen Chen; Sergey Shabala; Feng Xu (Plant Science, 2026)

Fatty acid composition drives integrated changes in oxidative stability, phytonutrients and processing contaminants of diacylglycerols under thermal stress - Yingyi Zheng; Linjie Chen; Yee-Ying Lee; Mingchen Xu; Chin-Ping Tan; Yong Wang; Aijun Li; Zhen Zhang (Food Research International, 2026)

Natural deep eutectic solvent-extracted propolis bioactives and ZIF-L integrated PVA films for active packaging and oyster preservation - Tian Du; Qing-Ping Zheng; Ye-Ting Wang; Meng Li; Yan-Zhen Zheng (Food Research International, 2026)

Regulation of small-molecule compounds on LC-PUFA biosynthesis during adipogenic transdifferentiation of Salmo salar muscle cells and preparation of cell-cultured fish fat - Yingxin Wei; Tingting Hao; Yiming Feng; Pengyu Ji; Ruiyi Zhai; Ping Dong; Jie Xue; Zhaojie Li; Changhu Xue; Hongwei Zheng (Food Research International, 2026)

Rhamnolipids: from biosynthesis to applications - Ai-Ping Pang; Zhiqing Zhang; Guo-Zhao Li; Yun Wang; Kun Yang; Junping Zhou; Lianggang Huang; Li-Qun Jin; Zhi-Qiang Liu; Yu-Guo Zheng (Food Chemistry, 2026)

Integrated analysis of lipid remodeling and volatile evolution during refining of Antarctic krill oil - Xinya Huang; Meiyu Zheng; Jin Zhang; Jinglun Zhou; Qingyang Zhang; Zhengting Zhu; Ping Kong; Shu Wang; Bin Li; Zhigang Hu; Kangyu Zhao; Dongping He; et al. (Food Chemistry, 2026)

Beyond mortality: A multi-outcome assessment of health economic benefits from air pollution control in China - Hao-Wen Liao; Zhi-Ming Han; Guo-Ping Dong; Duo-Hong Chen; Min Xie; Jun Liu; Junyu Zheng; Yun-Ting Zhang; Haseeb Tufail Moryani; Muhammad Amjad; Yang Zhou; Wen-Wen Bao; et al. (Environmental Research, 2026)

Unlocking multiscale structure-property relationships in epoxy thermosets: A machine learning-driven approach to superior multi-objective performance - Gaoming Li; Yeping Wu; Yujie Xie; Chunhua Zhu; Song Yao; Zhongtao Chen; Ping Zhang; Zixuan Luo; Xiuli Zhao; Sixun Zheng; Yinyu Zhang (Chemical Engineering Journal, 2026)

Rosa roxburghii-derived Mg-doped carbon dots as bioactive nanoregulators in hydrogel scaffolds: orchestrating Nrf2/NF-κB signaling for enhanced periodontal repair in diabetes - Xuedong Deng; Lingxiang Sun; Xi Chen; Zheng Wang; Yilin Ping; Wen Ze Han; Lu Wang; Tingting Wu; Yifan Zhao; Bing Li; Xiuping Wu (Chemical Engineering Journal, 2026)

Tracking clinically critical antibiotic-resistant bacteria and resistance genes in biogas slurry-amended soil: occurrence, enrichment and vertical distribution - Jiwei Li; Yi Lu; Xingshuo Wang; Lifeng Ping; Hua Li; Guanyu Zheng; Ming Hung Wong; Shengdao Shan (Bioresource Technology, 2026)

Assessment of a farmland-constrained deep learning framework for fine-scale extraction of farmland shelterbelts from Sentinel-2 - Yingqi Xu; Ping Lv; Zhuo Zhang; Lanjie Li; Zheng Chai; Cheng Tang; Yuanyuan Li (Agroforestry Systems, 2026)

Mapping the True 3D Architecture: Quantitative Morphological Diversity of Human Hepatic Functional Unit Revealed by Fluorescence Micro-optical Section Tomography - Na Chen; Hongjun Liu; Xiaofeng Mei; Silin Liu; Hongjia Hu; Yunxi Lv; Qi Li; Wei Feng; Yifang Ping; Lu Zheng; Shiwu Dong; Yi Wu (Tissue and Cell, 2026)

Bicarbonate-driven enhancement of PGPR-assisted phytoremediation for Cu-contaminated soil through plant-microbiome interactions - Ping Wang; Yixuan Lü; Wenxuan Li; Yang Zhao; Zhiman Li; Xingke Yang; Yuankai Yang; Huijun Guan; Yixin Feng; Lixue Zheng; Ke Chen; Tianlong Hao; et al. (Rhizosphere, 2026)

Green synchronous fluorescence spectroscopy using non-carcinogenic standard: Rapid determination of carcinogenic polycyclic aromatic hydrocarbons in dairy products - Yi-Han Guo; Jia-Rong He; Jia-Wen Wei; Hong-Jun Liu; Jia-Lin Li; Ping-Ping Wu; Gaofeng Zheng; He-Dong Luo; Na Li; Yao-Qun Li (Food Control, 2026)

Efficient antibiotic degradation by concentrated solar activation of trichloroisocyanuric acid: The role of triplet-state-mediated singlet oxygen generation - Yue Yang; Li Tang; Kun Chen; Ping Chen; Yixun Zheng; Bingbing Liu; Jin Wu; Shimin Zhou; Yongpeng Zhang; Yuxin Xian; Wenying Lv; Guoguang Liu (Chemical Engineering Journal, 2026)

Functionalized biochar loaded with plant growth-promoting Enterobacter sp. TK: A bifunctional material for cadmium immobilization and maize-assisted phytoremediation - Xingke Yang; Wenxuan Li; Yuankai Yang; Yixuan Lü; Yang Zhao; Ke Chen; Lixue Zheng; Huijun Guan; Yixin Feng; Ping Wang; Tianlong Hao; Chunfeng Guan (Chemical Engineering Journal, 2026)

Surface coordination-induced heterogeneous nucleation of hierarchical coatings enabling pyrolysis vapor-mediated post mineralization for adaptive protection - Chengliang Zhou; Yanli Liao; Yanlei Gao; Xin He; Ping Jiang; Xia Zheng; Suwen Yang; Xingong Li (Chemical Engineering Journal, 2026)

From serpentinization to carbonation: Petrological and geochemical constraints from an ophiolitic reaction profile - Hong-Da Zheng; Qing Xiong; Xiang Zhou; Biao Chang; Hong-Kun Dai; Hong-Zhu Cai; Li Wang; Yi-Cong Li; Long-Fei Xue; Ming Chen; Jian-Ping Zheng (Chemical Geology, 2026)

Mechanistic insights into sucralose immunotoxicology: Dose-related modulation of the gut-immune axis in food allergy - Wenyan Li; Qiang Shi; Yifan Nie; Zhongliang Wang; Shuangyan Zheng; Ping Tong; Jinyan Gao; Yong Wu; Hongbing Chen (Chemico-Biological Interactions, 2026)

Assessing cognitive impairment in epilepsy using Arterial spin-labeled (ASL) perfusion imaging - Qiuyan Chen; Jie Zhang; Rong Chen; Yameng Qin; Xu Wang; Qiang Liu; Zheng Yin; Ping Yang; Feng Rao; Longnan Wang; Mengyun Li; Yanzi Jin; et al. (Brain Imaging and Behavior, 2026)

Modeling and analysis of structural effects and detection characteristics for a new toroidal coil–excited lateral resistivity logging-while-drilling (LWD) tool - Ya-Ping Zheng; Wei Xu; Hao Li; Yong-Song Zheng; Wei-Ping Wu; Ze-Hua Yan; Xin Li; Min Liu (Applied Geophysics, 2026)

Quantitative evaluation method of dual laterolog for fracture parameters in carbonate reservoirs in the Sichuan Basin - Qiang Lai; Ben-Jian Zhang; Hang Zhang; Yu-Yu Wu; Wei Xu; Jun Tang; Li Shen; Ya-Ping Zheng (Applied Geophysics, 2026)

Chloride ions-assisted high-efficiency natural seawater splitting enabled by noble-metal-free MnOx(OH)y/GaN nanowires - Yumeng Li; Liang Qiu; Xiantong Zheng; Lin Yao; Muhammad Salman Nasir; Zijian Huang; Ying Li; Yixin Li; Ding Wang; Wenxing Yang; Jianyang Zang; Ping Wang; et al. (Science Bulletin, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Combined effects of microplastics and Pb on soil-tobacco systems revealed by soil microbiomics and metabolomics - Rong ZHAO; Zeyu ZUO; Ping CONG; Haibin LI; Mingwei LI; Yanna ZHAO; Fang ZUO; Jiao SUN; Yuhuan SUN; Guangjian XU; Xuebo ZHENG; Fayuan WANG (Pedosphere, 2026)

Comprehensive life-cycle assessment of a hybrid renewable energy system–powered decentralized sewage treatment system in cold and rural Inner Mongolia - Shangbin Ma; Ping Miao; Shugang Guo; Yaoting Hu; Hongli Ma; Pengyu Li; Pengfei Cao; Dawen Gao; Jing Luo; Jianguo Liu; Tianlong Zheng (Journal of Water Process Engineering, 2026)

Zeolite-assisted Ga0.8V0.2Ox oxygen carriers boost propane dehydrogenation via chemical looping - Bo Chen; Yuhao Wang; Ping Jin; Hua Wang; Kongzhai Li; Aimin Zhang; Yane Zheng (Fuel, 2026)

Dynamic changes, flavor contributions, and enzymatic transformation mechanisms of phenolic acids during black tea processing - Anan Xu; Shanshan Wang; Qianhuang Xiao; Sixu Li; Zheng Tu; Meng Tao; Yanyan Cao; Qinwei Guo; Ping Xu; Zhengquan Liu (Food Chemistry, 2026)

TRPV4-mediated mechanotransduction governs surface topography-induced bone formation via macrophage-osteoclast axis - Jingqi Wu; Jiayi Gu; Ping He; Yuxiao Liu; Jingrong Chen; Lixin Yang; Wei Lei; Tong-Chuan He; Joost D. de Bruijn; Liwen Zheng; Hongmei Zhang; Huipin Yuan; et al. (Chemical Engineering Journal, 2026)

Evolution of anammox granular sludge performance during long-term preservation: Insights from double exponential kinetics - Chao Pan; Leiyan Guo; Dongdong Xu; Junwei Wu; Wenji Li; Wenda Chen; Changyong Wu; Shuang Pei; Ping Zheng; Meng Zhang (Bioresource Technology, 2026)

Characterizing brain structural and functional abnormalities in borderline personality disorder by seed-based d mapping approach - Wanru Qiu; Sen Li; Aoxue Zhang; Hao Yu; Jian Cui; Yinghong Xu; Liangliang Ping; Hao Zheng; Chunyu Dong; Kun Li; Cong Zhou (Brain Imaging and Behavior, 2026)

Research on tunnel construction quality control based on blockchain technology and Bayesian networks - Li-ping Cai; Qiaona Gong; Feng Jiang; Mingzhan Yuan; Zhiyong Xiao; Shuai Zhang; Chengcheng Zheng; Yue Wu (Applied Geophysics, 2026)

Chemical speciation, source apportionment, and pollution assessment of phosphorus in sediments from typical urban lakes in Southern China - Tianning Li; Linsen Tang; Huiyang Qiu; Fangwen Zheng; Ping Liu; Jinfu Liu (Environmental Monitoring and Assessment, 2026)

Exploring contributions and responses of microbial quantity and diversity to coastal seasonal hypoxia - Guihao Li; Jiarong Hu; Pengfei Zheng; Ping Zhu; Yaping Wang; Songbao Zou; Xiaoli Zhang; Eleni Gentekaki; Song Sun; Aolin Zhu; Jun Gong (Marine Pollution Bulletin, 2026)

Shift of nitrogen metabolism drives the evolution of multidrug resistance in wastewater microbiomes under long-term fluoride stress - Yun-Tian He; Fei Wang; Shu-Yu Yu; Chen-Xin Xie; Li Yuan; Zheng-Hao Li; Guo-Ping Sheng (Water Research, 2026)

Pancancer pro-angiogenic atlas unravels tumor-educated pericyte-augmented anti-angiogenic resistance - Yongqiang Zheng; Hui Sun; Zhe Fu; Haojie Chen; Guangyao Cai; Xin Huang; Yi-Qian Pan; Kai Yu; Ping Chen; Zhuoran Liang; Junteng Li; Jiamin Hu; et al. (Science Bulletin, 2026)

Community traits and assembly mechanisms of comammox Nitrospira across maize, rice, and forest ecosystems in Eastern China - Xiang Li; Mingmei Lu; Yarui Shi; Tengyu Feng; Xiaoting Zheng; Ping Liu; Ruixian Yang; Kesheng Zhang; Xuesong Luo (Journal of Soils and Sediments, 2026)

Structural and dynamic insights into SPDT for phosphorus allocation in rice - Haitao He; Yan Liu; Jie Zhang; Xiaofeng Zheng; Lihuan Jiang; Zhangmeng Du; Jiaqi Zuo; Shuo Cao; Xuemei Peng; Zhiwen Zheng; Kun Li; Cuicui Shen; et al. (Science China Life Sciences, 2026)

Non-equilibrium criticality-enhanced quantum sensing with superconducting qubits - Hao Li; Yaoling Yang; Yun-Hao Shi; Zheng-An Wang; Ziting Wang; Jintao Li; Yipeng Zhang; Kui Zhao; Yueshan Xu; Cheng-Lin Deng; Yu Liu; Wei-Guo Ma; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Coupling between mobile genetic elements and potential sulfur cycling microorganisms is associated with antibiotic resistance gene distribution in coastal sediments - Li Chen; Diantao Ping; Danyu Zheng; Shan Zhou; Chaoyue Zhang; Qi Chen; Xiaohui Wang; Xuri Dong; Lixin Zhu (Journal of Environmental Chemical Engineering, 2026)

In vitro simulated digestion of Ganoderma lucidum proteoglycan and its effects on gut microbiota in type 2 diabetic rats - Qianqian Zhang; Xinru Zheng; Jieying Chen; Ying Zhang; Jiaqi Li; Yingxin Wang; Yanna Pan; Fanzhen Yu; Zeng Zhang; Hongjie Yang; Yanming He; Ping Zhou (Food Bioscience, 2026)

TGase-induced WPI-GA microgels for stabilized HIPEs and encapsulation probiotics with enhanced thermal stability and gastrointestinal survival - Yaxin Yin; Yingnan Zou; Chin Ping Tan; Deyang Li; Xiaojiao Zheng; Daodong Pan; Maolin Tu (Food Hydrocolloids, 2026)

Based on the “biotin-streptavidin” system to construct exosome- linked hydrogel for promoting healing of chronic wounds in obesity by regulating the NF-κB pathway - Lingxiang Sun; Wenze Han; Yilin Ping; Xi Chen; Xuedong Deng; Zheng Wang; Jingjing Deng; Jian Zhou; Tingting Wu; Yifan Zhao; Xiuping Wu; Bing Li (Chemical Engineering Journal, 2026)

Hematopoiesis could be improved by correcting aberrant bone marrow macrophages polarization in aplastic anemia patients - Chen-Yuan Li; Dan-Dan Chen; Xin-Yan Zhang; Shu-Qian Tang; Meng-Zhu Shen; Ya-Ting Yu; Zhi-Wei Zhang; Zheng-Li Xu; Yuan-Yuan Zhang; Jin-Song Jia; Lan-Ping Xu; Yu Wang; et al. (Science China Life Sciences, 2026)

Does a positive culture correlate with the volume of synovial fluid inoculated into blood culture bottles for the diagnosis of periprosthetic joint infection? - Jia-Zheng Xu; Zhi-Sen Gao; Zhen Zhang; Ping Song; Wei Chai; Rui Li (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

A Novel Wave-Absorbing Support System for Mitigating Rock Burst in Deep-Buried Hard Rock Tunnels - Yue-Mao Zhao; Zheng-Chen Ge; Ben-Guo He; Cheng-Xiang Yang; Xing-Long Li; Xiao-Jun Yu; De-Xian Li; Yong-Ping Liu (Rock Mechanics and Rock Engineering, 2026)

Microscopic Hydraulic–Mechanical Coupling Fracturing Behavior and Failure Mechanisms of Reservoir Rocks - Zhi Zhao; Zhi-Hong Li; Yun-Gang Duan; Liang-Fu Xie; Zheng Li; Guo-Feng Yu; Xiao-Ping Zhou (Rock Mechanics and Rock Engineering, 2026)

Rapid evaluation of the comprehensive quality of paeonol/cyclodextrin supramolecular complexes using CASSA based on near-infrared spectroscopy combined with artificial intelligence - Bo-yao Zhang; Xin-li Li; Cheng Qian; Si-min Xue; Zhi-tong Zhang; Si-yi Liu; Guo Zhang; Guo-ping Peng; Ning Ding; Yun-feng Zheng (Molecular Diversity, 2026)

Impact of macroalgae farming on the carbonate system and biogenic sulfur dynamics in Sansha Bay, China - Ping Wang; Zheng-Xin Hu; Yu Xin; Bing-Han Li; Lu Han; Shu-Hang Dong; Chun-Ying Liu; Tao Liu; Jing-Wen Hu; Jiang-Chen Gong; Gui-Peng Yang (Marine Pollution Bulletin, 2026)

A multicomponent Fc-fused subunit vaccine induces cross-protective immunity against porcine reproductive and respiratory syndrome virus QYYZ-like and NADC30-like strains - Linxing Tian; Zhengdan Lin; Mengxi Pan; Yanwen Wen; Mingxing Lu; Shudan Liu; Chao Zhang; Zhenxiang Rong; Jiahui Ma; Ruiqu Zhou; Nan Cao; Xinghua Chen; et al. (Veterinary Microbiology, 2026)

Decoding the molecular mechanisms of metaplast transformation in coal pyrolysis - Zhao Lei; Chuandong Zheng; Qin Pei; Qiang Ling; Xiangchun Liu; Xiaodong Li; Ping Cui (Fuel, 2026)

Unraveling grain quality in cereals: development, heat stress, and molecular mechanisms - Ping Li; Zheng Li; Jiangyue Su; Yanjie Lv; Shuhua Liao; Pu Wang; Shoubing Huang (Food Chemistry, 2026)

A critical review on abiotic geologic hydrogen generation: Mechanisms and controls - Qingxia Zheng; Ruibo Wu; Ping Li; Zhe Ding; Wentao Zhang; Huiyang Mei; Weichao Zhang; Jianjun Liang; Qiaohui Fan (Earth-Science Reviews, 2026)

Ultra-sensitive and highly stable position-pressure dual-modal flexible sensor for human-computer interaction - Jiufei Luo; Xuejun Ma; Xiaolin Zheng; Yuxin Li; Zhidan Luo; Yi Lu; Ping-an Yang (Chemical Engineering Journal, 2026)

Quantifying the decoupling of pollution magnitude and geochemical signatures in livestock manure: a novel geometric fingerprint approach - Qiu Cheng; Yi Jijun; Fan Shoubo; Du Qiuxiang; Li Qianglin; Wang Liting; Liang Qingling; Zheng Guihua; Xiong Ping (Environmental Monitoring and Assessment, 2026)

Comparative analysis of chemical composition in Zanthoxylum avicennae leaves and branches based on UPLC-Q-Orbitrap HRMS, and evaluation of their antioxidant activities - Liang-Qian Zhang; Yuan Tian; Li-Ping Dai; Xing-Er Ye; Yi-Qin Zheng; Nan-Chen Lai; Wei Dai; Qi Wang (Natural Product Research, 2026)

Eocene topography differentiation between the western and eastern North China Craton: Insights from multi-method chronometry in the northern Taihangshan Mountains - Li-Xia Feng; Ping-Ping Li; Zeng-Zhen Wang; Rong Ren; Lin Wu; Bo Zheng; Bo Liu; Jian-Qing Ji; Bao-Fu Han (Tectonophysics, 2026)

Impacts of rainfall runoff on algal community in a humid region reservoir riverine zone - Cunli Li; Miao Yang; Aiju You; Guangwei Zhu; Ping Zhang; Qiaoxi Zheng; Mengyuan Zhu; Linxing Tu; Hongqing Zhang; Lei Fu; Bin Wang; Jinwen Hu; et al. (Journal of Environmental Chemical Engineering, 2026)

Influence of free surface on microwave-induced rock fracturing: An experimental and numerical study - Yanlong Zheng; Ziqiang Su; Gaofeng Zhao; Ping Che; Jianchun Li (International Journal of Rock Mechanics and Mining Sciences, 2026)

Lactic acid bacteria diversity in traditional fermented dairy products: Seasonal influences and microbial interactions - Jie Zhao; Yangbo Jiao; Ping Du; Dan Wang; Yu Li; Xin Su; Shuaili Zheng; Liang Zhou; Jiaqi Xie; Jie Yu (Food Bioscience, 2026)

Zircon thermal annealing ages determine a late Eocene birth for the First Bend of the Yangtze River - Yang Zhang; Rui Li; Guang-Yan Zhou; David Chew; Jian-Ping Zheng; Qing Xiong; Wei Wang (Earth and Planetary Science Letters, 2026)

Plant–microbe interactions underpin contrasting enzymatic responses to flooding intensity variation in the cascade reservoir riparian areas - Nan-ping Wu; Shan-ze Li; Kailang Yin; Yu-chun Wang; Zheng Sun; Xuming Xu; Qingkong Chen; Yufei Bao; Jie Wen (CATENA, 2026)

The Spatiotemporal Evolution of Sugarcane Growth Based on Remote Sensing Monitoring and its Influence Factors Detection Regression Analysis in Guangxi, China - Yun-chuan Yang; Chang-zheng Wei; Xin-chang Xie; Li-ping Liao; Li-qing Liang; Zong-heng Li; Meng-dong He; Chong-xun Mo; Xun-gui Li; Gui-kai Sun (Sugar Tech, 2026)

Mantle dunites archive multistage melt metasomatism under a fossil slow-ultraslow spreading center: an example from the Tibetan Xigaze ophiolite - Li Wang; Qing Xiong; Hong-Kun Dai; Xiang Zhou; Hong-Da Zheng; Hao-Qin Sun; Yi-Cong Li; Long-Fei Xue; Alessio Sanfilippo; Valentin Basch; Jian-Ping Zheng (Contributions to Mineralogy and Petrology, 2026)

DMSN@AuNPs-enhanced QCM immunosensor array for non-invasive and highly sensitive detection of Cyfra21-1 in saliva - Xiaojing Zhang; Hongyang Guo; Li Sin Wong; Hangming Xiong; Liubing Kong; Guangqing Ren; Yanjie Hu; Yong Zhou; Shuaike Zheng; Li Zhang; K. Jimmy Hsia; Hao Wan; et al. (Analytica Chimica Acta, 2026)

The presence of native semi-fossorial herbivores enhances the coupling between species and functional diversity in alpine meadows - Yuan Yuan Duan; Kun Qin; Yu Chen; Jie Li; Ni Wang; Xiao Dan Sun; Yan Ping Bai; Lin Han Li; Zheng Gang Guo (Agriculture, Ecosystems & Environment, 2026)

A Framework for Extending Rock Strength Criteria to Anisotropy - Huai-Sheng Xu; Shao-Jun Li; Ding-Ping Xu; Min-Zong Zheng; Quan Jiang; Guang-Liang Feng; Liu Liu (Rock Mechanics and Rock Engineering, 2026)

MTA-SM: Multi-machine path planning and time-window scheduling joint optimization method in hilly safflower harvesting - Liwei Yang; Ping Li; Zhongshuo Ding; Chao Sun; Fei Chen; Yijiang Zheng; Yun Ge (Computers and Electronics in Agriculture, 2026)

Raccoon dog parvovirus NS1 protein antagonizes type I interferon signaling by promoting selective autophagic degradation of IRF3 - Wen-yu Cao; Rui-qi Wang; Jin-yang Zheng; Ping Ma; Bo Hu; Cheng-qi Zhang; Ya-jie Sun; Jia-jia Liu; Ding-rui Guo; Zi-han Zhao; Xin Cao; Xue Bai; et al. (Veterinary Microbiology, 2026)

Who is the best allogeneic hematopoietic stem cell transplant donor for severe aplastic anemia? Data from the Chinese Bone Marrow Transplantation Registry Group (CBMTRG) - Zheng-Li Xu; Lan-Ping Xu; Shun-Qing Wang; De-Pei Wu; Xi Zhang; Su-Jun Gao; Ling-Hui Xia; Rui Xi; Jian-Min Yang; Qi-Fa Liu; Ming Jiang; Xiao-Sheng Fang; et al. (Science Bulletin, 2026)

The overlooked role of nitrate in mediating electron transfer and enhancing reactive species generation in TiO2 photocatalytic water remediation - Zheng Hu; Jin Wu; Lingzhi Shen; Zili Lin; Zihong Xu; Zhenjun Xiao; Zheng Fang; Daguang Li; Ping Chen; Wenying Lv; Guoguang Liu (Process Safety and Environmental Protection, 2026)

Posttranslational regulation of TOR kinase activity controls resource allocation between plant growth and immunity in Arabidopsis - Jianwei Li; Ran Wang; Chenying Li; Xijie Guo; Qinghong Li; Zhixuan Wu; Shanshan Zeng; Fan Qi; Yuchen Wang; Zhiyi Jia; Weiwei Yu; Zeming Huang; et al. (Molecular Plant, 2026)

Warming shifts priming effects from negative to positive: New insights into carbon cycling in aquaculture waters - Ping Jiang; Xinyi Wang; Xuedong Zheng; Hao Yang; Y. Jun Xu; Yiwen Zhang; Yang Wang; Yifei Zhang; Wenjun Yang; Chen Ye; Siyue Li (Journal of Hydrology, 2026)

Performance assessment of an electrokinetic barrier-aquifer system using a dual-domain solute transport model - Jian-Ping Li; Zhang-Long Chen; Shi-Jin Feng; Wen Zheng; Gang Wang (Journal of Hydrology, 2026)

In-situ reactivation of the catalyst for hydrodeoxygenation of bio-oil to biofuel by coupling the self-rotation and revolution of catalysts in the swirling flow - Yao Zhang; Zheng-hao Yang; Yu-long Chang; Jian-ping Li; Bang-da Wang; Zi-heng Jin; Liang Ma; Xia Jiang; Hua-lin Wang (Journal of Cleaner Production, 2026)

Metabolic microenvironment self-adaptive cobalt-based hydrogel dressing sustains spatiotemporal ROS generation for chronic diabetic wound repair - Ping Li; Lu Yang; Yifei Song; Shanshan Li; Wenhong Zheng; Mengteng Tang; Guoyang Xu; Wei Feng; Li-Li Li (Chemical Engineering Journal, 2026)

Clostridium dalinum: A Novel Lactic Acid Bacterium with Excellent Antioxidant and Anti-inflammatory Functions Through NF-κB, Keap1-Nrf2-ARE Signaling Pathways - Zheng-Qiang Li; Rui Li; Wei Deng; Rui An; Ping Ma; Jun Li; Rong She; Xiao-Yan Yang; Xu Yang; Wen Xiao (Probiotics and Antimicrobial Proteins, 2026)

Unraveling the carcinogenic mechanisms of benzo[a]pyrene in prostate cancer: a multi-omics approach - Jiansheng Xiao; Handa Zheng; Guohao Wu; Ping Li; Qiyu Zhong; Qiao Lv; Jiahui Chen; Caiyong Lai; Dongming Ye (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Establishment of an embryonic cell line of Grapholita molesta (Lepidoptera: Tortricidae) and in vitro replication of Cydia pomonella granulovirus in it - Gui-Ling Zheng; Yu-Fan Yao; Xiao-Yu Zhang; Qian-Long Yu; Jie Li; Yi-Ping Li; Dong Chu; Chang-You Li (In Vitro Cellular & Developmental Biology - Animal, 2026)

Transgenerational Effects of Elevated Temperature on Life History and Lambda-Cyhalothrin Sensitivity in Cydia Pomonella - Kang-Wu Zheng; Zi-Han Wei; Zi-Nan Xia; Bo-Kun Wang; Ping Gao; Yu-Ting Li; Xue-Qing Yang (Neotropical Entomology, 2026)

Rapid temperature field prediction in natural product extraction - Yequan Yan; Yang Yu; Qilong Xue; Jingxuan Zhang; Jiping Pang; Ping Li; Yehan Hou; Lei Wang; Zheng Li (Journal of Food Engineering, 2026)

Microbial dynamics of wild and cultured Sinularia flexibilis: Implications for coral aquaculture - Li-Guo Zheng; Kuei-Hung Lai; Ping-Jyun Sung; You-Ying Chen; Jimmy Kuo; Jui-Hsin Su; Mohamed El-Shazly (Aquaculture, 2026)

Multi-phase distribution and predictive modeling of polycyclic aromatic hydrocarbons in the East China marginal seas - Zishan Diao; Yiteng Sun; Minggang Zheng; Xue Zhang; Wenpeng Li; Xianyin Ping; Bin Hui; Fanping Zhu; Jing Wang; Shuguang Wang; Xiaohan Zhang; Xianzheng Yuan (Water Research, 2026)

Reactive transport and retention of Cd, Pb, and Zn under coexisting multimetal-xanthate conditions in porous media - Bowen Luo; Kouping Chen; Xianwu Zheng; Jichun Wu; Ping Li; Huali Chen (Water Research, 2026)

Mechanical resistance of higher EPS contents in larger granules restricts anammox bacterial growth - Dongdong Xu; Tao Liu; Jiahui Fan; Wenda Chen; Yiyu Li; Meng Zhang; Ping Zheng; Jianhua Guo (Water Research, 2026)

Environmental co-exposure to roxarsone and heavy metals drives bacterial antibiotic multidrug resistance via genetic and phenotypic adaptations - Qian-He Liu; Li Yuan; Zheng-Hao Li; Kenneth Mei Yee Leung; Guo-Ping Sheng (Water Research, 2026)

Experimental and numerical study of a novel slope-type sliding isolation system for seismic protection of electrical equipment - Wanchen Meng; Yanhui Liu; Wenzhi Zheng; Ping Tan; Hao Li; Dengjie Zhu; Fubao Guo (Soil Dynamics and Earthquake Engineering, 2026)

Late Cretaceous-Early Eocene rapid exhumation in the Basu, eastern Tibet: Implications for the growth of the proto-Tibetan Plateau - Xunzhang Zhu; Dongliang Liu; Haibing Li; Jinjiang Zhang; Marie-Luce Chevalier; Jiawei Pan; Zhongbao Zhao; Shenqiang Chen; Yihu Zhang; Ping Wang; Chao Li; Fucai Liu; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Effects of root exudates analogues of Robinia pseudoacacia L. on water retention capacity and capillary rise in loess: An experimental study - Tao Xiao; Ping Li; Sai K. Vanapalli; Zixuan Zheng; Guanzhou Ren; Hui Zhai; Kai Han; Jiading Wang (Journal of Hydrology, 2026)

Unveiling the interaction of uranyl and arsenate: Insights into the formation mechanisms of uranyl arsenate minerals - Penggang Li; Ping Zhang; Zhihui Yang; Lin Yu; Junhao Zheng; Mengying Si; Qi Liao; Feiping Zhao; Weichun Yang (Journal of Environmental Sciences, 2026)

Isomeric halide engineering of self-assembled hole-selective layers for efficient indoor perovskite photovoltaics - Zhong-En Shi; Yi-Ting Hong; Cheng-Chieh Lu; Po-Cheng Shih; Shih-I Lu; Hsiao-Chi Hsieh; Sie-Rong Li; Yu-Che Lin; Zheng-Xuan Cai; Yan-Duo Lin; Chih-Ping Chen (Chemical Engineering Journal, 2026)

Deciphering mechanisms of stress-induced metabolic shifts in Corynebacterium glutamicum by transcriptomics and contextualised modelling - Xiaomeng Ni; Ning Gao; Wenjing Hu; Xuan Guo; Jiao Liu; Jiuzhou Chen; Ningyun Cai; Xiaojia Zhao; Jibin Sun; Yu Li; Yan Zhu; Ping Zheng (Bioresource Technology, 2026)

Genetic context-dependent regulation of FlbE enhances morphology modulation and citric acid production in Aspergillus niger - Meiling Chen; Xiaomei Zheng; Peng Du; Xiaomeng Ni; Zhimin Li; Ping Zheng; Jibin Sun (Bioresource Technology, 2026)

Mapping the spatial variability of hydrogen and oxygen isotopic compositions in Chinese lake water: Patterns and drivers - Hu Liu; Ping Zhang; Huanye Wang; Zhoufeng Wang; Zhonghui Liu; Meng Xing; Zheng Wang; Yixuan Li; Yunning Cao; Xiangzhong Li; Weiguo Liu (Science China Earth Sciences, 2026)

Oral Administrations of Short-Chain Fatty Acids or Probiotics Extend the Survival Times and Mitigate the Neuropathological Damages in the Scrapie-Infected Hamsters - Yuan Wang; Dong-Lin Liang; Run-Dong Cao; Ruhan A.; Jia-Feng Zeng; Bing Xu; Ju-Zheng Li; Wei-Wei Zhang; Li-Ping Gao; Kang Xiao; Xiao-Ping Dong; Qi Shi (Molecular Neurobiology, 2026)

Analysis of clinical characteristics and prognostic factors in AIDS complicated by cryptococcal meningitis - Yanlan Liang; Xiyang Dong; Yong Deng; Zhende Lin; Caixia Zheng; Jiaxuan Li; Yijie Lin; Huatang Zhang; Xing Wang; Wenwu Lin; Wencong Hong; Su Zhang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Groundwater depletion in China’s Granary: The unintended consequences of cropping pattern shifts - Yiqun Shang; Jinwei Dong; Ping Fu; Nanshan You; Xi Zhang; Yuanyuan Di; Yan Zhou; Xi Chen; Zhichao Li; Xinqi Zheng (Journal of Hydrology, 2025)

Ni/Al-based additives for deep desulfurization of high-sulfur coal: Cooperative desulfurization and sulfur migration behavior - Zheng-Zhi Zhang; Zhan-Ku Li; Jing-Tao Yao; Mu-Xin Liu; Jing-Chong Yan; Wei-Dong Zhang; Zhi-Cai Wang; Zhi-Ping Lei; Shi-Biao Ren; Heng-Fu Shui (Journal of Environmental Chemical Engineering, 2025)

A transition in aquaculture systems: Industrial systems substantially reduce CO2 and CH4 diffusion versus traditional earthen ponds - Yifei Zhang; Ping Yang; Yiwen Zhang; Jiayu Zhao; Zhuangpeng Zheng; Siyue Li (Environmental Research, 2025)

Mechanically robust and rapidly self-recovering hyaluronic acid-based conductive hydrogels via fully physical double-network crosslinking for sensitive strain sensors - Ye-Xiong Huang; Mei-Dan Luo; Dewei Ye; Jinmin Li; Ku Shu; Xian-Ping Chen; Kai Zheng (Chemical Engineering Journal, 2025)

IFNGR1, IRF8 genetic polymorphisms modulate the susceptibility of non-tuberculous mycobacteria pulmonary disease and influence the patients’ treatment outcomes and immune status - Li-ping Cheng; Zhi-bin Liu; Lei Wang; Jie Cao; Qing-rong Qu; Hai Lou; Xiao-na Shen; Juan Yang; Yuanyuan Yu; Rui Juan Zheng; Wei Sha; Qin Sun (Inflammation Research, 2025)

Exploration of new azole derivatives containing ethanolamine moiety as anti-UC agents by inhibiting NF-κB/MAPK pathways - Ming-Qian Ju; Zheng-Xiao Huang; Qing-Yan Mo; Shuai Liu; Dong-Xue Wang; Yan-Ping Li; Chun-Ping Wan; Ze-Wei Mao (Molecular Diversity, 2025)

Plastispheres as unique niches for promoting turnover of dissolved organic matter in aquatic environments - Yan-Jun Liu; Zheng-Hao Li; Yan-Yun Hu; Jia-Heng Zhao; Li Yuan; Guo-Ping Sheng (Water Research, 2025)

Metagenome-assembled genomes reveal Pseudogracilibacillus amylolyticus sp. nov., a functional uncultured microorganism in high-temperature Daqu - Ai-Ping Lv; Ying-Han; Bao-Zhu Fang; Guo-Zheng Wang; Man-Chun Liu; Bing-Ru Bian; Zhuo-Huan Zheng; Kai Li; Bing-Yu Li; Jian-Yu Jiao; Lan Liu; Lei Dong; et al. (Systematic and Applied Microbiology, 2025)

Chaotic circuit-enhanced electrokinetic leaching of ionic rare earth ores with (NH4)2SO4-MgSO4 compound salt - Yu Wan; Anqi Li; Xin Zhang; Shiliang Gu; Guocan Zheng; Qian Zhan; Jinjing Tang; Changyuan Tao; Jinhui Li; Ping Li; Zuohua Liu (Journal of Cleaner Production, 2025)

Ecological restoration in plateau pika-disturbed alpine meadows: Soil-microbe-enzyme stoichiometry and microbial adaptations during vegetation recovery of bare patches - Yuan Yuan Duan; Huan Yang; Jie Li; Ni Wang; Tong Wu; Xiao Dan Sun; Yan Ping Bai; Lin Han Li; Zheng Gang Guo (Journal of Environmental Management, 2025)

miR-927 links nutrient signals and 20-hydroxyecdysone regulation and mediates oviposition in Bactrocera dorsalis - Tong-Jun Jin; Zheng-Yang Wang; Qian-Ping Xie; Li-Yuan Zheng; Guy Smagghe; Jin-Jun Wang; Qiang Zhang; Wei Dou (Insect Biochemistry and Molecular Biology, 2025)

High-throughput discrimination of chlorogenic acid isomers in Lonicerae Japonicae Flos by U-shaped mobility analyzer-mass spectrometer - Meng Ding; Luwei Zheng; Ao Zhou; Yuling Li; Yiming Wang; Xiaoqiang Zhang; Wenjian Sun; Wen Gao; Ping Li; Hua Yang (Food Chemistry, 2025)

Substrate stiffness modulates the behavior of muscle stem cells of large yellow croaker through driving cellular mechanosensing - Xiaomeng Yan; Zhaojie Li; Ningyang Li; Ping Dong; Hongwei Zheng; Changhu Xue (Food Bioscience, 2025)

Platinum-copper nanocubezyme facilitate spinal cord recovery via synchronously alleviating oxidative stress and mitigating BNIP3-mediated mitochondrial dysfunction - Xiangge Liu; Cheng Peng; Huiyi Yang; Jiajun Deng; Ping Wu; Yongchun Xiao; Li Wan; Ke Wang; Guowei Zhang; Hua Yang; Jianyu Zou; Judun Zheng; et al. (Chemical Engineering Journal, 2025)

[3 + 2 + 1] iridium(III) complexes for high-efficiency saturated red organic light-emitting diodes - Ping Chen; Qingwu Wu; Gui-Yan Yang; Qifei Xie; Sheng Yu; Ming-Yu Teng; Huabo Han; Guo-Li Huang; You-Xuan Zheng; Guangzhao Lu (Chemical Engineering Journal, 2025)

Effects of plateau pika disturbance on soil net nitrogen mineralization from small to large scales in alpine meadows - Yuan Yuan Duan; Huan Yang; Jie Li; Ni Wang; Tong Wu; Xiao Dan Sun; Yan Ping Bai; Lin Han Li; Zheng Gang Guo (CATENA, 2025)

The role of TLR4/NF-kB signaling axis in pneumonia: from molecular mechanisms to regulation by phytochemicals - Jun Yin; Jianxiang Huang; Ping Zhou; Linwei Li; Qin Zheng; Hong Fu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Synthesis and antitumor evaluation of oleanolic acid acylhydrazone derivatives - Juan Cai; Bo-Wen Pan; Liang-Liang Zheng; You-Ping Tian; Zhang-Chao Dong; Li-Juan Liu; Ting-Ting Feng; Ying Zhou; Xiong-Wei Liu; Yang Shi (Molecular Diversity, 2025)

Eco-intensified recovery of acetonitrile and ethanol from industrial wastewater via heat-integrated reactive pressure-swing distillation - Jian Zhai; Ting Li; Xueke Zheng; Qingbo Sun; Chunbo Hao; Xuefei Leng; Ping Zhao; Jinwen Li; Yuran Zhou (Process Safety and Environmental Protection, 2025)

Furofuran and tetrahydrofuran lignans from Lancea tibetica - Wenbo Li; Fuhua Zhu; Lu Tang; Jun Xu; Xiaoying Zhang; Zhicheng Duan; Wei Zhang; Ping Hai; Yongbiao Zheng; Haiqing Liu; Xia Li; Yanfang Su (Phytochemistry, 2025)

Discovery of a new 1-monoglyceride from Streptomyces albogriseolus JM128 symbiotic with Lendenfeldia sponge - Yun-Ting Zeng; Chia-Ching Liaw; Yu-Chi Lin; Su-Ying Chien; You-Ying Chen; Li-Guo Zheng; Chih-Yin Huang; Hsi-Wen Sun; Ping-Jyun Sung (Phytochemistry Letters, 2025)

Bimetallic cobalt-cerium loaded copper foam for enhanced paraxylene low-temperature catalytic oxidation: Mechanistic insights and role of oxygen vacancies - Chenyang Zhao; Huanhuan Wu; Guangfei Qu; Yongheng Yuan; Zheng Yuan; Guojun Liu; Zhishuncheng Li; Junyan Li; Yingying Cai; Ping Ning (Journal of Environmental Chemical Engineering, 2025)

Strengthened protonation and electrochemical behavior in Sr-doped LaMnO3/peroxymonosulfate system - Ping Liang; Qina Yang; Bolun Zhang; Jie Wang; Zhenhan Li; Xinxin Zhang; Hongguang Liu; Chi Zhang; Zheng Liu (Journal of Environmental Chemical Engineering, 2025)

In situ stabilization of antimony and arsenic in co-contaminated soil using organic matter-Fe/Mn (hydr)oxides colloids and their mineral phase transformation - Junhao Zheng; Lu Liu; Qi Li; Pengwei Zhao; Qi Liao; Qingzhu Li; Zhihui Yang; Mengying Si; Yang Ping; Hao Xu; Weichun Yang (Journal of Environmental Sciences, 2025)

Protein engineering and flow reactor design for anchored peptide-mediated continuous biocatalysis - Huan Li; Chun-Jiang Ma; Ya-Ting Gao; Qing-qing Zhou; Huan Chen; Feng Cheng; Ya-Ping Xue; Yu-Guo Zheng (Chemical Engineering Journal, 2025)

Cold crystallization-enabled permanent shape transformation in 4D-printed PLA/TPU composites for personalized wearable devices - Chuanru Zheng; Xi Li; Juan Tan; Anna Tan; Xiuchen Li; Hailiang Ni; Wenhao Yu; Yuefeng Bai; Ping Hu; Wei Min Huang; Hongmei Chen (Chemical Engineering Journal, 2025)

Targeting the clogging of anaerobic reactors in treating high calcium-containing wastewater: A unique perspective on the sludge bed embolism - Wenda Chen; Dongdong Xu; Wenji Li; Chao Pan; Leiyan Guo; Ping Zheng; Meng Zhang (Chemical Engineering Journal, 2025)

Targeted gene therapy for intracranial aneurysm using SOX17-CRISPRa - Dujie Xie; Yi Yuan; Panyao Long; Juan Huang; Mi Jiang; Yongzhong Tang; Yuanqiang Luo; Cancan Zhang; Ping Zheng; Liang Yang; Yiwei Chen; Xiaobo Li; et al. (Chemical Engineering Journal, 2025)

FOXM1 upregulation, promotes immune escape in gastric cancer through activation of Notch signaling pathway - Shangkun Du; Ping Li; Yabin Liu; Bindan Cai; Gang Li; Wenbin Wang; Rui Yan; Xiangkui Zheng; Tianliang Bai (Molecular and Cellular Biochemistry, 2025)

Rice-duck farming enhances phosphorus use and grain yield via altering soil phosphorus fractions in the Yangtze River Delta of eastern China - Hui Gao; Qingnan Chu; Xiangyu Liu; Liang Zheng; Shuhan Xu; Linkui Cao; Detian Li; Shuai Yin; Ping He; Chengrong Chen; Zhimin Sha (Agriculture, Ecosystems & Environment, 2025)

Molecular characterization of porcine reproductive and respiratory syndrome virus in Henan and Shanxi, China, during 2023–2024 - Tao Wang; Xuan-Ang Wang; Jia-Qi Zhang; Lan-Lan Zheng; Ping-Li Wang; Hong-Ying Chen; Shi-Jie Ma (Archives of Virology, 2025)

Transcriptome profiling of mRNA responding to inflammation in bovine mammary epithelial cells induced by lipopolysaccharide - Jin-peng Wang; Zheng-xing Wang; Bin-wu Bao; Yan-xia Li; Zhuo-ma Luoreng; Xing-ping Wang (Research in Veterinary Science, 2025)

AhR-mediated histone lactylation drives cellular senescence during benzo[a]pyrene-evoked chronic obstructive pulmonary disease - Li-Hong Chen; Jun-Ping Wei; Meng-Die Li; Xiu Lu; Yi-Cheng Ma; Yu Wang; Ling Zheng; Jun Fei; Wei Cao; De-Xiang Xu; Jin Yang; Hui Zhao; et al. (Journal of Hazardous Materials, 2025)

A novel damping adaptive pendulum isolation system for seismic resilience enhancement of continuous bridges - Wenzhi Zheng; Junliang Chen; Hao Wang; Ping Tan; Jian Li; Siqi Wang (Engineering Structures, 2025)

Unraveling the effect of sorbitol on Cu-based catalysts for the continuous hydrogenation of CO2-derived ethylene carbonate to methanol and ethylene glycol - Tong-Yang Song; Ji-Zheng Zhang; Jun He; Xian-Lang Chen; Xin-Yuan Huang; Ai-Ping Jia; Xiaohong Li; Rong-Rong Li; Ji-Qing Lu (Chemical Engineering Journal, 2025)

Sulfide-based autotrophic denitrification process with efficient nitrogen removal under high salinity stress: Threshold behaviors and recovery enhanced via glutamate supplementation - Kaiyu Zhang; Qaisar Mahmood; Jiayi Lv; Na Liang; Xiaopeng Zhu; Jinye Li; Jing Cai; Ping Zheng (Bioresource Technology, 2025)

Transcriptome and Metabolome Conjoint Analysis Revealed that PaGLK Affects Photosynthesis and Composition of Root Exudates in Poplar - Xiang-dong Bai; Yu Zheng; Li Cao; Wei Wang; Jing Jiang; Qi-bin Yu; Chuan-ping Yang; Gui-feng Liu (Plant Molecular Biology Reporter, 2025)

Chinese Tuina ameliorates muscle damage by regulating endoplasmic reticulum stress and autophagy in a rat model of skeletal muscle contusion - Hai-chao Liu; Hao-ming Zhu; Ming Li; Bo-rui Chen; Zheng-yu Yang; Yu Wang; Shi-zhong Wang; Shao-qing Chen; Jian-ping Lin (Tissue and Cell, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

BarleyOmics: A comprehensive multi-omics database of barley - Junheng Zhao; Shanggeng Xie; Chenyang Zhang; Zengjie Hu; Xiangqian Lu; Nannan Zheng; Yujie Fu; Jie Yao; Ping Zhou; Danyin Huang; Zhizhong Zhang; Mengdi Li; et al. (Molecular Plant, 2025)

Ultrafast piezoresistive flexible pressure sensor for vibration and sound detection with a bandwidth over 20 kHz - Yangyang Yan; Jinzhi Zheng; Qingrong Zhang; Yanling Li; Guofu Li; Zhongkui Zhang; Ping Wang; Wenjun Wu; Jingyu Zhai; Yang Xu (Chemical Engineering Journal, 2025)

High-quality reference genome and population analysis of allotetraploid Elymus sibiricus provide insight into genome origin and environmental adaptations to the Qinghai-Tibetan Plateau - Xinrui Li; Changbing Zhang; Lili Wang; Gai Huang; Daxu Li; Changmian Ji; Zujun Yang; Minghong You; Lijun Yan; Lili Chen; Wenlong Gou; Xiong Lei; et al. (Science China Life Sciences, 2025)

Complete genome analysis of a novel phenui-like virus in Morus alba - Hanze Zheng; Yangwei Gao; Xiaodi Hu; Zhongtian Xu; Jian-Ping Chen; Yiyuan Li (Archives of Virology, 2025)

Leaf and Root Traits Show Contrasting Resource Exploitation Strategies, but Converge Along Elevation in the Hengduan Mountain Forests - Jie Song; Sebastian Seibold; Liang‐Liang Ma; Jia‐Yun Zou; Jie Liu; Ming‐Shu Zhu; Wei Zheng; Zhi‐Qiong Mo; Sheng‐Ping Ming; Jin Li; Kun Xu; De‐Zhu Li; et al. (Journal of Biogeography, 2025)
Aim The variations of leaf and root traits in communities are associated with above‐ and below‐ground resource exploitation strategies and are used to infer community assembly processes along environmental gradients. However, little is known about variations in leaf and root traits and their drivers along elevations in mountain forests. Location Yulong Mountain, southeastern Hengduan Mountains, Southwest China. Taxon Seed plants. Methods We measured six leaf traits and seven root traits across 47 woody species and collected environmental variables from forest plots along a 1200 m elevational gradient. We employed linear mixed models to examine how resource exploitation strategies (community‐weighted mean, CWM) and functional diversity (standardised effect size of RaoQ, SES.RaoQ) associated with leaf and root traits varied along elevations. Furthermore, we determined the relative effects of environmental variables on these metrics. Results We observed that the resource exploitation strategy of leaves shifted from an acquisitive to a conservative strategy (higher leaf carbon concentration) with increasing elevation. Conversely, root trait variation exhibited an opposite trend, shifting from a conservative to an acquisitive strategy (higher root branching intensity but lower root diameter and root tissue density) along elevations, potentially influenced by mycorrhizal interactions. We detected functional convergence for leaf and root traits across elevations, with a greater degree of functional convergence at high elevations. Leaf trait convergence was closely linked to soil nitrogen conditions, whereas root trait convergence was associated with soil organic carbon levels. Main Conclusions Our results highlight that the patterns of resource exploitation strategies along elevational gradients are decoupled for leaf and root traits, with distinct environmental factors shaping the convergence of root and leaf traits. We argue that forest communities in mountain ecosystems may modify their resource exploitation strategies and functional diversity through varying combinations of leaf and root traits to improve resilience to future global change.

Development and identification of porcine monoclonal antibodies against PEDV from single B cells - Xuan-ang Wang; Hong-xuan Li; Lan-Lan Zheng; Shi-jie Ma; Ping-Li Wang; Li Zhao; Hong-Ying Chen (Veterinary Immunology and Immunopathology, 2025)

In vivo and in vitro degradation and biological toxicity studies of polyesters with varying degradation rates - Ze-Yang Zhang; Wei-Zhen Zheng; Zhi-Chao Zhen; Xiao Li; Ping-Li Wang; Bo Lu; Xiu-bin Yang; Dan Huang; Jun-Hui Ji; Ge-Xia Wang (Journal of Hazardous Materials, 2025)

Microwave-induced strength reduction and weakening mechanisms of basic rocks - Zhongjun Ma; Xiaobao Zhao; Han Li; Hanwen Liu; Yangwei Long; Yanlong Zheng; Ping Che (International Journal of Rock Mechanics and Mining Sciences, 2025)

Flexural behavior of reinforced concrete beams subjected to natural corrosion in marine environment - Yang Liu; Wei-Ping Zhang; Chao Jiang; Feng Wu; Jun-Li Qiu; Rui-Lin Wang; Nai-Hao Zheng (Engineering Structures, 2025)

Thermally-activated CO2 reduction in photoelectrochemical cell by near-room-temperature heat - Jun Zhang; Jili Zheng; Xiaotian Li; Dan Ping; Yawen Song; Shiwei Zhang; Wei Yang; Miao Du; Yaxin Zheng (Chemical Engineering Journal, 2025)

A Unified Nonlinear Creep Damage Coupled Model for Rocks Based on Fractional Calculus and Statistical Damage Model - Da-Lang Tian; Zheng-Chuan Li; Fan Shen; Yu-tong Li; Zheng Li; Xiao-Ping Zhou (Rock Mechanics and Rock Engineering, 2025)

Semaphorin 3A protects against thoracic aortic aneurysm dissection by suppressing aortic angiogenesis - Li-Fei Wu; Jiao-Jiao Zhang; Xing Zhang; De-Ping Wang; Zhi-Fa Zheng; Jing Shen; Ying Zhou; Li-Juan Gao; Xuan Shang; Jun-Ya Ning; Qing-Hua Liu; Lan Zhou; et al. (Angiogenesis, 2025)

Dress me an outfit: advanced probiotics hybrid systems for intelligent IBD therapy - Yonglu Li; Yadi Wang; Yapeng Li; Shihai Yan; Xin Gao; Ping Li; Xiaodong Zheng; Qing Gu (Critical Reviews in Food Science and Nutrition, 2025)

Advancing autotrophic nitrogen removal in low C/N ratio wastewater: Innovative application of supercapacitor to enhance microbial electrolysis cells - Sen Fan; Yuhan Song; Decong Zheng; Xinyuan Peng; Sitao Li; Ping Gao; Daping Li (Journal of Environmental Sciences, 2025)

Altering wilting time and chopping length to optimize Medicago polymorpha L. fermentation ripening rate and flavour - Ning Mao; Hanyu Zhang; Ermei Du; Meiling Fan; Shihao Liu; Chaosheng Liao; Chao Chen; Hong Sun; Yulong Zheng; Ping Li; Yixiao Xie (Food Bioscience, 2025)

Characterization of GR-14 peptide from Cordyceps militaris mycelial albumin and its mechanism of heat protection on Lactobacillus fermentum J26 - Ping-Ping Gao; Han-Qing Liu; Qian-Wang Zheng; Zhi-Wei Ye; Li-Qiong Guo; Yuan Zou; Jun-Fang Lin (Food Bioscience, 2025)

Terpene-conjugated curcumin analogs alleviated alcoholic liver injury in rats through mitigation of intestinal barrier abnormalities - Shuaihu Tao; Ruanping Song; Ziyu Wang; Wenjing Xie; Siyuan Xiao; Yangyang Liao; Xinjie Zhang; Qiongdan Hu; Xinxing Tang; Jingyuan Huang; Wan Liao; Hongtao Xiao; et al. (Food Bioscience, 2025)

Incorporating atomic-level center into porphyrin-based COF for photocatalytic H2 evolution - Guo-Wei Guan; Su-Tao Zheng; Li-Ping Zhang; Si-Yu Hou; Xiang-Yu Liu; Qing-Yuan Yang (Chemical Engineering Journal, 2025)

Insights into mantle metasomatism during oceanic subduction from late Paleozoic (∼260 Ma) high-Mg diorites in the northeastern Tibetan Plateau - Feng-Hui Zou; Jian-Ping Zheng; Cai-Lai Wu; Chang-Qian Ma; Li-Huan Deng (Chemical Geology, 2025)

Chromosome-level genome assembly of a high-yield Chinese soybean variety Mengdou1137 unlocks genetic potential of disease and lodging resistance - Rujian Sun; Bincheng Sun; Zihao Zheng; Qi Zhang; Xingguo Hu; Rongqi Guo; Lei Feng; Shen Chai; Jingshun Wang; Ping Qiu; Ping Yu; Ying Liu; et al. (Theoretical and Applied Genetics, 2025)

Agricultural practices influence phosphorus transport and ecosystem health in rice-paddy systems: Insights from HYDRUS-1D simulations - Shuoshuo Liang; Qingnan Chu; Ali Ashrafi; Zheng Zhao; Xiangyu Liu; Shuang Liu; Bei Yang; Detian Li; Ping He; Linkui Cao; Zhimin Sha; Chengrong Chen (Agriculture, Ecosystems & Environment, 2025)

Mass deposition of microbes from wildfire smoke to the sea surface microlayer - Siyao Yue; Yafang Cheng; Lishan Zheng; Senchao Lai; Shan Wang; Tianli Song; Linjie Li; Ping Li; Jialei Zhu; Meng Li; Lianfang Wei; Chaoqun Ma; et al. (Limnology and Oceanography, 2025)
Microbes in the sea surface microlayer (SML) are key to connecting the ocean and the atmosphere, affecting the exchange of matter, momentum, and heat at the interface. However, their sources have never been quantified systematically. Seawater has long been deemed their major source, whereas atmospheric deposition is regarded as trivial or merely providing additional nutrients. Here, combining atmospheric observations and quantitative budget analyses, we show that during the Indonesian peatland wildfire events the smoke can directly deposit abundant microbes into the SML, which can be comparable to the estimated supply from seawater and potentially diversify the microbial community of the SML. This land–air–ocean interaction is relevant for global climate, as it may induce previously unknown effects on the air–sea interactions, especially in an increasingly warming future with more intensifying wildfires.

ROS-responsive dextran-benzeneboronic acid pinacol ester micelles encapsulating edaravone for the treatment and mechanism of cerebral ischemia-reperfusion injury - Hexiang Zhao; Ping Yang; Mou Zhang; Wenshu Zheng; Renli Qi; Xiaofeng Zhu; Jinghui Li; Shipeng Li (Metabolic Brain Disease, 2025)

Cortical thickness alternation in obsessive-compulsive disorder patients compared with healthy controls - Chunyu Dong; Hao Zheng; Hailong Shen; Yu Wan; Yinghong Xu; Ying Li; Liangliang Ping; Hao Yu; Chuanxin Liu; Jian Cui; Kun Li; Cong Zhou (Brain Imaging and Behavior, 2025)

Aged microplastics-induced growth inhibition via DNA damage, GH/IGF-1 and HPT axes disruption in zebrafish larvae - Qing Ge; Tong Zheng; Ping Ding; Zhenyuan Li; Xihua Lin; Xintong Li; Miao He; Guocheng Hu (Science of The Total Environment, 2025)

Preparation, adsorption and structure of Ce doped layered manganese ion-sieve based on Li2MnO3 spatial structure - Qian Liu; Li Zhang; Yucheng Liu; Xiaoqiang Zheng; Xuna Liu; Zhongquan Zhong; Liping Wei; Qianqian Zhao; Tingting Yao; Ping Yang (Environmental Research, 2025)

Development of a shear strengthening conductive hydrogel for impact protection and distress signal emission - Juan Tan; Xi Li; Chuan Ru Zheng; Anna Tan; Xiu Chen Li; Hai Liang Ni; Wen Hao Yu; Yue Feng Bai; Ping Hu; Hong Mei Chen (Chemical Engineering Journal, 2025)

Multifunctional Sr/Zn-doped TiO2 micro/nanoporous coating enhances osseointegration by modulating signaling crosstalk of bone-related cells - Tian-Xia Zheng; Nuo-Ya Yang; Jiu-Peng Deng; Wei Dong; Li-Fang Feng; Yuanyuan-Ding; Jin-Ping Yang; Xin-Jia Cai; Yan Liu; Meng-Chun Qi (Chemical Engineering Journal, 2025)

Study on multi-objective joint optimization of water and sediment operation considering multiple uncertainties: a case study in the lower yellow river - Fangzheng Zhao; Peng Yi; Ping-an Zhong; Xinyu Wan; Jieyu Li; Sen Wang; Weiyi Shi; Xinyu Wang; Ke Zheng (Stochastic Environmental Research and Risk Assessment, 2025)

Impacts of Naphthenic Acids (NAs) Exposure on Soil Bacterial Community and Antibiotic Resistance Genes (ARGs) Dissemination - Qianzhi Zeng; Qiangwei Liu; Yunhong Pu; Ping Gong; Yuxin Li; Yanan Sun; Yiming Hao; Qing Yang; Yaxuan Wu; Bowen Yang; Shengnan Shi; Zheng Gong (Current Microbiology, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Unveiling a novel mechanism for anaerobic hexavalent chromium reduction mediated by extracellular reductases - Wei Shao; Zheng-Hao Li; Li Yuan; Guo-Ping Sheng (Journal of Environmental Management, 2025)

Degradation of phoxim by ultrasonic assisted calcium sulfite activated persulfate: Kinetics and mechanisms insights - Zhenjun Xiao; Junlong Zhang; Yijie Lin; Kaixuan Zheng; Zili Lin; Mengyang Niu; Wanlin Lin; Yuchun Hong; Zhongyang Li; Ping Chen; Qingbin Song; Wenying Lv; et al. (Journal of Environmental Chemical Engineering, 2025)

Dietary retinoic acid improved the growth, lipid metabolism and immune status in Macrobrachium rosenbergii - Qin-Cheng Huang; Li Wang; Zhi-Min Gu; Cui Liu; Tian-Tian Ye; Jun-Jun Yan; Ji-Lun Meng; Yu-Tong Zheng; Xian-Ping Ge; Zhi-Deng Lin; Guo-Yuan Zou (Frontiers in Marine Science, 2025)
The effect of dietary retinoic acid (RA) on the growth, lipid deposition, oxidation resistance, immunity, hepatopancreatic and intestinal health of Macrobrachium rosenbergii was evaluated. A total of 1200 prawns (0.22 ± 0.00 g) were divided into six groups and fed their corresponding feed containing 4, 132, 296, 562, 1206 or 2562 mg/kg dietary RA. The weight gain rate, specific growth rate and final body weight of the prawns changed linearly and quadratically, with the maximum observed in those fed 296 mg/kg dietary RA. Increasing dietary RA linearly and quadratically raised the RA content in the whole body. Compared to the prawns fed 4 mg/kg dietary RA, there was significantly lower lipid deposition in the muscle, hepatopancreas and whole body of prawns fed 296 mg/kg dietary RA. Prawns fed 296 mg/kg dietary RA had lower triglyceride (TG) content in the hepatopancreas with upregulated gene expression of retinoid X receptor ( RXR ), diacylglycerol acyltransferase 1 ( dgat1 ) and carnitine palmitoyltransferase 1 ( cpt1 ). Additionally, 296 mg/kg dietary RA increased the protein expression of RXR, CAMKKβ and phospho-AMPK. A dietary RA level of 296 mg/kg could decrease oxidative stress by upregulating the expression of peroxiredoxin 5 ( prx5 ) and improve immunity by upregulating expression of toll - like receptor 2 ( toll2 ), myeloid differentiation factor 88 (myd88 ) and dosal in the hepatopancreas. The intestinal health related genes ( crustin 2 / 3 / 4 , anti-lipopolysaccharide factor 1 / 7 , prx5 , peritrophin-1 , myosin light chain kinase , claudin , myd88 and dosal ) and morphological structure were also positively affected by dietary RA. Furthermore, dietary RA could relieve the immune responses induced by lipopolysaccharide, thus leading to lower transcription of antimicrobial peptides. In summary, dietary RA could improve the growth, lipid utilisation, antioxidant capacity and immunity of M . rosenbergii . To avoid the negative effects of excessive addition and obtain optimal growth, a diet containing 296 mg/kg dietary RA was suggested by the present study.

RIPK3 activation of CaMKII triggers mitochondrial apoptosis in NIBV-infected renal tubular epithelial cells - Ying Li; Qiurong Qi; Yifei Chen; Mengbing Ding; Manzi Huang; Cheng Huang; Ping Liu; Xiaona Gao; Xiaoquan Guo; Zhanhong Zheng (Veterinary Microbiology, 2025)

Aflatoxin B1 exposure induces Alzheimer's disease like pathology by disrupting redox homeostasis and activating ferroptotic signals in C57BL/6 J mice - Jinxian Lin; Huihui Hong; Sicheng Liu; Zhengwei Liang; Qixue Zheng; Kun Luo; Jiayi Li; Zhulin Du; Jinping Yu; Lingling Yang; Ping Deng; Huifeng Pi; et al. (Science of The Total Environment, 2025)

Enhanced Cr(VI) reduction and immobilization by Fe0 coupled with biochar through galvanic interaction - Qian Zuo; Bing Li; Zhiyi Deng; Xiangyu Zheng; Ping Li; Jinhua Wu (Journal of Water Process Engineering, 2025)

Regulation of iron homeostasis by IMA1 and bHLH104 under phosphate starvation in Arabidopsis - Lu Zheng; Xiangxiang Meng; Wenfeng Li; Yinglong Chen; Renfang Shen; Ping Lan (Journal of Plant Physiology, 2025)

Liubao insect tea polyphenols ameliorate DSS-induced experimental colitis by protecting intestinal barrier and regulating intestinal microbiota - Xinyu Feng; Yanwen Chen; Lina Luo; Zhoutao Fang; Shicheng Ma; Zhongxia Li; Jing Huang; Yani Pan; Helin Lv; Shuying Gong; Xiaodong Zheng; Fangyuan Fan; et al. (Food Chemistry, 2025)

Multifunctional flexible MXene/TA@CNC electronic hydrogel patch with robust adhesion and self-healing properties for wearable electronics - Haoyu Wang; Ping Han; Ying Yu; Shaolong Han; Yue Qiao; Yuehan Li; Bin Sun; Zheng Gu (Chemical Engineering Journal, 2025)

Enhanced production of recombinant calf chymosin in Kluyveromyces lactis via CRISPR-Cas9 engineering - Yanli Zheng; Shiqing Wang; Yuhui Deng; Ping Hu; Qingxin Xue; Jiaxin Li; Lei Lei; Zhuhua Chan; Jiangke Yang; Wenfang Peng (Bioresource Technology, 2025)

Identification of Potential Causal Genes for Neurodegenerative Diseases by Mitochondria-Related Genome-Wide Mendelian Randomization - Kang-Fu Yin; Ting Chen; Xiao-Jing Gu; Zheng Jiang; Wei-Ming Su; Qing-Qing Duan; Xiang-Jin Wen; Bei Cao; Ju-Rong Li; Li-Yi Chi; Yong-Ping Chen (Molecular Neurobiology, 2025)

Effect of Particle Size, Sphericity, and Distribution on Seepage in Granular Porous Media - Bo-bo Xiong; Rui Kuang; Ping Zhang; Bin Tian; Hong-hu Gao; Qian Zheng; Yu-qin Li (Geotechnical and Geological Engineering, 2025)

Transparent geological exploration for intelligent and safe open-pit mining based on ambient noise seismic imaging - Ping-Feng Li; Qiang-Qiang Zheng; Ying Xu; Di Wei; Jia-wei Qian; Bao-Ji Yang (Applied Geophysics, 2025)

Estradiol Enhances Cerebellar Molecular Layer Interneuron-Purkinje Cell Synaptic Transmission and Improves Motor Learning Through ER-β in Vivo in Mice - Yong-Rui Piao; Mei-Rui Li; Ming-Ze Sun; Yang Liu; Chao-Yue Chen; Chun-Ping Chu; Yuki Todo; Zheng Tang; Chun-Yan Wang; Wen-Zhe Jin; De-Lai Qiu (The Cerebellum, 2025)

PhenologyNet: A fine-grained approach for crop-phenology classification fusing convolutional neural network and phenotypic similarity - Hai-Chao Yang; Jian-Ping Zhou; Chao Zheng; Zheng Wu; Yi Li; Li-Gong Li (Computers and Electronics in Agriculture, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Relationship between pyrolytic sulfur migration behavior and structural composition of high-sulfur fat coal - Zhan-Ku Li; Zheng-Zhi Zhang; Kai Zhang; Hong-Lei Yan; Jing-Chong Yan; Zhi-Ping Lei; Shi-Biao Ren; Zhi-Cai Wang; Shi-Gang Kang; Heng-Fu Shui (Fuel, 2025)

Ni@S-1 facilitated efficient reduction of CO2-containing CO via chemical looping - Ping Jin; Yuhao Wang; Kongzhai Li; Hua Wang; Yane Zheng (Fuel, 2025)

Aquaculture source of atmospheric N2O in China: Comparison of system types, management practices and measurement methods - Yifei Zhang; Guanghui Zhao; Ping Yang; Changchun Song; Yang Wang; Yiwen Zhang; Yuxing Zou; Zhuangpeng Zheng; Kam W. Tang; Siyue Li (Environmental Research, 2025)

Tauroursodeoxycholic acid targets HSP90 to promote protein homeostasis and extends healthy lifespan - Jia-Yu Liu; Yao Wang; Yue Guo; Run-Qi Zheng; Yun-Ying Wang; Yan-Yan Shen; Yan-Hong Liu; Ai-Ping Cao; Rui-Bo Wang; Bo-Yang Xie; Shuai Jiang; Qiu-Ying Han; et al. (Science China Life Sciences, 2025)

Identification and characterization of GRAS genes in passion fruit (Passiflora edulis Sims) revealed their roles in development regulation and stress response - Xinkai Cai; Denglin Li; Chaojia Liu; Jiayi Chen; Xiuqing Wei; Sitong Hu; Lin Lu; Shengzhen Chen; Qinglong Yao; Shiyu Xie; Xiaowen Xu; Ruoyu Liu; et al. (Plant Cell Reports, 2025)

Design and evaluation of C18 stationary phases with different polar-embedded groups for liquid chromatography - Xiao-Dong Cheng; Zheng Zhang; Yun-Ping Li; Xue-xin Dai (Analytica Chimica Acta, 2025)

Sulfate-driven microbial collaboration for synergistic remediation of chloroethene-heavy metal pollution - Zheng-Tao Li; He-Ping Zhao (Water Research, 2025)

Molecular fractionation mediates genotoxicity evolution of hydrochar-derived dissolved organic matter at the iron oxyhydroxides-water interface - Yan-Jun Liu; He-Yun Yang; Shu-Xian Gao; Zheng-Hao Li; Yan-Yun Hu; Xing Zheng; Guo-Ping Sheng (Water Research, 2025)

Corrigendum to “Cobalt induces neurodegenerative damages through Pin1 inactivation in mice and human neuroglioma cells” [J Hazard Mater 419 (2021) 126378] - Fuli Zheng; Yuqing Li; Fengshun Zhang; Yi Sun; Chunyan Zheng; Zhousong Luo; Yuan-Liang Wang; Michael Aschner; Hong Zheng; Liqiong Lin; Ping Cai; Wenya Shao; et al. (Journal of Hazardous Materials, 2025)

Ultrahigh energy storage density and efficiency of antiferroelectric AgNbO3-based MLCCs via reducing the off-center cations displacement - Ting Tang; Dong Liu; Long Wang; Jiaze Li; Zheng Zhang; Lei Zhao; Bo-Ping Zhang; Li-Feng Zhu (Chemical Engineering Journal, 2025)

The beneficial potential of protein hydrolysates as prebiotic for probiotics and its biological activity: a review - Ping-Ping Gao; Han-Qing Liu; Zhi-Wei Ye; Qian-Wang Zheng; Yuan Zou; Tao Wei; Li-Qiong Guo; Jun-Fang Lin (Critical Reviews in Food Science and Nutrition, 2024)

Varied chromosome distribution behaviours during meiosis in triploid Chinese chives contribute to the formation of viable pollen - Peng-Qiang Yao; Li-Hua Xie; Mei-Yu Li; Si-Qian Jiao; Shuai-Zheng Qi; Zhe Wang; Shi-Ping Cheng (Chromosome Research, 2024)

Inter-annual and spatial variations of air-sea CO2 fluxes and acidification mechanism in the coastal waters of Qingdao, China during 2011–2019 - Zheng-Xin Hu; Tie Li; Tian-Tian Ge; Jing-Wen Hu; Ping-Wang; Chun-Ying Liu; Gui-Peng Yang (Marine Pollution Bulletin, 2024)

Oxygen-induced evolution of anammox granular sludge explains its unique responses during preservation - Leiyan Guo; Chao Pan; Junwei Wu; Yang Yu; Dongdong Xu; Wenda Chen; Wenji Li; Ping Zheng; Meng Zhang (Water Research, 2024)

Precipitation-induced biomass enhancement and differential allocation in Inner Mongolia's herbaceous and shrub communities - Xiangyun Li; Ya Hu; Zhaobin Song; Ping Cong; Huan Cheng; Xuebo Zheng; Wenjing Song; Ping Yue; Shaokun Wang; Xiaoan Zuo (Science of The Total Environment, 2024)

Discovery of polyoxygenated briaranes from octocoral Briareum stechei - Yue-Wen Chuang; Wei-Chen Ting; Su-Ying Chien; Li-Guo Zheng; Chih-Yin Huang; Zhi-Hong Wen; Yu-Jen Wu; Junichi Tanaka; You-Ying Chen; Jui-Hsin Su; Ping-Jyun Sung (Phytochemistry Letters, 2024)

Associations of maternal serum concentration of iron-related indicators with gestational diabetes mellitus in Chinese: A pilot prospective cohort study - Geng-dong Chen; Peng-sheng Li; Zi-xing Zhou; Ting-ting Pang; Hai-yan Wang; Xiao-yan Gou; Shao-xin Ye; Dong-xin Lin; Da-zhi Fan; Zheng-ping Liu (Journal of Trace Elements in Medicine and Biology, 2024)

Closed-loop recycling of biodegradable poly(butylene adipate-co-terephthalate) based on hydrolysis and repolymerization strategy - Wei-Zhen Zheng; Xiao Li; Jing Xie; Ze-Yang Zhang; Ping-Li Wang; Dan Huang; Zhong-Lai Ren; Jun-Hui Ji; Ge-Xia Wang (Journal of Environmental Chemical Engineering, 2024)

Cohort Profile: TRacing Etiology of Non-communicable Diseases (TREND): Rationale, Progress and Perspective - Hui-Ying Ren; Ying Lv; Bei-Ning Ma; Chang Gao; Hong-Mei Yuan; Hai-Hong Meng; Zheng-Qian Cao; Ya-Ting Chen; Yan-Xi Zhang; Yu-Ting Zhang; Wei Liu; Yu-Ping Fan; et al. (Phenomics, 2024)
The TRacing Etiology of Non-communicable Diseases (TREND) cohort is a prospective longitudinal cohort and biobank that is mainly based in Ma’anshan, Anhui Province, China. The primary aim of the study is to decipher comprehensive molecular characterization and deep phenotyping for a broad spectrum of chronic non-communicable diseases (NCDs), which focuses on providing mechanistic insights with diagnostic, prognostic and therapeutic implications. The recruitment was initiated in 2023 and is expected to complete in 2025 with 20,000 participants originated from urban and rural area. In the first phase, 3360 participants were recruited. Follow-up visits are scheduled annually and intervally for a total of 30 years. The cohort includes individuals aged over 18 years. Two participants with first-degree linkage were recruited from a household. The age distribution of recruited participants was stratified into four categories: 18–45, 45–55, 55–65, and ≥65 years, aligning with the population proportions of Ma’anshan. Meanwhile, the gender distribution was controlled by pairing men and women from the same household. Data collected at baseline includes socio-economic information, medical history, lifestyle and nutritional habits, anthropometrics, blood oxygen, electrocardiogram (ECG), heart sound, as well as blood, urine and feces tests results. Molecular profiling includes genome, proteome, metabolome, microbiome and extracellular vesicles -omics. Blood, urine and fecal samples are collected and stored at −80 °C in a storage facility for future research.

Genome-wide identification and biochemical characterization of glycoside hydrolase gene family members in Tilletia Horrida - Xinyue Shu; Yuping Zhong; Xiaoqun Yi; Aijun Wang; Ping Li; Desuo Yin; Aiping Zheng (Molecular Biology Reports, 2024)

Muscone inhibits angiotensin II–induced cardiac hypertrophy through the STAT3, MAPK and TGF-β/SMAD signaling pathways - Yi-jiang Liu; Jia-jia Xu; Cui Yang; Yan-lin Li; Min-wei Chen; Shi-xiao Liu; Xiang-hui Zheng; Ping Luo; Rui Li; Di Xiao; Zhong-gui Shan (Molecular Biology Reports, 2024)
Background Muscone is a chemical monomer derived from musk. Although many studies have confirmed the cardioprotective effects of muscone, the effects of muscone on cardiac hypertrophy and its potential mechanisms are unclear.The aim of the present study was to investigate the effect of muscone on angiotensin (Ang) II-induced cardiac hypertrophy. Methods and results In the present study, we found for the first time that muscone exerted inhibitory effects on Ang II-induced cardiac hypertrophy and cardiac injury in mice. Cardiac function was analyzed by echocardiography measurement, and the degree of cardiac fibrosis was determined by the quantitative real-time polymerase chain reaction (qRT-PCR), Masson trichrome staining and western blot assay. Secondly, qRT-PCR experiment showed that muscone attenuated cardiac injury by reducing the secretion of pro-inflammatory cytokines and promoting the secretion of anti-inflammatory cytokines. Moreover, western blot analysis found that muscone exerted cardio-protective effects by inhibiting phosphorylation of key proteins in the STAT3, MAPK and TGF-β/SMAD pathways. In addition, CCK-8 and determination of serum biochemical indexes showed that no significant toxicity or side effects of muscone on normal cells and organs. Conclusions Muscone could attenuate Ang II-induced cardiac hypertrophy, in part, by inhibiting the STAT3, MAPK, and TGF-β/SMAD signaling pathways.

Molecular evidence of internal carbon-driven partial denitrification in a mainstream pilot A-B system coupled with side-stream EBPR treating municipal wastewater - Da Kang; Yuan Yan; IL Han; Jangho Lee; Kester McCullough; Guangyu Li; Zijian Leo Wang; Peisheng He; Dongqi Wang; Stephanie Klaus; Ping Zheng; Varun Srinivasan; et al. (Water Research, 2024)

Dynamic evolution of particulate and gaseous emissions for typical residential coal combustion - Siyuan Li; Dantong Liu; Xiaotong Jiang; Ping Tian; JiuJiang Sheng; Yangzhou Wu; Kang Hu; Kai Bi; Ruijie Li; Delong Zhao; Mengyu Huang; Shaofei Kong; et al. (Science of The Total Environment, 2024)

Vegetation restoration enhancing soil carbon sequestration in karst rocky desertification ecosystems: A meta-analysis - Wei Zheng; Xiaobin Guo; Ping Zhou; Li Tang; Jiaxin Lai; Yuting Dai; Wende Yan; Jinshui Wu (Journal of Environmental Management, 2024)

Enhancing reductive dechlorination of trichloroethylene in bioelectrochemical systems with conductive materials - Su-Hao Chen; Zheng-Tao Li; Chun-Yu Lai; He-Ping Zhao (Environmental Research, 2024)

Improved recovery of lithium from spent lithium-ion batteries by reduction roasting and NaHCO3 leaching - Wenke Liu; Qingwei Qin; Hailin Zhang; Wei Zhao; Xing Chen; Jiachun Xiong; Yunwu Han; Shili Zheng; Chunguang Zhang; Guangqiang Li; Ping Li (Waste Management, 2024)

Laboratorial radiative shocks with multiple parameters and first quantifying verifications to core-collapse supernovae - Lu Zhang; Jianhua Zheng; Zhenghua Yang; Tianming Song; Shuai Zhang; Tong Liu; Yunfeng Wei; Longyu Kuang; Longfei Jing; Zhiwei Lin; Liling Li; Hang Li; et al. (Science Bulletin, 2024)

Sustainable recycling of the biodegradable polyester poly(butylene succinate) via selective catalytic hydrolysis and repolymerization - Wei-Zhen Zheng; Xiao Li; Peng-Yuan Xu; Ze-Yang Zhang; Ping-Li Wang; Bo Lu; Dan Huang; Zhi-Chao Zhen; Jun-Hui Ji; Ge-Xia Wang (Resources, Conservation and Recycling, 2024)

Petrogenesis of ca. 2.0 Ga granites in the Kongling Complex: Implications for a tectonic transition of the Yangtze Craton from compression to extension - Liang Zhang; Shao-Bing Zhang; Zhen-Xin Li; Ting Liang; Zheng-Xiang Li; Xiang-Ping Zha (Precambrian Research, 2024)

7S,8R-Dihydroxydeepoxysarcophytoxide: A natural dihydrofuranocembranoid from the octocoral Sarcophyton stellatum - Jyh-Horng Sheu; Li-Guo Zheng; You-Ying Chen; Su-Ying Chien; Ping-Jyun Sung (Phytochemistry Letters, 2024)

Water-soluble biodegradable polyesters with pH and ionic responsivity - Xiao Li; Wei-Zhen Zheng; Peng-Yuan Xu; Ze-Yang Zhang; Ping-Li Wang; Bo Lu; Dan Huang; Zhi-Chao Zhen; Yang Zhao; Jun-Hui Ji; Ge-Xia Wang (Journal of Hazardous Materials, 2024)

Crystal phase conversion of amorphous Fe−Mn binary oxides promote the sequestration and redistribution of arsenic, cadmium, and lead in the soil: Comparison with crystalline form - Junhao Zheng; Yan Xie; Yang Ping; Hao Xu; Qi Li; Qi Liao; Qingzhu Li; Zhihui Yang; Weichun Yang; Mengying Si (Journal of Environmental Chemical Engineering, 2024)

Waste reduction and high value utilization of jarosite-alunite residue (JAR) produced from the recovery of spent lithium-ion battery - Wenke Liu; Ping Li; Qingwei Qin; Wei Zhao; Hailin Zhang; Yunwu Han; Feijie Wu; Qiang Zhang; Shili Zheng; Guangqiang Li (Hydrometallurgy, 2024)

Synthesis of activated carbon-supported nano copper oxide and its inactivation performance on Escherichia coli in water - Bing Li; Qian Zuo; Zhiyi Deng; Xiangyu Zheng; Ping Li; Jinhua Wu (Chemical Engineering Journal, 2024)

Loss of CHCHD2 Stability Coordinates with C1QBP/CHCHD2/CHCHD10 Complex Impairment to Mediate PD-Linked Mitochondrial Dysfunction - Yan-Lin Ren; Zheng Jiang; Jia-Yi Wang; Qin He; Si-Xu Li; Xiao-Jing Gu; Yang-Ran Qi; Min Zhang; Wen-Jie Yang; Bei Cao; Jing-Yu Li; Yi Wang; et al. (Molecular Neurobiology, 2024)

Microbial metabolism strengths carbon sequestration and crop yield in upland red soil after long-term ex situ incorporation of straw - Li Tang; Xiaobin Guo; Daoyou Huang; Xiaomeng Wei; Hao Sheng; Pei Luo; Ping Zhou; Wei Gao; Yan Li; Miaomiao Zhang; Wei Zheng; Jinshui Wu (Journal of Soils and Sediments, 2024)

Label-Free Detection of Programmed Death-Ligand 1 for Prognosis Using a Truncated Aptamer and SYBR Green I - Ling Li; Zheng-Ling Li; Wei Wang; Xin-Xin Long; Ping Liu; Guo-Tian Wang; Shi-Qing Sun; Rong-Lian Du (Journal of Fluorescence, 2024)

Seasonal changes of plankton community and its influencing factors in subtropical coastal marine areas revealed by eDNA-based network analysis - Xiaoqi Lin; Kunhuan Li; Hancheng Zhao; Yan Gao; Zonghang Zhang; Lin Wang; Xinjie Wang; Edmond Sanganyado; Zhao Zheng; Qilin Gutang; Sailan Liu; Ping Li; et al. (Frontiers in Marine Science, 2024)
Introduction Coastal marine ecosystems are among the most ecologically and socio-economically dynamic regions on Earth, and the study of eukaryotic planktonic communities is an important aspect of aquatic ecology. It is essential to monitor plankton biodiversity and identify influencing factors in order to measure human effects on coastal waters and help contribute to ecosystem preservation. Environmental DNA (eDNA) metabarcoding analysis is an advanced toolfor detecting the presence of aquatic organisms, which has revolutionary significance for biodiversity monitoring and real-time detection of wild environments. Methods In this study, eDNA metabarcoding was used to study seasonal changes in eukaryotic plankton communities in subtropical coastal waters of the northern South China Sea, to explore how various trophic groups affect the complexity and stability of the species network. Results The results showed that the summer interaction network is looser and had has reduce biodiversitycompared to the spring interaction network. As an important part of the planktonic community, the abundance and diversity of algae reflect the interactions between different species and the influence of environmental factors on the dominant species, particularly temperature and nutrients. In addition, producer diversity set the basis for species network complexity and indirectly affected network stability, while consumer diversity and its flexible predation strategies may directly lead to differences in network stability across seasons. There were close correlations among species interaction, environmental factors and species diversity. Discussion This study can help us understand the ecosystem functions throughout the year and the complex interactions of planktonic communities from a multiple trophic level perspective, and provide effective methods for sustainable resource utilization and ecological environmental protection in the future.

The evolution of calcified anaerobic granular sludge bed informs the deep insight into its agglomeration process - Wenda Chen; Dongdong Xu; Wenji Li; Chao Pan; Leiyan Guo; Abbas Ghulam; Meng Zhang; Ping Zheng (Water Research, 2024)

A citrullinated antigenic vaccine in treatment of autoimmune arthritis - Xu Jin; Tianya Dong; Qian Wang; Yang Xie; Xiangyu Fang; Chaonan Wei; Shuyan Liu; Xi Zheng; Ping Wang; Danxue Zhu; Lulu Cao; Suwei Dong; et al. (Science Bulletin, 2024)

Multi-omics insights into the function and evolution of sodium benzoate biodegradation pathway in Benzoatithermus flavus gen. nov., sp. nov. from hot spring - Chao-Jian Hu; Yi-Qing Lv; Wen-Dong Xian; Jian-Yu Jiao; Zheng-Han Lian; Sha Tan; Meng-Meng Li; Zhen-Hao Luo; Ze-Tao Liu; Ai-Ping Lv; Lan Liu; Mukhtiar Ali; et al. (Journal of Hazardous Materials, 2024)

Rapid evaluation of the quality of Smilax glabra Roxb. using QADS based on FT-NIR combined with multiple intelligent algorithms - Geng-zhi Zhan; Xin-yue Guo; Zi-chao Qiu; Lu-yao Cai; Qian Hu; Ye Gao; Shu-wan Tang; Cun-yu Li; Yun-feng Zheng; Guo-ping Peng (Food Chemistry, 2024)

Hinokione: an abietene diterpene with pancreatic β cells regeneration and hypoglycemic activity, and other derivatives with novel structures from the woods of Agathis dammara - Zheng Wang; Zhe-Wei Yu; Yi Zhang; Wen-Hui Wang; Xin-Yi Wu; Shun-Zhi Liu; Yan-Lin Bin; Bang-Ping Cai; Shi-Yan Huang; Mei-Juan Fang; Rong Qi; Ming-Yu Li; et al. (Journal of Natural Medicines, 2024)

Molecular characterization of fad6 gene and its transcriptional changes in response to different initial diets and nutritional status in yellow catfish (Pelteobagrus fulvidraco) - Bo Zhou; Xiu-Ying Wei; Zheng-Yong Wen; Bin Wang; Yu-Ying Zhao; Wan-Hong Zeng; Yu He; Panita Prathomya; Yun-Yun Lv; Yan-Ping Li; Jun Wang; Rui Li; et al. (Frontiers in Marine Science, 2024)
Fatty acid desaturases (FADs) are rate-limiting enzymes for the biosynthesis of highly unsaturated fatty acids (HUFAs). As a new member of the FAD family, Fad6 and its roles remain unclear in various teleost fishes. In this study, we identified a fad6 gene from yellow catfish (yc fad6 ) and determined its spatiotemporal expression patterns and responses to different initial diets and nutritional status in yellow catfish. Our results showed that the open reading frame (ORF) of yc fad6 was 1,080 bp in length, encoding a protein of 359 amino acids. Multiple protein sequences alignment proved that fad6 is highly conserved among diverse vertebrates. Meanwhile, phylogenetic analysis revealed that Southern catfish and yellow catfish were clustered into one branch, supporting evolutionary consistence between the fad6 gene and fish morphology. Moreover, comparisons of genomic synteny and gene structure revealed functional and evolutionary conservation of the fad6 gene in various teleost fishes. Tissue distribution analysis by quantitative RT-PCR demonstrated that the yc fad6 gene was extensively expressed in examined tissues, with higher transcription levels in the heart and liver. Meanwhile, yc fad6 gene was widely expressed in various developmental stages, indicating Fad6 may play important roles in HUFA biosynthesis at early developmental stages in yellow catfish. Functional experiments verified that the transcription of yc fad6 decreased significantly with the extension of feeding time (with egg yolk or Artemia nauplii ) at the early developmental stages, indicating that a diet rich in HUFA can remarkably inhibit the transcription of yc fad6 in yellow catfish. In addition, yc fad6 transcription was significantly reduced after a short-term (24-h) or long-term food deprivation (1-week) and then continued to decrease during refeeding, suggesting that nutritional states can affect the transcription of yc fad6 , which further regulates the metabolism of HUFAs. Anyway, these fundamental findings provide basic references for further investigating evolutionary and physiological functions of the fad6 gene in yellow catfish as well as in other teleost fishes.

Garciyunnanones A–R: Caged polycyclic polyprenylated acylphloroglucinols decorated with a lavandulyl substituent from Garcinia yunnanensis - Miaomiao Nan; Yueyou Yang; Ping Ying; Qiang Zheng; Youjun Wu; Tianjie Cao; Ting Li; Weiming Huang; Chuanlu Fu; Lingyi Kong; Wenjun Xu (Phytochemistry, 2024)

Dimeric piperidinoquinoline alkaloids from the seeds of Chimonanthus salicifolius - Zhan-Peng Yu; Yu-Xia Wang; Li-Hong Hong; Ya-Lin Li; Jian-Fei Zhang; Mu Li; Ping Ying; Qiang Zheng; Ling-Yi Kong; Jian-Guang Luo (Phytochemistry Letters, 2024)

Investigation of high-risk antibiotic resistance bacteria and their associated antibiotic resistance genes in different agricultural soils with biogas slurry from China - Yi Lu; Junhui Wu; Jiwei Li; Zailin Du; Changai Zhang; Yanjun Chai; Zewen Jin; Zichuan Li; Jun Meng; Haifeng Zhuang; Lifeng Ping; Ming Hung Wong; et al. (Journal of Hazardous Materials, 2024)

Potential of Cordyceps militaris protein hydrolysates as prebiotic and thermo-protectants of Lactobacillus fermentum J26 - Ping-Ping Gao; Han-Qing Liu; Qian-Wang Zheng; Yuan Zou; Zhi-Wei Ye; Tao Wei; Li-Qiong Guo; Jun-Fang Lin (Food Bioscience, 2024)

Phytic acid inhibits RafGOFScrib−/− tumor growth and invasion by suppressing the Yki-mediated JAK/STAT pathway in Drosophila melanogaster - Li Jin; Xinyu Zheng; Chenxi Yu; Ping Li; Guiran Xiao (Food Bioscience, 2024)

Immobilization of Nickel- and Cobalt-Based Complexes in NH2-UiO-66 for Efficient CO2 Photoreduction - Yu Jiang; Si-Chao Liu; Li-Ping Zhang; Guo-Wei Guan; Yi-Tao Li; Shuang Ni; Run-Yuan Jiang; Su-Tao Zheng; Hao-Ran Liu; Hao-Ling Lan; Qing-Yuan Yang (Chemical Engineering Journal, 2024)

Near-infrared-LED photostimulated luminescent nanoprobes based on lanthanide-doped SrS nanocrystals - Wei Lian; Qianqi Yang; Yuhan Liu; Datao Tu; Liangzhi Cai; Xiaoying Shang; Bowen Li; Ping Hu; Wei Zheng; Zhuo Chen; Xueyuan Chen (Chemical Engineering Journal, 2024)

Mining for QTL controlling maize low-phosphorus response genes combined with deep resequencing of RIL parental genomes and in silico GWAS analysis - Bowen Luo; Peng Ma; Chong Zhang; Xiao Zhang; Jing Li; Junchi Ma; Zheng Han; Shuhao Zhang; Ting Yu; Guidi Zhang; Hongkai Zhang; Haiying Zhang; et al. (Theoretical and Applied Genetics, 2024)

Efficacy and safety of dabigatran and rivaroxaban in atrial fibrillation patients with impaired liver function: a multicenter retrospective cohort study - Xinhai Huang; Wenlin Xu; Guilan Wu; Ruijuan Li; Ping Gu; Qiaowei Zheng; Xiumei Liu; Hengfen Dai; Xiangsheng Lin; Yuxin Liu; Xiaoming Du; Jun Su; et al. (European Journal of Clinical Pharmacology, 2024)

Relay intercropping boosts soybean recovery growth and delays nodule senescence to achieve yield advantages - Ping Chen; Benchuan Zheng; Huan Yang; Qing Du; Zhidan Fu; Kai Luo; Yilin Li; Ping Lin; Xihong Peng; Tian Pu; Yushan Wu; Xiaochun Wang; et al. (Agriculture, Ecosystems & Environment, 2024)

VGluT2 neuron subtypes in the paraventricular thalamic nucleus regulate depression in paraquat-induced Parkinson’s disease - Yu Zhang; Yihua Jiang; Zhen Yu; Yinhan Li; Xinpei Lin; Yali Weng; Zhenkun Guo; Hong Hu; Wenya Shao; Guangxia Yu; Fuli Zheng; Ping Cai; et al. (Journal of Hazardous Materials, 2024)

Microglial exosomes in paraquat-induced Parkinson's disease: Neuroprotection and biomarker clues - Jingwen Wu; Wenya Shao; Xu Liu; Fuli Zheng; Yaping Wang; Ping Cai; Zhenkun Guo; Hong Hu; Guangxia Yu; Jianhui Guo; Linlin Yao; Siying Wu; et al. (Environmental Pollution, 2024)

Insights into nitrogen-doped BiOBr with oxygen vacancy and carbon quantum dots photocatalysts for the degradation of sulfonamide antibiotics: Actions to promote exciton dissociation and carrier migration - Zhenchao Li; Chenghui Wen; Daguang Li; Zheng Fang; Zili Lin; Dezhu Liu; Yishun Wang; Xiaoyu Zhang; Ping Chen; Wenying Lv; Guoguang Liu (Chemical Engineering Journal, 2024)

GHK-Cu/Pionin-loaded in situ electrospun PVB/PVP smart dressing promotes wound healing via anti-oxidant, anti-inflammatory, antimicrobial, and tissue regenerative effects - Yan Wang; Zhichao Zheng; Janak L. Pathak; Haoyu Cheng; Sizhen Huang; Zi Fu; Ping Li; Lihong Wu; Huade Zheng (Chemical Engineering Journal, 2024)

Heating and Water Transport Behavior of Sandstones Under Microwave Irradiation - Qinhua Zhao; Yanlong Zheng; Jianchun Li; Ping Che; Xiaobao Zhao (Rock Mechanics and Rock Engineering, 2024)

Evaluation and projection of circulation conditions tied to summertime compound drought and heatwave frequency over the Yangtze River Delta, China, for the carbon neutrality period based on CMIP6 GCMs - Jing Wang; Ping Liang; Fei Cheng; Yanju Liu; Chengyu Song; Wei Wu; Qingfeng Zheng; Tianyu Zhang; Ping Qu; Yujie Li; Yihui Ding (International Journal of Climatology, 2024)
Frequent occurrences of compound droughts and heatwaves (CDHWs) may have considerable adverse impacts on human health and socioeconomic development. To project future summertime CDHWs over the Yangtze River Delta (YRD) of China under carbon neutrality (CN) for policymakers, we used nine global climate models (GCMs) from the Coupled Model Intercomparison Project Phase 6 (CMIP6) and evaluated and projected circulation conditions tied to the summer YRD CDHW frequency in the boreal summer. The results show that a marked mid‐tropospheric regional‐scale anticyclonic anomaly centred over the East China Sea can be deemed the dominant system linking the more frequent occurrence of YRD CDHWs. Our selected nine CMIP6 GCMs better captured the observed climatological and anomalous spatial circulation patterns connected to the summer YRD CDHW frequency. Moreover, the nine models' multi‐model ensemble mean (9MME) was better than most of the individual models regarding the related climatological circulation simulations. The 9MME‐projected changes in circulation conditions tied to summer YRD CDHWs during the carbon neutrality period (2050–2060) under SSP119 favour the comparable occurrence of the YRD with that for the same period under the medium greenhouse gas (GHG) warming scenario (SSP245), but the intensities of the CDHWs are the least severe. However, the highest number of YRD CDHWs is driven by the high GHG warming scenario (SSP585), and these CDHWs feature the most severe intensity. Our research identified a new paradigm regarding the frequency and intensity of the summer YRD CDHW under SSP119, highlighting the potential role of the newly accessible CN‐oriented sustainable development pathway in alleviating compound extremes.

Unveiling the molecular mechanisms of size-dependent effect of polystyrene micro/nano-plastics on Chlamydomonas reinhardtii through proteomic profiling - Xiaoxue Li; Zheng Chu; Chenran Feng; Ping Song; Tong Yang; Lirun Zhou; Xin Zhao; Xin Chai; Jiale Xing; Sa Chen; Junzhe Zhang; Jigang Wang; et al. (Chemosphere, 2024)

Dependence of evolution of Cyanobacteria superiority on temperature and nutrient use efficiency in a meso-eutrophic plateau lake - Jing Cao; Yue Wu; Ze-kun Li; Ze-ying Hou; Tian-hao Wu; Zhao-sheng Chu; Bing-hui Zheng; Ping-ping Yang; Yi-yan Yang; Cun-sheng Li; Qian-hua Li; Xia Guo (Science of The Total Environment, 2024)

Mn-assisted Fe-electrocoagulation strategy for enhanced efficient arsenic removal and its mechanism - Ping Zhang; Feiping Zhao; Penggang Li; Junhao Zheng; Weichun Yang; Qingzhu Li; Zhihui Yang (Process Safety and Environmental Protection, 2024)

Isolation of 24-homoscalarane sesterterpenoids from a sponge of the genus Lendenfeldia - Li-Guo Zheng; You-Yan Chen; Chia-Ching Liaw; Yu-Chi Lin; Su-Ying Chien; Yi-Hao Lo; Yu-Chi Tsai; Hao-Chun Hu; You-Ying Chen; Tsong-Long Hwang; Tzu-Ming Ou; Ping-Jyun Sung (Phytochemistry Letters, 2024)

Early Triassic high-K granitoids and enclaves of the Daheba pluton, West Qinling (China): Implications for relative contributions of crust and mantle - Feng-Hui Zou; M. Santosh; Chang-Qian Ma; Cai-Lai Wu; Jian-Ping Zheng; Fa-Bin Pan; Han-Ming Gu; Li-Huan Deng (Journal of Asian Earth Sciences, 2024)

Phyllosphere bacterial composition from Brassica oleracea and Raphanus sativus, the feeding food for Plutella xylostella - Wenhong Li; Ligang Xiang; Ping Zheng; Xu Tian; Hancheng Wang (Journal of Asia-Pacific Entomology, 2024)

Bacterial structures and their associated ARGs in Shanghai subway air, China - Lijun Zhang; Xiaojing Li; Yongping Liu; Yi Zheng; Lisha Shi; Yichen Ding; Jian Chen; Ping Xiao (Journal of Aerosol Science, 2024)

Photoaged polystyrene microplastics result in neurotoxicity associated with neurotransmission and neurodevelopment in zebrafish larvae (Danio rerio) - Xintong Li; Tong Zheng; Jiayi Zhang; Haibo Chen; Chongdan Xiang; Yanan Sun; Yao Dang; Ping Ding; Guocheng Hu; Yunjiang Yu (Environmental Research, 2024)

Experimental study and numerical model of a new passive adaptive isolation bearing - Siqi Wang; Yong Yuan; Ping Tan; Yafeng Li; Wenzhi Zheng; Dehong Zhang (Engineering Structures, 2024)

Kidney-targeted antioxidant salvianolic acid B nanoparticles restoring lysosome homeostasis for acute kidney injury therapy - Jian-Li Chen; Xiao-Hui Jia; Xuan Wu; Ming-Heng Yuan; Xinyue Xia; Dan Yin; Xu Chen; Ze-Yun Gu; Jia-Zheng Liu; Li-Ping Bai; Kathy Qian Luo; Jianfang Wang; et al. (Chemical Engineering Journal, 2024)

Chemical constitutents and chemotaxonomic research of the deep-sea-derived fungus Talaromyces minioluteus W19 - Kai Zhang; Yuan Wang; Teng Long; Ya-Ping Xie; Zheng-Biao Zou; Yong Zhang; You Li; Ming-Min Xie; Guang-Ming Liu; Xian-Wen Yang (Biochemical Systematics and Ecology, 2024)

Retraction Note: Hedgehog signaling-related genomics signature for the accurate progress and prognosis prediction in gastric cancer - Guoliang Zhang; Guojun Xia; Jungang Luo; Ping Ye; Huangen Wang; Shaodong Li; Difeng Zheng (Functional & Integrative Genomics, 2024)

Streptomyces camelliae sp. nov., isolated from rhizosphere soil of Camellia oleifera Abel - Zheng Yaxi; Deng Aihua; Xu Xiaoxiao; Li Chenxi; Peng Yi; Tang Ting; Liu Jin; Ming Yiru; Mo Ping (Archives of Microbiology, 2024)

Dynamic energy evolution and fragmentation characteristics of damaged rock under impact compression loading - Qiang-Qiang Zheng; Jia-Wei Qian; Ping-Feng Li; Zhi-Qiang Yin; Huan-Ting Zhao (Applied Geophysics, 2024)

Rainstorm and strong wind weathers largely increase greenhouse gases flux in shallow ponds - Yifei Zhang; Ping Yang; Yang Wang; Guanghui Zhao; Zhuangpeng Zheng; Yuxing Zou; Yiwen Zhang; Siyue Li (Science of The Total Environment, 2024)

Experimental investigation and numerical modeling of effect of specimen size on microwave-induced fracturing of diorite - Zhongjun Ma; Yanlong Zheng; Fuxin Rui; Gaofeng Zhao; Jianchun Li; Ping Che (Minerals Engineering, 2024)

Artificial microbial consortia engineering: Intensify nitrogen removal from mature landfill leachate by simultaneous nitrification and denitrification - Xia Ke; Yi-Xin Li; Ting-Ting Guo; Zu-Lian Liao; Su-Qin Tang; Yi-Cheng Zhang; Shi-Peng Zhou; Ya-Ping Xue; Yu-Guo Zheng (Journal of Water Process Engineering, 2024)

Straw management adopted by large farms sustains grain yield but mitigates greenhouse gas emissions - Zhenzhen Li; Yong Lin; Zheng-Rong Kan; Sana ur Rehman; Atta Mohi Ud Din; Feng-Min Li; Shixiang Zhang; Ping Wu; Yingfu Ding; Chensheng Xu; Congying Rao; Huaxin Dai; et al. (Field Crops Research, 2024)

LncRNA NR_030777 promotes mitophagy by targeting CDK1-related mitochondrial fission and ATG12 to attenuate paraquat-induced Parkinson's disease - Nengzhou Chen; Hong Hu; Jianping Tang; Fuli Zheng; Zhenkun Guo; Xinpei Lin; Michael Aschner; Wenya Shao; Guangxia Yu; Ping Cai; Wei-Chun Chou; Siying Wu; et al. (Environmental Pollution, 2024)

A bipolar SMPS network for measuring atmospheric aerosols using natural air ions - Yiran Li; Jin Wu; Hao Wu; Xiaomeng Liu; Qi Zhou; Yiqun Lu; Yuhang Wu; Mengyu Liu; Hengjia Ou; Shixin Mai; Xuehui He; Huaying Song; et al. (Atmospheric Environment, 2024)

Proposal of Streptomyces bellus Margalith and Beretta 1960 as a Later Heterotypic Synonym of Streptomyces coeruleorubidus (Preobrazhenskaya 1957) Pridham et al. 1958 and an Emended Description of Streptomyces coeruleorubidus - Yi Peng; Ping Mo; Yaxi Zheng; Chenxi Li; Kerui Huang (Current Microbiology, 2024)

Unveiling the inhibitory mechanisms of chromium exposure on microbial reductive dechlorination: Kinetics and microbial responses - Zheng-Tao Li; Xin Song; Songhu Yuan; He-Ping Zhao (Water Research, 2024)

Gamma-ray irradiation as an effective method for mitigating antibiotic resistant bacteria and antibiotic resistance genes in aquatic environments - Ming-Qi Zhang; Xiao-Yong Zhang; Han-Chao Zhang; Hai-Bin Qiu; Zheng-Hao Li; Dong-Hua Xie; Li Yuan; Guo-Ping Sheng (Journal of Hazardous Materials, 2024)

Application of iron tailings in the coagulation of landfill leachate by bipolar membrane electrodialysis - Yanchao Jin; Guodong Wang; Zheng Li; Chun-Yan Lin; Li-Ping Li; Xiao Chen; Rui Ding; Jianxi Liu; Riyao Chen (Journal of Cleaner Production, 2024)

Cognitive Deficits and Alzheimer’s Disease-Like Pathologies in the Aged Chinese Tree Shrew - Hongli Li; Bo-Lin Xiang; Xiao Li; Cong Li; Yu Li; Ying Miao; Guo-Lan Ma; Yu-Hua Ma; Jia-Qi Chen; Qing-Yu Zhang; Long-Bao Lv; Ping Zheng; et al. (Molecular Neurobiology, 2024)

Microbial colony sequencing combined with metabolomics revealed the effects of chronic hexavalent chromium and nickel combined exposure on intestinal inflammation in mice - Yueming Gu; Shuangyan Zheng; Cheng Huang; Xianhong Cao; Ping Liu; Yu Zhuang; Guyue Li; Guoliang Hu; Xiaona Gao; Xiaoquan Guo (Science of The Total Environment, 2024)

Active dark carbon fixation evidenced by 14C isotope assimilation and metagenomic data across the estuarine-coastal continuum - Bolin Liu; Yanling Zheng; Xinyu Wang; Lin Qi; Jie Zhou; Zhirui An; Li Wu; Feiyang Chen; Zhuke Lin; Guoyu Yin; Hongpo Dong; Xiaofei Li; et al. (Science of The Total Environment, 2024)

Multistage and diverse melt-mantle interaction in dunite-harzburgite channel systems beneath oceanic slow-ultraslow spreading centers: Evidence from the Xigaze ophiolite (Tibet) - Li Wang; Qing Xiong; Jian-Ping Zheng; Hong-Kun Dai; Lian-Rong Tian; Xiang Zhou (Lithos, 2024)

Efficient capture of iodine in steam and water media by hydrogen bond-driven charge transfer complexes - Li Zhang; Yu-Ting Luo; Jia-Qi Fan; Sai-Jin Xiao; Qiong-Qing Zheng; Xiao-Lin Liu; Quan-Gen Tan; Chen Sun; Qiang Shi; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2024)

Sustainable management and valorization of biomass wastes using synthetic microbial consortia - Shi-Peng Zhou; Xia Ke; Li-Qun Jin; Ya-Ping Xue; Yu-Guo Zheng (Bioresource Technology, 2024)

Dissection and validation of quantitative trait loci (QTLs) conferring grain size and grain weight in rice - Ping Sun; Yuanyuan Zheng; Pingbo Li; Hong Ye; Hao Zhou; Guanjun Gao; Qinglu Zhang; Yuqing He (Euphytica, 2024)

Formation and prolonged preservation of dense arc root cumulates: insights from retrograded eclogite xenoliths in the western Yangtze craton - Min Wang; Jian-Ping Zheng; Hong-Kun Dai; Qing Xiong; Yi-Xiong Li; Jin-Wei Guo (Contributions to Mineralogy and Petrology, 2024)

Dietary ellagic acid supplementation improves meat quality in growing-finishing pigs - Tengteng Huang; Huawei Li; Xiaoling Chen; Daiwen Chen; Jun He; Bing Yu; Yuheng Luo; Ping Zheng; Hong Chen; Zhiqing Huang (Animal Feed Science and Technology, 2024)

A system dynamics simulation-based strategic analysis of integrated water resources utilization and management in Shenzhen city - Guangzhi Zheng; Jing-Cheng Han; Ping Li; Bing Li; Xiaofeng Wu; Yuefei Huang; Muhammad Ahmad (Environmental Science and Pollution Research, 2024)

A framework for nonlinear peak response evaluation from linear response spectra of base-isolated structures using the bilinear hysteretic model - Kui Yang; Ping Tan; Huating Chen; Jiaxi Li; Wenzhi Zheng (Soil Dynamics and Earthquake Engineering, 2024)

Road dust exposure and human corneal damage in a plateau high geological background provincial capital city: Spatial distribution, sources, bioaccessibility, and cytotoxicity of dust heavy metals - Zi-Yue Yang; Hai Liu; Jing-Ya Li; Ya-Bo Bao; Ji Yang; Li Li; Zi-Yu Zhao; Qin-Xiang Zheng; Ping Xiang (Science of The Total Environment, 2024)

Iridoid and lignan glycosides from Lancea tibetica - Yi Zhu; Junlin Wang; Lu Tang; Yuxin Shang; Weiyi Zhao; Wei Zhang; Ping Hai; Yongbiao Zheng; Wenbo Li; Yanfang Su (Phytochemistry Letters, 2024)

Investigation on the failure mechanism of a tunnel entrance high-steep slope with ultra-large wedge blocks based on discrete element method - Huai-sheng Xu; Shao-jun Li; Ding-ping Xu; Xiu-yang Liu; Yue-lin Xia; Guan-qi Wang; Xing-dong Ma; Zheng-jun Zhou (Computers and Geotechnics, 2024)

Layered double hydroxide@zeolite composite modified sponge: A versatile biocarrier for enhancing nitrogen removal in biofilters - Zhuwu Jiang; Mengfan Wu; Panyang Gu; Wenzhong Huang; Chang-Ping Yu; Zhongjian Zheng; Yanqu Wang; Ning Yao; Yan Li (Chemical Engineering Journal, 2024)

Effects of nitrogen supply on hydrogen-oxidizing bacterial enrichment to produce microbial protein: Comparing nitrogen fixation and ammonium assimilation - Haoran Wang; Lixia Zhang; Chang Tian; Sen Fan; Decong Zheng; Yuhan Song; Ping Gao; Daping Li (Bioresource Technology, 2024)

Phycoremediation and valorization of hypersaline pickled mustard wastewater via Chaetoceros muelleri and indigenous bacteria - Kai Zhang; Shuqin Jiang; Juan Zhang; Jishu Zheng; Ping Li; Song Wang; Ru Bi; Lihong Gao (Bioresource Technology, 2024)

Electrochemical surface plasmon resonance approach to probe redox interactions between microbial extracellular polymeric substances and p-nitrophenol - Wei Shao; Xin Zhang; Zheng-Hao Li; Juan Xu; Guo-Ping Sheng (Journal of Environmental Management, 2024)

FAM21 interacts with Ku to promote the localization of WASH to DNA double strand break sites - Tao Wang; Ai-Xue Zheng; Ping Li; Tuo Tang; Lu-Ping Zhang; Yu Hong; Xian Hong; Zhi-Hui Deng (DNA Repair, 2024)

Multidentate anchoring strategy for synergistically modulating crystallization and stability towards efficient perovskite solar cells - Ping Hu; Wenbo Zhou; Junliang Chen; Xin Xie; Jingwei Zhu; Yuxin Zheng; Yafeng Li; Junming Li; Mingdeng Wei (Chemical Engineering Journal, 2024)

Lipopolysaccharides from a Shiraia fruiting body-associated bacterium elicit host fungal hypocrellin A biosynthesis through nitric oxide generation - Xin Ping Li; Wen Hao Shen; Lu Lu Zhou; Qun Yan Huang; Rui Peng Cong; Li Ping Zheng; Jian Wen Wang (Carbohydrate Polymers, 2024)

Preparation and characterization of lotus root starch based bioactive edible film containing quercetin-encapsulated nanoparticle and its effect on grape preservation - Ya-Fan Zeng; Ying-Ying Chen; Yuan-Yuan Deng; Chao Zheng; Cheng-Zhi Hong; Qiang-Ming Li; Xue-Fei Yang; Li-Hua Pan; Jian-Ping Luo; Xue-Ying Li; Xue-Qiang Zha (Carbohydrate Polymers, 2024)

Mechanism of Antidepressant Action of (2R,6R)-6-Hydroxynorketamine (HNK) and Its Compounds: Insights from Proteomic Analysis - Chaohui Zhen; Chong Wang; Yanjun Ma; Yuli Pang; Feiyue Cai; Jiali Meng; Yuefei He; Ping Xiao; Jianxi Liu; Xi Mei; Shupeng Li; Guanzheng Wu; et al. (Molecular Neurobiology, 2024)

Adipose Tissue Exosome circ_sxc Mediates the Modulatory of Adiposomes on Brain Aging by Inhibiting Brain dme-miR-87-3p - Qiufang Li; Lingxiao Wang; Chao Tang; Xiaoya Wang; Zhengwen Yu; Xu Ping; Meng Ding; Lan Zheng (Molecular Neurobiology, 2024)

Self-assembly construction of 1D carbon nitride nanotubes and cobalt-modified for superior photocatalytic degradation of sulfonamide antibiotics - Zifeng Lin; Zhongquan Wang; Zihong Xu; Zhenjun Xiao; Zheng Fang; Jin Luo; Ping Li; Ping Chen; Wenying Lv; Guoguang Liu (Chemosphere, 2023)

Enhanced resuscitation of anammox granular sludge by adding folate: A perspective from the growth factor - Chao Pan; Leiyan Guo; Yang Yu; Wenji Li; Dongdong Xu; Wenda Chen; Lin Zhu; Baolan Hu; Ping Zheng; Meng Zhang (Chemical Engineering Journal, 2023)

Transposon-based identification of genes involved in the rimocidin biosynthesis in Streptomyces rimosus M527 - Hai-yue Bao; Hui-jie Li; Yong-yong Zhang; Andreas Bechthold; Xiao-ping Yu; Zheng Ma (World Journal of Microbiology and Biotechnology, 2023)

Bamboo polysaccharides elicit hypocrellin A biosynthesis of a bambusicolous fungus Shiraia sp. S9 - Wen Hao Shen; Lu Lu Zhou; Xin Ping Li; Rui Peng Cong; Qun Yan Huang; Li Ping Zheng; Jian Wen Wang (World Journal of Microbiology and Biotechnology, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Enhancing data reliability in quantitative characterization of moisture distribution in sludge using DSC: Impact of sample attributes and test parameters - Ya-Li Zhang; Hao Zhang; Wen-Hui Liu; Ping Sun; Shao-Ming Zheng; Yun-Yan Gao; Yuan-Ping Zeng; Hou-Feng Wang; Raymond Jianxiong Zeng (Journal of Environmental Management, 2023)

The effects of arsenic on dechlorination of trichloroethene by consortium DH: Microbial response and resistance - Zheng-Tao Li; Si-Ying Yang; He-Ping Zhao (Science of The Total Environment, 2023)

Late-Permian subduction-to-collision transition and closure of Paleo-Asian Ocean in eastern Central Asian Orogenic Belt: Evidence from borehole cores in the Songliao Basin, Northeast China - Haihua Zhang; Liang Qiu; Dan-Ping Yan; Zifu Zhao; Keda Cai; Jian Zhang; Shuwang Chen; Yongfei Li; Ying Song; Yuejuan Zheng; Shouliang Sun; Fanhao Gong; et al. (Gondwana Research, 2023)

Application of UPLC-Triple TOF-MS/MS metabolomics strategy to reveal the dynamic changes of triterpenoid saponins during the decocting process of Asian ginseng and American ginseng - Li-Hua Chen; You-Bo Zhang; Xiu-Wei Yang; Jing Xu; Zhao-Jing Wang; Yi-Zheng Sun; Wei Xu; Ying-Ping Wang (Food Chemistry, 2023)

Bioelectrochemical system accelerates reductive dechlorination through extracellular electron transfer networks - Su-Hao Chen; Zheng-Tao Li; He-Ping Zhao (Environmental Research, 2023)

Refining health risk assessment of arsenic in wild edible boletus from typical high geochemical background areas: The role of As species, bioavailability, and enterotoxicity - Mengying Li; Zheng Chen; Qing Xiong; Yunzhen Mu; Yumei Xie; Mengyan Zhang; Lena Q. Ma; Ping Xiang (Environmental Pollution, 2023)

Near-infrared-triggered chirality-dependent photodynamic therapy based on hybrid upconversion nanoparticle hydrogels - Tianyong Guan; Yan Liu; Jiayao Li; Mingmao Chen; Xiaoying Shang; Ping Hu; Renfu Li; Hang Gao; Datao Tu; Wei Zheng; Xueyuan Chen (Chemical Engineering Journal, 2023)

The culprit for the declining performance of anaerobic reactors caused by calcification: Bioavailability deterioration - Wenda Chen; Huiming Tang; Dongdong Xu; Wenji Li; Chao Pan; Leiyan Guo; Da Kang; Ping Zheng; Meng Zhang (Bioresource Technology, 2023)

Ecological distribution of anaerobic granular sludge towards efficient anaerobic reactor - Wenda Chen; Huiming Tang; Dongdong Xu; Wenji Li; Chao Pan; Leiyan Guo; Da Kang; Baolan Hu; Ping Zheng; Meng Zhang (Bioresource Technology, 2023)

Proteomic profile of the germinating seeds reveals enhanced seedling growth in Arabidopsis rpp1a mutant - Lu Zheng; Peijun Zhou; Yilin Pan; Bingjuan Li; Renfang Shen; Ping Lan (Plant Molecular Biology, 2023)

The Epidemiology of Tinea Capitis in Guangxi Province, China - Dongyan Zheng; Tianwei Liang; Weixuan Wu; Najwa Al-Odaini; Kaisu Pan; Lan Huang; Guomei Huang; Lulu Tang; Xinlei Li; Shao He; Huahui Jian; Nibo Wei; et al. (Mycopathologia, 2023)

Experimental research progress of grid to rod fretting in pressurized water reactors - Yong-jun Jiao; Zheng-yang Li; Zeng-ping Pu; Mei-yin Zheng; Quan-yao Ren; Zhen-bing Cai; Yin-wei Wu; Sui-zheng Qiu (Annals of Nuclear Energy, 2023)

Assessing tunnel basement structure damage under train excitation: Impacts of surrounding rock deterioration - Zi-Qiang Li; Kun-ping Chen; Wei-wei Huang; Jian-wen Feng; Hang Zhang; Zheng Li; Shi-jian Yang (Transportation Geotechnics, 2023)

Ridge tillage increased halophyte fine root production and turnover rates by altering soil properties in an abandoned farmland in northwest China - Xu Zheng; Chao-qun Chen; Lu-hua Li; Jia-ping Wang (Rhizosphere, 2023)

A novel global snow depth retrieval method considering snow metamorphism and forest influence - Shuo Gao; Zhen Li; Ping Zhang; Quan Chen; Lei Huang; Jianmin Zhou; Changjun Zhao; Haiwei Qiao; Zhaojun Zheng (Remote Sensing of Environment, 2023)

In-situ gas flow separation between biochar and the heat carrier in a circulating fluidized bed reactor for biomass pyrolysis - Zheng-hao Yang; Zhen He; Xiang-gang Zhang; Xia Jiang; Zi-heng Jin; Jian-ping Li; Liang Ma; Hua-lin Wang; Yu-long Chang (Chemical Engineering Journal, 2023)

Towards intensified preservation technology of anammox granular sludge: Insights into the role of energy support - Chao Pan; Wenji Li; Dongdong Xu; Wenda Chen; Leiyan Guo; Da Kang; Baolan Hu; Ping Zheng; Meng Zhang (Chemical Engineering Journal, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Distinct chromium removal mechanisms by iron-modified biochar under varying pH: Role of iron and chromium speciation - Lecheng Liu; Ping Sun; Youyuan Chen; Xiaochen Li; Xilai Zheng (Chemosphere, 2023)

Face mask derived micro(nano)plastics and organic compounds potentially induce threat to aquatic ecosystem security revealed by toxicogenomics-based assay - Yan-Jun Liu; He-Yun Yang; Yan-Yun Hu; Zheng-Hao Li; Hao Yin; Yun-Tian He; Keng-Qiang Zhong; Li Yuan; Xing Zheng; Guo-Ping Sheng (Water Research, 2023)

Quantitative evaluation for the sources and aging processes of organic aerosols in urban Guangzhou: Insights from a comprehensive method of dual‑carbon isotopes and macro tracers - Fan Jiang; Junwen Liu; Zhineng Cheng; Ping Ding; Sanyuan Zhu; Xin Yuan; Wei Chen; Zhisheng Zhang; Zheng Zong; Chongguo Tian; Weiwei Hu; Junyu Zheng; et al. (Science of The Total Environment, 2023)

Antibiotic resistomes in face-mask biofilm along an urban river: Multiple drivers and co-occurrence with human opportunistic pathogens - Yan-Jun Liu; Zheng-Hao Li; Yun-Tian He; Li Yuan; Guo-Ping Sheng (Journal of Hazardous Materials, 2023)

Enhanced photochemical degradation and transformation of ciprofloxacin in a UV/calcium peroxide system: pH effects, defluorination kinetics, and different components numerical analysis - Zheng Fang; Zifeng Lin; Ping Chen; Mengying Feng; Haijin Liu; Zhenjun Xiao; Zili Lin; Dagaung Li; Dezhu Liu; Yudan Zhang; Wenying Lv; Guoguang Liu (Journal of Cleaner Production, 2023)

Laboratory characterization of soft clay mixed with EPS, lime, fly ash, and sodium silicate - Ping Jiang; Wenqian Zheng; Lin Zhou; Na Li; Wei Wang (Bulletin of Engineering Geology and the Environment, 2023)

Comprehensive analysis of the key amino acid substitutions in the polymerase and NP of avian influenza virus that enhance polymerase activity and affect adaptation to mammalian hosts - Yanna Guo; Tongtong Sun; Xuebing Bai; Bing Liang; Lulu Deng; Yiqing Zheng; Mengqi Yu; Yinjing Li; Jihui Ping (Veterinary Microbiology, 2023)

Sinomenine ameliorates rheumatoid arthritis by modulating tryptophan metabolism and activating aryl hydrocarbon receptor via gut microbiota regulation - Zheng-Meng Jiang; Su-Ling Zeng; Tian-Qing Huang; Yang Lin; Fang-Fang Wang; Xing-Jiao Gao; Jing Li; Ping Li; E-Hu Liu (Science Bulletin, 2023)

Saltwater incursion regulates N2O emission pathways and potential nitrification and denitrification in intertidal wetland - Yinghui Jiang; Guoyu Yin; Ye Li; Lijun Hou; Min Liu; Cheng Chen; Dongsheng Zheng; Han Wu; Dengzhou Gao; Yanling Zheng; Ping Han (Biology and Fertility of Soils, 2023)

Inactivation of epithelial sodium ion channel molecules serves as effective diagnostic biomarkers in clear cell renal cell carcinoma - Qian Zheng; Yifang Wang; Ran Zhao; Peipei Han; Jun Zhao; Limei Li; Xiaohui Zhou; Ping Li; Yingxi Mo; Xinli Pan; Wenqi Luo; Xiaoying Zhou (Genes & Genomics, 2023)

A facile approach to undecylenic acid-functionalized stationary phases for per aqueous liquid chromatography - Xiao-Dong Cheng; Zheng Zhang; Yun-Ping Li (Analytica Chimica Acta, 2023)

Detoxification mechanisms of biochar on plants in chromium contaminated soil: Chromium chemical forms and subcellular distribution - Ping Sun; Youyuan Chen; Xiaochen Li; Lecheng Liu; Jiameng Guo; Xilai Zheng; Xiaoli Liu (Chemosphere, 2023)

Transcriptomic and physiological analysis of the effect of octanoic acid on Meloidogyne incognita - Jian-Yu Wang; Qiu-Yue Li; Li Ren; Cheng Guo; Jian-Ping Qu; Zheng Gao; Hui-Fang Wang; Qian Zhang; Bo Zhou (Pesticide Biochemistry and Physiology, 2023)

Novel insights into versatile nanomaterials integrated bioreceptors toward zearalenone ultrasensitive discrimination - Quanliang Li; Xiyu Wang; Xiaomeng Wang; Lin Zheng; Ping Chen; Biying Zhang (Food Chemistry, 2023)

What affects the accuracy and applicability of determining wastewater sludge water content via low-field nuclear magnetic resonance? - Ya-Li Zhang; Ping Sun; Bing-Bing Dai; Shao-Ming Zheng; Dan-Di Ran; Tian-Xin Wu; Raymond Jianxiong Zeng; Hou-Feng Wang (Environmental Research, 2023)

Superelastic pendulum isolator with multi-stage variable curvature for seismic resilience enhancement of cold-regional bridges - Wenzhi Zheng; Ping Tan; Jian Li; Hao Wang; Yanhui Liu; Zhibin Xian (Engineering Structures, 2023)

Confined and mediated intercalation of nanoparticles in graphene oxide membrane to fine-tune desalination performance - Siyu Zhou; Kecheng Guan; Zheng Wang; Qiangqiang Song; Zhan Li; Ping Xu; Luyao Deng; Shang Xiang; Hideto Matsuyama (Chemical Engineering Journal, 2023)

The mechanisms of rapid seed germination in Caragana species adapted to low mean annual precipitation - Shi-Hua Qi; Guang-Qian Yao; Md. Mahadi Hasan; Hui Jiang; Xu-Dong Liu; Zheng-Fei Nie; Xia-Yi Zhang; Ya-Xian Du; Xue-Qian Tian; Feng-Ping Li; Xue-Rong Li; Xiang-Wen Fang (Trees, 2023)

Stellate ganglion block suppresses hippocampal ferroptosis to attenuate cerebral ischemia-reperfusion injury via the Hippo pathway - Chunwang Zhou; Mengyuan Li; Yingxin Chu; Liyan Zheng; Shubo Zhang; Xiujiang Gao; Ping Gao (Metabolic Brain Disease, 2023)

Investigation of the stability and failure mechanism of slopes in Xiyu conglomerate due to toe erosion - Qiang Zhang; Yanni Zheng; Chaojun Jia; Ping Sun; Wenxin Li (Bulletin of Engineering Geology and the Environment, 2023)

Multiple Episodes of Zircon Growth during Anatectic Metamorphism of Metasedimentary Rocks in Collisional Orogens: Constraints from Felsic Granulites in the Bohemian Massif - Guang Yang; Ren-Xu Chen; Yong-Fei Zheng; Qiong-Xia Xia; Yong-Jie Yu; Kun Li; Zhaochu Hu; Bing Gong; Xiang-Ping Zha (Journal of Earth Science, 2023)

Corrigendum to “Identification of sex-linked marker and candidate sex determination gene in ornamental fish, African scat (Scatophagus tetracanthus)” [Aquaculture 563 (2023) /739023] - You-Xing Peng; Yuan-Qing Huang; Jian Zhong; Zheng-Ting Jiang; Sen Fan; Hong-Juan Shi; Hua-Pu Chen; Si-Ping Deng; Guang-Li Li; Dong-Neng Jiang (Aquaculture, 2023)

Effects of disinfectants, sponge densities, water circulation rates, and vibration frequency on the artificial incubation of redclaw crayfish embryos - Cheng Shun; Jiang Wen-ping; Liu Shi-li; Chi Mei-li; Zheng Jian-bo; Liu Yi-nuo; Hang Xiao-ying; Peng Miao; Li Fei; Wang Dan-li (Aquaculture, 2023)

Southern Ocean warming and its climatic impacts - Wenju Cai; Libao Gao; Yiyong Luo; Xichen Li; Xiaotong Zheng; Xuebin Zhang; Xuhua Cheng; Fan Jia; Ariaan Purich; Agus Santoso; Yan Du; David M. Holland; et al. (Science Bulletin, 2023)

An oligosaccharide marker for rapid authentication of edible bird’s nest - Li-Feng Li; Hui-Yuan Cheng; Jun Lang; Tin-Long Wong; Ji-Xia Zhang; Wen-Jie Wu; Quan-Wei Zhang; Hau-Yee Kong; Check-Hei Lai; Hau-Yee Fung; Man Liu; Wan-Rong Bao; et al. (Food Chemistry, 2023)

Considering flood scaling property in multi-objective calibration of the SWAT model: a case study in Zijinguan watershed, Northern China - Yanchen Zheng; Jianzhu Li; Ting Zhang; Youtong Rong; Ping Feng (Natural Hazards, 2023)

Extracellular Vesicles Derived from Bone Mesenchymal Stem Cells Carrying circ_0000075 Relieves Cerebral Ischemic Injury by Competitively Inhibiting miR-218-5p and Up-regulating E3 Ubiquitin Ligase SMURF2 - Yue Liu; You-Ping Li; Li-Min Xiao; Li-Ke Chen; Su-Yue Zheng; Er-Ming Zeng; Chun-Hua Xu (Molecular Neurobiology, 2023)

Elevated Interleukin-37 Associated with Dengue Viral Load in Patients with Dengue Fever - Jun-Ai Zhang; Jia-Jun Wang; Wen-Ting Zhang; Li Zhang; Bi-Ying Zheng; Gan-Bin Liu; Jing Liang; Yuan-Bin Lu; Xian-Jin Wu; Shu-Ying Yao; Guo-Ying Chen; Yun-Qi Xie; et al. (Current Microbiology, 2023)
Dengue remains a public health issue worldwide. Similar to chronic infectious diseases, stimulation of cytokine production is not enough to drive immune effector cells for effective virus clearance. One possible mechanism is the virus induces a large number of negative stimulatory cytokines inhibiting immune response. Interleukin 37 (IL-37) plays a crucial regulatory role in infection and immunity, inhibits innate and adaptive immunity as an anti-inflammatory cytokine by inhibiting proinflammatory mediators and pathways. To date, there are few studies reporting correlations between dengue fever (DF) and IL-37. In this study we found that the serum IL-37b and IL-37b-producing monocytes in patients were significantly increased in DF patients. A majority of the IL-37b produced by DF patients was produced by monocytes, not lymphocytes. Increased levels of IL-6, IL-10, and IFN-α were also found in DF patients. However, we failed to detect IL-1β, IL-17A and TNF-α in plasma, because of off-target. In our study, there was no relation between IL-6, IL-10, and IFN-α expressions and IL-37b in serum ( P > 0.05). The IL-37b-producing monocytes were negatively correlated with the level of IFN-α in serum and platelet count, and positively correlated with lymphocytes percentage ( P < 0.05, respectively). Additionally, serum DENV nonstructural protein 1 levels were positively correlated with monocytes percentages ( P < 0.05). Our data represents findings for IL-37b expression and its potential mechanisms in DF patients’ immune response.

Water transport in continental subduction zones: Constraints from eclogite from the Dabie orogen, east-central China - Zhi-Min Wang; Ren-Xu Chen; Yong-Fei Zheng; Shuning Li; Lin Zhu; Bing Gong; Xiang-Ping Zha; Wan-Cai Li (Journal of Asian Earth Sciences, 2023)

Carbon nanofibers with gas selective layer containing rich and accessible ultramicropores for methane/nitrogen separation - Tian-Yi Li; Yong-Sheng Wang; Meng-Yao Zhang; Bo-Yang Liu; Zhe Zheng; Guang-Ping Hao; An-Hui Lu (Chemical Engineering Journal, 2023)

Tailorable carbon cloth electrodes covered with heterostructured Co/CoO/CoN interfaces for scalable electrocatalytic overall water splitting - Wei Zhang; Cong Li; Jun-Yang Ji; Zheng Niu; Hongwei Gu; Brendan F. Abrahams; Jian-Ping Lang (Chemical Engineering Journal, 2023)

Valorization of lignin through reductive catalytic fractionation of fermented corn stover residues - Wen-Zheng Yin; Ling-Ping Xiao; Shuang-Lin Zou; Wen-Xin Li; Hongliang Wang; Run-Cang Sun (Bioresource Technology, 2023)

Single-base resolution mapping of 2′-O-methylation sites by an exoribonuclease-enriched chemical method - Ping Zhang; Junhong Huang; Wujian Zheng; Lifan Chen; Shurong Liu; Anrui Liu; Jiayi Ye; Jie Zhou; Zhirong Chen; Qiaojuan Huang; Shun Liu; Keren Zhou; et al. (Science China Life Sciences, 2023)

In Vitro Antifungal Activity of Azoles and Other Antifungal Agents Against Pathogenic Yeasts from Vulvovaginal Candidiasis in China - Siyue Kan; Nana Song; Qiuyu Pang; Huan Mei; Hailin Zheng; Dongmei Li; Fan Cui; Guixia Lv; Ruifang An; Ping Li; Zhengai Xiong; Shangrong Fan; et al. (Mycopathologia, 2023)

An in-situ strategy to construct uracil-conjugated covalent organic frameworks with tunable fluorescence/recognition characteristics for sensitive and selective Mercury(II) detection - Xi-Rui Deng; A-Wei Hu; Sheng-Qian Hu; Wen-Li Yang; Chen Sun; Sai-Jin Xiao; Gui-Ping Yang; Qiong-Qing Zheng; Ru-Ping Liang; Li Zhang; Jian-Ding Qiu (Analytica Chimica Acta, 2023)

Thallium removal from wastewater using sulfidized zero-valent manganese: Effects of sulfidation method and liquid nitrogen pretreatment - Zhengqin Shi; Ping Zhang; Xiaohan Li; Yijie Zheng; Juanxi Huang; Yaxuan Wang; Xiatiao Luo; Gaosheng Zhang; Tangfu Xiao; Jianyou Long; Huosheng Li (Chemosphere, 2023)

Effects of Reticuloendotheliosis virus on TLR-3/IFN-Β pathway in specific pathogen-free chickens - Wen-Jie Wu; Xiao-Ping Lv; Xiao-Yan Wang; Xue-Li Gao; Chao-Nan Liu; Chen-Hui Zhao; Xian-Zhe Gu; Shi-Min Zheng (Research in Veterinary Science, 2023)

Petrogenesis of the Chakabeishan pegmatites, North Qaidam Terrane: Implications for Indosinian lithium mineralization in the northern Tibetan Plateau - Jin-Heng Liu; Qiang Wang; Bing-Zhang Wang; Wu-Fu Li; Chuan-Bing Xu; Shan-Ping Li; Zi-Long Wang; Lu-Lu Hao; Tai-Zhong Song; Chun-Tao Wang; Ying Zheng; Jin-Shou Wang (Lithos, 2023)

Molecular characterization of a teleost-specific toll-like receptor 22 (tlr22) gene from yellow catfish (Pelteobagrus fulvidraco) and its transcriptional change in response to poly I:C and Aeromonas hydrophila stimuli - Xiu-Ying Wei; Jun Wang; Sheng-Tao Guo; Yun-Yun Lv; Yan-Ping Li; Chuan-Jie Qin; Yuan-Chao Zou; Qing-Chao Shi; Peng Hu; Xiao-Qin Xiong; Yang He; Rui Li; et al. (Fish & Shellfish Immunology, 2023)

Nitrogen loss from anaerobic ammonium oxidation coupled to Iron(III) reduction activity across estuarine and coastal wetlands of China: Spatial variations, controlling factors, and environmental implications - Shuntao Chen; Dengzhou Gao; Xiaofei Li; Dongyao Sun; Yanling Zheng; Hongpo Dong; Xia Liang; Guoyu Yin; Ping Han; Min Liu; Lijun Hou (CATENA, 2023)

Glucocorticoid and glycolysis inhibitors cooperatively abrogate acute graft-versus-host disease - Qi Wen; Zheng-Li Xu; Yu Wang; Meng Lv; Yang Song; Zhong-Shi Lyv; Tong Xing; Lan-Ping Xu; Xiao-Hui Zhang; Xiao-Jun Huang; Yuan Kong (Science China Life Sciences, 2023)

24-Epibrassinolide Enhances Resistance Against Colletotrichum fructicola by Promoting Lignin Biosynthesis in Camellia sinensis L. - Lan Zhang; Zheng Zhang; Golam Jalal Ahammed; Xiaorong Wang; Huihan Fang; Peng Yan; Li-Ping Zhang; Shibei Ge; Jianyu Fu; Wen-Yan Han; Xin Li (Journal of Plant Growth Regulation, 2023)

RETRACTED ARTICLE: Hedgehog signaling-related genomics signature for the accurate progress and prognosis prediction in gastric cancer - Guoliang Zhang; Guojun Xia; Jungang Luo; Ping Ye; Huangen Wang; Shaodong Li; Difeng Zheng (Functional & Integrative Genomics, 2023)

ARSCP: An antimicrobial residue surveillance cloud platform for animal-derived foods - Jun-Jun Yu; Ya-Lin Hu; Cheng-Zheng Liu; Shuai-Bin Wu; Zi-Jian Zheng; Ze-Hua Cui; Li Chen; Tian Wei; Shi-Kai Sun; Jun Ning; Xiang Wen; Qiu-Yue Diao; et al. (Science of The Total Environment, 2023)

Morphological evolution of paired sand spits at the Fudu river mouth: Wave effects and anthropogenic factors - Shanhang Chi; Chi Zhang; Ping Wang; Jian Shi; Fangming Li; Yuan Li; Peng Wang; Jinhai Zheng; Jiawen Sun; Viet Thanh Nguyen (Marine Geology, 2023)

Caenorhabditis elegans: a nature present for advanced food science - Yonglu Li; Yadi Wang; Ping Li; Qingqing Zhou; Xiaodong Zheng; Qing Gu (Current Opinion in Food Science, 2023)

Holdup of sub-granules towards enhanced production of anammox sludge in a dual circulation sludge bed reactor - Dongdong Xu; Wenda Chen; Chao Pan; Wenji Li; Leiyan Guo; Da Kang; Ping Zheng; Baolan Hu; Meng Zhang (Chemical Engineering Journal, 2023)

A 2D mesoporous hydrazone covalent organic framework for selective detection and ultrafast recovery of Au(III) from electronic waste - Li Zhang; Jia-Qi Fan; Qiong-Qing Zheng; Sai-Jin Xiao; Cheng-Rong Zhang; Shun-Mo Yi; Xin Liu; Wei Jiang; Quan-Gen Tan; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

Potential for volatile fatty acid production via anaerobically-fermenting rice straw pretreated with silage effluent and phenyllactic acid - Hong Sun; Chaosheng Liao; Liangyin Chen; Qiming Cheng; Yulong Zheng; Chunmei Wang; Yixiao Xie; Chao Chen; Ping Li (Bioresource Technology, 2023)

Identification of sex-linked marker and candidate sex determination gene in ornamental fish, African scat (Scatophagus tetracanthus) - You-Xing Peng; Yuan-Qing Huang; Jian Zhong; Zheng-Ting Jiang; Sen Fan; Hong-Juan Shi; Hua-Pu Chen; Si-Ping Deng; Guang-Li Li; Dong-Neng Jiang (Aquaculture, 2023)

Effects of light color, photoperiod, and growth-related gene interference or overexpression on the survival, growth, or physiological and biochemical indices of red claw crayfish juveniles - Shun Cheng; Jian-bo Zheng; Yong-yi Jia; Mei-li Chi; Wen-ping Jiang; Shi-li Liu; Fei Li; Yi-nuo Liu; Zhi-min Gu; Dan-li Wang (Aquaculture, 2023)

Influence of facing conditions on the dynamic response of back-to-back MSE walls - Yewei Zheng; Fuxiu Li; Wenhao Guo; Ping Wang; Guangqing Yang (Soil Dynamics and Earthquake Engineering, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Ultra-depleted melt product preserved in the Ladong ophiolitic peridotites of the North Qilian Orogenic Belt, Northern Tibet - Xiang Zhou; Jian-Ping Zheng; Zeng-Bao Huang; Zhi-Yong Li; Wei-Qi Zhang; Hong-Da Zheng; Qing Xiong; Hong-Kun Dai (Lithos, 2023)

Enhancing flotation removal of unburned carbon from fly ash by coal tar-based collector: Experiment and simulation - Kanghao Zheng; Wenjun Zhang; Yijiang Li; An Ping; Feng Wu; Guangyuan Xie; Wencheng Xia (Fuel, 2023)

Seismic performance upgrading of bridges using superelastic pendulum isolators with variable stiffness considering temperature effects - Wenzhi Zheng; Ping Tan; Jian Li; Hao Wang; Yanhui Liu; Kui Yang (Engineering Structures, 2023)

Regulating electronic structure by Mn doping for nickel cobalt hydroxide nanosheets/carbon nanotube to promote oxygen evolution reaction and oxidation of urea and hydrazine - Kaili Wu; Chenyang Cao; Keren Li; Chaojie Lyu; Jiarun Cheng; Hongyu Li; Pengfei Hu; Jiwen Wu; Woon-Ming Lau; Xixi Zhu; Ping Qian; Jinlong Zheng (Chemical Engineering Journal, 2023)

Insights into CQDs-doped perylene diimide photocatalysts for the degradation of naproxen - Zheng Fang; Yang Liu; Ping Chen; Daguang Li; Haijin Liu; Zhenjun Xiao; Yixun Zheng; Zifeng Lin; Jin Luo; Wenying Lv; Guoguang Liu (Chemical Engineering Journal, 2023)

An antibody cocktail with broadened mutational resistance and effective protection against SARS-CoV-2 - Chunyun Sun; Hang Chi; Fei Yuan; Jing Li; Ji Yang; Aihua Zheng; Fei Wang; Lingling Sun; Yanjing Zhang; Ping Hu; Lihua Jiao; Yongqiang Deng; et al. (Science China Life Sciences, 2023)

Correction to: Gpx4, Selenov, and Txnrd3 Are Three Most Testis-Abundant Selenogenes Resistant to Dietary Selenium Concentrations and Actively Expressed During Reproductive Ages in Rats - Aiping Liu; Fengna Li; Ping Xu; Yanmei Chen; Xiongshun Liang; Shijie Zheng; Huicui Meng; Yumei Zhu; Junluan Mo; Chunmei Gong; Ji-Chang Zhou (Biological Trace Element Research, 2023)

Gpx4, Selenov, and Txnrd3 Are Three Most Testis-Abundant Selenogenes Resistant to Dietary Selenium Concentrations and Actively Expressed During Reproductive Ages in Rats - Aiping Liu; Fengna Li; Ping Xu; Yanmei Chen; Xiongshun Liang; Shijie Zheng; Huicui Meng; Yumei Zhu; Junluan Mo; Chunmei Gong; Ji-Chang Zhou (Biological Trace Element Research, 2023)

Abietane diterpenoids with neuroprotective activities from Phlegmariurus carinatus - Yang Liu; Qiang Wang; Dong-Kun Zheng; De Zhang; Zhen Xie; Jia-Wei Hu; Xin-Hua Xie; Jing Li; Shu-Ping Jiang (Natural Product Research, 2022)

Two new sesquiterpenoid lactone derivatives from Lindera aggregata - Song-Song Wen; Yan Wang; Jia-Ping Xu; Qi Liu; Lei Zhang; Jing Zheng; Lin Li; Na Zhang; Xin Liu; Yu-Wen Xu; Zhen-Liang Sun (Natural Product Research, 2022)

Isolation, identification, and quantification of triterpene saponins in the fresh fruits of Panax notoginseng - Zheng-yi Qu; He-cheng Wang; Yin-ping Jin; Ya-li Li; Ying-ping Wang (Natural Product Research, 2022)

Petrology and geochemistry of the Carboniferous cutinite-rich coals from the Hequ area of Shanxi Province, China - Daofu Song; Tieguan Wang; Ping Li; Jiadong Yan; Xiangji Zheng (Science China Earth Sciences, 2022)

Evaluation of the microwave-assisted organic acid separation of organic sulfur from high-sulfur coal - Jin Liu; Chaoshun Jiang; Hao Shen; Zheng Pang; Zhi Wang; Ping Li; Xing Xing (Clean Technologies and Environmental Policy, 2022)

Monitoring and control methods of harmful algal blooms in Chinese freshwater system: a review - Shengjun Xu; Ping Lyu; Xiaoxu Zheng; Haijun Yang; Bing Xia; Hui Li; Hao Zhang; Shuanglong Ma (Environmental Science and Pollution Research, 2022)

Ginseng volatile oil prolongs the lifespan and healthspan of Caenorhabditis elegans - Lixin Wang; Ping Qiao; Zhuoer Ouyang; Danyang Li; Jingtong Zheng; Guoqiang Wang; Fang Wang (Biogerontology, 2022)

Sphingopyxis yananensis sp. nov., a novel 2-nitropropane degrading bacterium isolated from a microbial fermentation bed substrate - Chao-chao Zheng; Ying-ying Jiang; Tian-fei Yu; Jing Li; Jia-min Ai; Mai-ping Li; Xiao-dong Liu; Zhen-shan Deng (Archives of Microbiology, 2022)

ML323, a USP1 inhibitor triggers cell cycle arrest, apoptosis and autophagy in esophageal squamous cell carcinoma cells - Yaxin Sun; Beibei Sha; Wenjing Huang; Miaomiao Li; Shan Zhao; Yuan Zhang; Jie Yan; Zheng Li; Jingwen Tang; Peiyan Duan; Jianxiang Shi; Pei Li; et al. (Apoptosis, 2022)

Prenatal and postnatal transfer of perfluoroalkyl substances from mothers to their offspring - Yingxue Liu; An Li; Qi An; Kai Liu; Ping Zheng; Shanshan Yin; Weiping Liu (Critical Reviews in Environmental Science and Technology, 2022)

Rhodoflexus caldus gen. nov., sp. nov., a new member of the phylum Bacteroidota isolated from a hot spring sediment - Ze-Tao Liu; Lan Liu; Wen-Dong Xian; Zheng-Han Lian; Jun-Yi Dai; Bao-Zhu Fang; Meng-Meng Li; Ai-Ping Lv; Zhen-Hao Luo; Jian-Yu Jiao; Wen-Jun Li (Antonie van Leeuwenhoek, 2022)

Low-carbon production or not? Co-opetition supply chain manufacturers’ production strategy under carbon cap-and-trade policy - Huiqin Zhang; Yuxiang Zhang; Ping Li; Hong Zheng; Zhigang Li (Environment, Development and Sustainability, 2022)

Discovery of potential anti-SARS-CoV-2 drugs based on large-scale screening in vitro and effect evaluation in vivo - Haoran Peng; Cuiling Ding; Liangliang Jiang; Wanda Tang; Yan Liu; Lanjuan Zhao; Zhigang Yi; Hao Ren; Chong Li; Yanhua He; Xu Zheng; Hailin Tang; et al. (Science China Life Sciences, 2022)

Rapid triage for ischemic stroke: a machine learning-driven approach in the context of predictive, preventive and personalised medicine - Yulu Zheng; Zheng Guo; Yanbo Zhang; Jianjing Shang; Leilei Yu; Ping Fu; Yizhi Liu; Xingang Li; Hao Wang; Ling Ren; Wei Zhang; Haifeng Hou; et al. (EPMA Journal, 2022)
Background Recognising the early signs of ischemic stroke (IS) in emergency settings has been challenging. Machine learning (ML), a robust tool for predictive, preventive and personalised medicine (PPPM/3PM), presents a possible solution for this issue and produces accurate predictions for real-time data processing. Methods This investigation evaluated 4999 IS patients among a total of 10,476 adults included in the initial dataset, and 1076 IS subjects among 3935 participants in the external validation dataset. Six ML-based models for the prediction of IS were trained on the initial dataset of 10,476 participants (split participants into a training set [80%] and an internal validation set [20%]). Selected clinical laboratory features routinely assessed at admission were used to inform the models. Model performance was mainly evaluated by the area under the receiver operating characteristic (AUC) curve. Additional techniques—permutation feature importance (PFI), local interpretable model-agnostic explanations (LIME), and SHapley Additive exPlanations (SHAP)—were applied for explaining the black-box ML models. Results Fifteen routine haematological and biochemical features were selected to establish ML-based models for the prediction of IS. The XGBoost-based model achieved the highest predictive performance, reaching AUCs of 0.91 (0.90–0.92) and 0.92 (0.91–0.93) in the internal and external datasets respectively. PFI globally revealed that demographic feature age, routine haematological parameters, haemoglobin and neutrophil count, and biochemical analytes total protein and high-density lipoprotein cholesterol were more influential on the model’s prediction. LIME and SHAP showed similar local feature attribution explanations. Conclusion In the context of PPPM/3PM, we used the selected predictors obtained from the results of common blood tests to develop and validate ML-based models for the diagnosis of IS. The XGBoost-based model offers the most accurate prediction. By incorporating the individualised patient profile, this prediction tool is simple and quick to administer. This is promising to support subjective decision making in resource-limited settings or primary care, thereby shortening the time window for the treatment, and improving outcomes after IS.

Expanding the clinical spectrum of adult-onset neuronal intranuclear inclusion disease - Yuwen Cao; Jingying Wu; Yunhua Yue; Chao Zhang; Shihua Liu; Ping Zhong; Shige Wang; Xiaojun Huang; Weiping Deng; Jing Pan; Lan Zheng; Qing Liu; et al. (Acta Neurologica Belgica, 2022)

The Effects of Ground and Treadmill Running on Energy Metabolism and Muscle Contractile Properties: A Randomized Cross-Over Study - Yuan Zhou; Jian-gang Chen; Xiao-long Li; Xin-liang Pan; Yi-zheng Zhou; Zheng-ao Li; Zhi-cheng Liang; Jia-min Long; Ming-ze Qin; Jing Zhang; Bing Shi; Bing-jun Wan; et al. (Journal of Science in Sport and Exercise, 2022)
Purpose This study aimed to compare the effects of ground and treadmill running on energy metabolism and muscle contractile properties, providing a basis for the general public to choose running venues. Methods Ten male college students (age, 20.10 ± 1.53 years; height, 176.20 ± 5.49 cm; weight, 72.14 ± 8.25 kg; body fat percent, 12.41% ± 4.65%) were recruited in this study. Energy expenditure (EE) was measured using the accelerometer (GT9X) combined with specific estimation equations. Average heart rate (HR) was measured using a heart rate band (Polar). Muscle contractile properties were assessed by measuring muscle displacement (Dm) and contraction velocity (Vc) using tensiomyography (TMG-S1). Blood glucose (Glu) and lactate (Lac) were measured by portable devices (eB-G and Lactate Scout). The running speed was 9 km/h and the duration was 25 min. Two-way ANOVA (protocol × time) was used to analyze the effect of running protocols on energy metabolism and muscle contractile properties. Results EE of treadmill running was significantly higher than EE of ground running (protocol main effect, P < 0.001), and HR of treadmill running was significantly higher than that of ground running in the first testing time (protocol simple effect, P = 0.026; protocol × time interaction P = 0.043). The decrease in Dm of the rectus femoris after treadmill running was significantly higher than that of ground running (protocol main effect, P = 0.009). The interaction of different running protocols and testing times on Lac was significant ( P = 0.025), but all results of the simple effects analysis were not statistically significant ( P > 0.05). Conclusion Our study found a difference in energy expenditure between treadmill and ground running at 9 km/h with duration of 25 min. In addition, treadmills are more likely to cause a decrease in muscle displacement distance of the rectus femoris measured after exercise than ground running. Future studies are needed to further investigate whether the differences are induced by internal metabolism or the environmental conditions of running.

MiR-1260b protects against LPS-induced degenerative changes in nucleus pulposus cells through targeting TCF7L2 - Shijie Chen; Guixia Shi; Jin Zeng; Ping Huang Li; Yi Peng; Zhiyu Ding; Hong Qing Cao; Ruping Zheng; Weiguo Wang (Human Cell, 2022)

Genome-based reclassification of the genus Meiothermus along with the proposal of a new genus Allomeiothermus gen. nov - Jian-Yu Jiao; Zheng-Han Lian; Ze-Tao Liu; Lan Liu; Meng-Meng Li; Ai-Ping Lv; Wen-Dong Xian; Ting Zhou; Zhitang Lyu; Nimaichand Salam; Wen-Jun Li (Antonie van Leeuwenhoek, 2022)

Dynamics of nitrogen and phosphorus profile and its driving forces in a subtropical deep reservoir - Cunli Li; Ping Zhang; Guangwei Zhu; Chao Chen; Yucheng Wang; Mengyuan Zhu; Hai Xu; Cuiling Jiang; Wei Zou; Pengcheng Shi; Qing Zheng (Environmental Science and Pollution Research, 2022)

The Predictability of Ocean Environments that Contributed to the 2020/21 Extreme Cold Events in China: 2020/21 La Niña and 2020 Arctic Sea Ice Loss - Fei Zheng; Ji-Ping Liu; Xiang-Hui Fang; Mi-Rong Song; Chao-Yuan Yang; Yuan Yuan; Ke-Xin Li; Ji Wang; Jiang Zhu (Advances in Atmospheric Sciences, 2022)
Several consecutive extreme cold events impacted China during the first half of winter 2020/21, breaking the low-temperature records in many cities. How to make accurate climate predictions of extreme cold events is still an urgent issue. The synergistic effect of the warm Arctic and cold tropical Pacific has been demonstrated to intensify the intrusions of cold air from polar regions into middle-high latitudes, further influencing the cold conditions in China. However, climate models failed to predict these two ocean environments at expected lead times. Most seasonal climate forecasts only predicted the 2020/21 La Niña after the signal had already become apparent and significantly underestimated the observed Arctic sea ice loss in autumn 2020 with a 1–2 month advancement. In this work, the corresponding physical factors that may help improve the accuracy of seasonal climate predictions are further explored. For the 2020/21 La Niña prediction, through sensitivity experiments involving different atmospheric–oceanic initial conditions, the predominant southeasterly wind anomalies over the equatorial Pacific in spring of 2020 are diagnosed to play an irreplaceable role in triggering this cold event. A reasonable inclusion of atmospheric surface winds into the initialization will help the model predict La Niña development from the early spring of 2020. For predicting the Arctic sea ice loss in autumn 2020, an anomalously cyclonic circulation from the central Arctic Ocean predicted by the model, which swept abnormally hot air over Siberia into the Arctic Ocean, is recognized as an important contributor to successfully predicting the minimum Arctic sea ice extent.

Transcriptomic analyses reveal the effect of nitric oxide on the lateral root development and growth of mangrove plant Kandelia obovata - Ming-Yue Wei; Huan Li; You-Hui Zhong; Zhi-Jun Shen; Dong-Na Ma; Chang-Hao Gao; Yi-Ling Liu; Wen-Hua Wang; Jing-Ya Zhang; Yan-Ping You; Hai-Lei Zheng (Plant and Soil, 2022)

LncRNA NEAT1 ameliorate ischemic stroke via promoting Mfn2 expression through binding to Nova and activates Sirt3 - Zhi-Wen Zhou; Xiang Ren; Li-Jun Zheng; Ai-Ping Li; Wen-Sheng Zhou (Metabolic Brain Disease, 2022)

Mitogenomes provide new insights into the evolutionary history of Prodiamesinae (Diptera: Chironomidae) - Xiao‐Long Lin; Yan‐Min Zhao; Li‐Ping Yan; Wen‐Bin Liu; Wen‐Jun Bu; Xin‐Hua Wang; Chen‐Guang Zheng (Zoologica Scripta, 2022)
Evolutionary analysis of Prodiamesinae has long been impeded by lack of information, and its phylogenetic relationship with Orthocladiinae remains questionable. Here, ten complete mitochondrial genomes (mitogenomes) of Orthocladiinae sensu lato were newly sequenced, including three Prodiamesinae species and seven Orthocladiinae species. Coupled with published mitogenomes, a total of 12 mitogenomes of Orthocladiinae sensu lato were selected for a comparative mitogenomic analysis and phylogenetic reconstruction. Mitogenomes of Orthocladiinae sensu lato are conserved in structure, and all genes arrange the same gene order as the ancestral insect mitogenome. Nucleotide composition is highly biased, and the control region displayed the highest A + T content. All protein‐coding genes are under purifying selection, and the ATP8 evolves at the fastest rate. In addition, the mitogenomes of Orthocladiinae sensu lato are highly conserved, and they are practically useful for phylogenetic inference, suggesting a re‐classification of Orthocladiinae by sinking Prodiamesinae as a subgroup of Orthocladiinae.

Homeostasis Regulation by Potassium Channel Subfamily K Member 3 (KCNK3) in Various Fishes - Zheng-Yong Wen; Chuan-Jie Qin; Yun-Yun Lv; Yan-Ping Li; Yuan-Chao Zou; Sheng-Tao Guo; Qiong Shi (Frontiers in Marine Science, 2021)
Potassium channels are important for K + transport and cell volume regulation, which play important roles in many biological processes such as hormone secretion, ion homeostasis, excitability, and cell development. In mammals, a total of 15 potassium channels were identified and they were divided into six subfamilies, including TALK (TALK1, TALK2, TASK2), TASK (TASK1, TASK3, TASK5), TREK (TREK1, TREK2, TRAAK), TWIK (TWIK1, TWIK2, KCNK7), THIK (THIK1, THIK2) and TRESK. TASK1, also known as potassium channel subfamily k member 3 (KCNK3), is the first member identified in the TASK subfamily. This K 2 P channel has potential applications in fish breeding and aquaculture industry due to its important roles in various physiological processes. Despite its functional role has been well studied in mammals; however, it is less known in fishes. In this review, we systematically summarize recent research advances of this critical potassium channel in representative fishes, such as gene number variation, tissue distribution, phylogeny, and potential homeostasis regulation role. This paper provides novel insights into the functional properties of these fish kcnk3 genes (including osmoregulation, energy homeostasis maintenance and fatty acids metabolism regulation), and also expands our knowledge about their variations among diverse fishes.

Nanometer effect promoting arsenic removal on α-MnO2 nano-surface in aqueous solution: DFT+U research - Guifa Li; Pengsen Zhao; Haizhong Zheng; Lixia Yang; Yongxiang Geng; Ping Peng (Environmental Science and Pollution Research, 2021)

Nitrogen contaminants damage on intestinal epithelial tight junctions: a review - Guo-ping Zhao; Jin-wang Li; Fang-wei Yang; Xiao-yu Wang; Fa-zheng Ren; Guo-fang Pang; Yi-xuan Li (Environmental Chemistry Letters, 2021)

Discovery of structural deletions in breast cancer predisposition genes using whole genome sequencing data from > 2000 women of African-ancestry - Zhishan Chen; Xingyi Guo; Jirong Long; Jie Ping; Bingshan Li; Mary Kay Fadden; Thomas U. Ahearn; Daniel O. Stram; Xiao-Ou Shu; Guochong Jia; Jonine Figueroa; Robertson Adjei; et al. (Human Genetics, 2021)

Resource utilization of organic spent adsorbent to prepare three-dimensional sulfate-functionalized layered double oxide for superior removal of azo dye - Lingjie Zhang; Siyin Zheng; Peng Li; Zhongbang Zhu; Youqin Zou; Ping Zhang (Environmental Science and Pollution Research, 2021)

Stable isotopes (δ2H) in feathers identify non-breeding origins of the endangered Jankowski’s Bunting - Zheng Han; Hai-Tao Wang; Kevin J. Kardynal; Keith A. Hobson; Wei-Ping Shang; li-shi Zhang; Yun-lei Jiang; Frédéric Jiguet (Journal of Ornithology, 2021)

Terpenoids from the South China Sea soft coral Sinularia multiflora - Zheng Wang; Ping-Lin Li; Xiang-Chao Luo; Qi Wang; Leen van Ofwegen; Xu-Li Tang; Guo-Qiang Li (Natural Product Research, 2021)

Risk factors for sleep disorders in patients undergoing peritoneal dialysis - Gui-Ling Liu; Qiu-Nan Zhan; You-Lu Zhao; Zu-Ying Xiong; Jin-Lan Liao; Ye-Ping Ren; Qin Wang; Li-Ping Duan; Zhao-Xia Zheng; Li Hao; Jie Dong (Sleep and Biological Rhythms, 2021)
Sleep disorders in patients with end-stage renal disease are common but have rarely been reported in previous studies. Therefore, we examined the prevalence of sleep disorders and the risk factors for declining sleep quality in patients undergoing peritoneal dialysis (PD). A multicenter prospective cohort study was conducted at five PD centers across different provinces in China. A total of 449 patients who underwent PD between March to November 2013 were enrolled. Demographic data, laboratory indicators, presence of depression, and sleep assessment data were collected. Sleep questionnaires reflecting five categories of sleep disorders, namely, insomnia, restless legs syndrome, excessive daytime sleepiness, possible narcolepsy, and sleepwalking and nightmares, were administered at baseline and at 24 months postoperatively. Sleep disorders were diagnosed when a patient had at least one sleep problem. At baseline, 335 (74.6%) patients had at least one type of sleep disorder. Depression, diabetes mellitus (DM), and male were found to be associated with the presence of a sleep disorder. At follow-up, the prevalence of insomnia, restless legs syndrome, and excessive daytime sleepiness had significantly increased in 285 patients. Furthermore, cardiovascular disease (CVD) was found to be associated with the presence of sleep disorders in patients with one or more disorders at baseline, whereas a low serum albumin level was found to be associated with sleep disorders in patients without any sleep disorders at baseline. The prevalence of sleep disorders was relatively high among PD patients at baseline and increased afterthe2-year follow-up. Depression, DM, and male were associated with all sleep disorders at baseline. CVD was associated with the presence of a sleep disorder at baseline and worse sleep quality at the 2-year follow-up; whereas a low serum albumin level was associated with the risk of acquiring a sleep disorder at the 2-year follow-up among patients with normal sleep status at baseline.

Long non-coding RNA TPT1-AS1 sensitizes breast cancer cell to paclitaxel and inhibits cell proliferation by miR-3156-5p/caspase 2 axis - Yuan Huang; Yabing Zheng; Xiying Shao; Lei Shi; Guangliang Li; Ping Huang (Human Cell, 2021)

Research on displacement prediction of step-type landslide under the influence of various environmental factors based on intelligent WCA-ELM in the Three Gorges Reservoir area - Yong-gang Zhang; Xin-quan Chen; Rao-ping Liao; Jun-li Wan; Zheng-ying He; Zi-xin Zhao; Yan Zhang; Zheng-yang Su (Natural Hazards, 2021)

LAI scale effect research based on compact airborne spectrographic imager data in the Heihe Oasis - Xiao-ai Dai; Chao Liu; Nai-wen Li; Mei-lian Wang; Yu-wei Yang; Xing-ping Yang; Shi-qi Zhang; Xu-wei He; Zheng-li Yang; Heng Lu; Jing-zhong Li; Ze-kun Wang (Journal of Mountain Science, 2021)

Correction to: Exploring the Genetic Association of the ABAT Gene with Alzheimer’s Disease - Quanzhen Zheng; Rui Bi; Min Xu; Deng-Feng Zhang; Li-Wen Tan; Ya-Ping Lu; Yong-Gang Yao (Molecular Neurobiology, 2021)

Exploring the Genetic Association of the ABAT Gene with Alzheimer’s Disease - Quanzhen Zheng; Rui Bi; Min Xu; Deng-Feng Zhang; Li-Wen Tan; Ya-Ping Lu; Yong-Gang Yao (Molecular Neurobiology, 2021)

RETRACTED ARTICLE: An energy and time prediction model for remanufacturing process using graphical evaluation and review technique (GERT) with multivariant uncertainties - Jiali Zhao; Zheng Xue; Tao Li; Jinfeng Ping; Shitong Peng (Environmental Science and Pollution Research, 2021)

Subcellular Localization of the D27 Protein in Sugarcane (Saccharum spp. Hybrids) Using an Optimized Protoplast Isolation, Purification, and Transient Gene Expression Protocol - Zhuan-di Wu; Xin Hu; Feng-gang Zan; Yong-bao Pan; David M. Burner; Zheng-ying Luo; Jia-yong Liu; Li-ping Zhao; Li Yao; Yong Zhao; Xin-long Liu; Hong-ming Xia; et al. (Sugar Tech, 2021)

Human β-Defensin 118 Attenuates Escherichia coli K88–Induced Inflammation and Intestinal Injury in Mice - Qian Lin; Qingqing Fu; Xiang Li; Yuheng Luo; Junqiu Luo; Daiwen Chen; Xiangbing Mao; Bing Yu; Ping Zheng; Zhiqing Huang; Jie Yu; Hui Yan; et al. (Probiotics and Antimicrobial Proteins, 2021)

Enrichment and characterization of an effective hexavalent chromium-reducing microbial community YEM001 - Yucai Lyu; Tao Yang; Herong Liu; Zheng Qi; Ping Li; Ziyao Shi; Zhen Xiang; Dachun Gong; Ning Li; Yaoping Zhang (Environmental Science and Pollution Research, 2021)

Genome-Wide Identification of Copper Stress-Regulated and Novel MicroRNAs in Mulberry Leaf - Qiuxia Du; Peng Guo; Yisu Shi; Jian Zhang; Danyan Zheng; Yang Li; Adolf Acheampong; Ping Wu; Qiang Lin; Weiguo Zhao (Biochemical Genetics, 2021)

Retraction Note to: Resibufogenin suppresses tumor growth and inhibits glycolysis in ovarian cancer by modulating PIM1 - Qian Li; Chuanwu Jiang; Yan Wang; Minghua Wei; Huijin Zheng; Yanqi Xu; Xuegang Xu; Fengyu Jia; Kai Liu; Gang Sun; Jianhua Zang; Ping Mo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Tyrosine kinase Fyn promotes apoptosis after intracerebral hemorrhage in rats by activating Drp1 signaling - Li Zhang; Lu Wang; Han Xiao; Hui Gan; Hui Chen; Shuyue Zheng; Dan Jian; Xuan Zhai; Ning Jiang; Zhao Jing; Ping Liang (Journal of Molecular Medicine, 2021)

Identification of Colletotrichum brevisporum causing fruit rot in yellow passion fruit (Passiflora edulis f. flavicarpa) in China - Fang Qiu; Xi Li; Chang Ping Xie; Jing Li; Fei Qing Zheng (Australasian Plant Pathology, 2021)

The MYB transcription factor Baymax1 plays a critical role in rice male fertility - Xiao-Jiao Xiang; Lian-Ping Sun; Ping Yu; Zheng-Fu Yang; Pei-Pei Zhang; Ying-Xin Zhang; Wei-Xun Wu; Dai-Bo Chen; Xiao-Deng Zhan; Riaz-Muhammad Khan; Adil Abbas; Shi-Hua Cheng; et al. (Theoretical and Applied Genetics, 2021)

Comparative proteomics reveals new insights into the endosperm responses to drought, salinity and submergence in germinating wheat seeds - Mingke Yan; Lu Zheng; Bingjuan Li; Renfang Shen; Ping Lan (Plant Molecular Biology, 2021)

Improved control of Frankliniella occidentalis on greenhouse pepper through the integration of Orius sauteri and neonicotinoid insecticides - Qing-cai Lin; Hao Chen; Dirk Babendreier; Jin-ping Zhang; Feng Zhang; Xiao-yan Dai; Zuo-wen Sun; Zhao-peng Shi; Xiao-lin Dong; Guang-an Wu; Yi Yu; Li Zheng; et al. (Journal of Pest Science, 2021)

The gut bacterial flora associated with brown planthopper is affected by host rice varieties - Zheng-Liang Wang; Hai-bo Pan; Wei Wu; Mu-Yu Li; Xiao-Ping Yu (Archives of Microbiology, 2021)

Dietary lipid concentrations influence growth, body composition, morphology of the liver and mid-intestine, and antioxidant status of marbled eel (Anguilla marmorata) - Shi-Jun Chen; Peng Liu; You-Ming Jia; Hong-Ping Liao; Shao-Xuan Zhu; Li-Liu Zhou; Xue-Ming Dan; Li Liu; Jia-Hao Li; Su-Bi Zheng; Jun-Jiang Yang; Lian Gan (Aquaculture International, 2020)

A near-infrared spectroscopy-based end-point determination method for the blending process of Dahuang soda tablets - Si-jun Wu; Ping Qiu; Pian Li; Zheng Li; Wen-long Li (Journal of Zhejiang University-SCIENCE B, 2020)

Population pharmacokinetics and dose optimization of ceftriaxone for children with community-acquired pneumonia - Muhammad Wasim Khan; Ya-Kun Wang; Yue-E Wu; Bo-Hao Tang; Min Kan; Hai-Yan Shi; Yi Zheng; Bao-Ping Xu; A-Dong Shen; Evelyne Jacqz-Aigrain; Li-Yuan Tian; Wei Zhao (European Journal of Clinical Pharmacology, 2020)

Comparative iTRAQ Proteomics Reveals Multiple Effects of Selenium Yeast on Dairy Cows in Parturition - Zhi-hua Ren; Li-peng Bai; Liu-hong Shen; Zheng-zhong Luo; Zi-han Zhou; Zhi-cai Zuo; Xiao-ping Ma; Jun-liang Deng; Ya Wang; Sheng-yu Xu; Yu-heng Luo; Sui-zhong Cao; et al. (Biological Trace Element Research, 2020)

Prenylated isoflavones with potential antiproliferative activities from Mappianthus iodoides - Yan-Ping Liu; Li-Li Sun; Xiang-Lin Zhang; Hai-Yuan Niu; Zheng-Hong Pan; Yan-Hui Fu (Natural Product Research, 2020)

Comparative analysis and natural evolution of squalene epoxidase in three Fritillaria species - Xu Lu; Lin-Ning Zhang; Jin-Fa Du; Xiao-Yan Zheng; Hui-Jun Li; Ping Li; Gui-Zhong Xin; Yan Jiang (Plant Molecular Biology, 2020)

Comparison of the movement and vertical structures of two types of the southwest vortex - Ping Lu; Weipeng Zheng; Yueqing Li (Meteorology and Atmospheric Physics, 2020)

A family cluster of severe acute respiratory syndrome coronavirus 2 infections - Xuesong Gao; Zheng Yuan; Di Yang; Hongjie Li; Yijin Zhang; Ping Gao; Xiaomin Liu; Wenshan Zhao; Te Xiao; Xuefei Duan (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Gametogenesis and reproductive traits of the cold-seep mussel Gigantidas platifrons in the South China Sea - Zhaoshan Zhong; Minxiao Wang; Hao Chen; Ping Zheng; Chaolun Li (Journal of Oceanology and Limnology, 2020)

Effects of High-Fat Diet on Steatosis, Endoplasmic Reticulum Stress and Autophagy in Liver of Tilapia (Oreochromis niloticus) - Rui Jia; Li-Ping Cao; Jin-Liang Du; Qin He; Zheng-Yan Gu; Galina Jeney; Pao Xu; Guo-Jun Yin (Frontiers in Marine Science, 2020)

Detection of serum IgM and IgG for COVID-19 diagnosis - Ling Zhong; Junlan Chuan; Bo Gong; Ping Shuai; Yu Zhou; Yi Zhang; Zhilin Jiang; Dingding Zhang; Xiaoqi Liu; Shi Ma; Yi Huang; He Lin; et al. (Science China Life Sciences, 2020)

Predicting plant–soil N cycling and soil N2O emissions in a Chinese old-growth temperate forest under global changes: uncertainty and implications - Weiwei Dai; Edith Bai; Wei Li; Ping Jiang; Guanhua Dai; Xingbo Zheng (Soil Ecology Letters, 2020)

Molecular detection and identification of Brassica juncea phyllody and witches’ broom-associated phytoplasmas of group 16SrVI-A in Inner Mongolia, China - Lei Zhang; Pei-Ling Song; Ping-Ping Sun; Wen-Jun Zhao; Zi-Qin Li; Zheng-Nan Li (European Journal of Plant Pathology, 2020)

Impact of urbanization factors on mortality due to unintentional injuries using panel data regression model and spatial-temporal analysis - Haixia Pu; Bin Li; Dongqi Luo; Shaobin Wang; Zhaolin Wang; Wei Zhao; Lingyu Zheng; Ping Duan (Environmental Science and Pollution Research, 2020)

RETRACTED ARTICLE: Resibufogenin suppresses tumor growth and inhibits glycolysis in ovarian cancer by modulating PIM1 - Qian Li; Chuanwu Jiang; Yan Wang; Minghua Wei; Huijin Zheng; Yanqi Xu; Xuegang Xu; Fengyu Jia; Kai Liu; Gang Sun; Jianhua Zang; Ping Mo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

A challenge in anaerobic digestion of swine wastewater: recalcitrance and enhanced-degradation of dietary fibres - Zhuo Zeng; Ping Zheng; Cheng Shi; Meng Zhang; Yiyu Li; Wudi Zhang; Shengdao Shan (Biodegradation, 2019)

Combined gastroscopic and choledochoscopic transabdominal nasobiliary drainage - Song-mei Lou; Min Zhang; Zheng-rong Wu; Gui-xing Jiang; Hua Shen; Yi Dai; Yue-long Liang; Li-ping Cao; Guo-ping Ding (Journal of Zhejiang University-SCIENCE B, 2019)

Complete genome sequences of five prunus necrotic ringspot virus isolates from Inner Mongolia of China and comparison to other PNRSV isolates around the world - Shuang Song; Ping-ping Sun; Ya-han Chen; Qiang Ma; Xiao-yun Wang; Ming-min Zhao; Zheng-nan Li (Journal of Plant Pathology, 2019)

Two novel alkaliphiles, Bacillus alkalisoli sp. nov., and Bacillus solitudinis sp. nov., isolated from saline-alkali soil - Guo-Hong Liu; Manik Prabhu Narsing Rao; Zhou-Yan Dong; Jie-Ping Wang; Zheng Chen; Bo Liu; Wen-Jun Li (Extremophiles, 2019)

Serratia microhaemolytica sp. nov., isolated from an artificial lake in Southern China - Juan Wang; Min-Ling Zheng; Jian-Yu Jiao; Wei-Jia Wang; Shuai Li; Min Xiao; Cha Chen; Ping-Hua Qu; Wen-Jun Li (Antonie van Leeuwenhoek, 2019)

Exotic Spartina alterniflora invasion alters soil nitrous oxide emission dynamics in a coastal wetland of China - Dengzhou Gao; Lijun Hou; Xiaofei Li; Min Liu; Yanling Zheng; Guoyu Yin; Yi Yang; Cheng Liu; Ping Han (Plant and Soil, 2019)

Molecular detection and identification of phytoplasmas in a novel 16SrI subgroup in sunflowers and cocklebur weeds - Lei Zhang; Ping-ping Sun; Qiang Ma; Xiao-zhao Xu; Hong-you Zhou; Zheng-nan Li (Journal of Plant Pathology, 2019)

Paternal effects on fatty acid composition of tree peony seed oil - Qing Hao; Li-Ping Peng; Zhen Li; Si-Qi Men; Ning-Ning Tong; Qing-Yan Shu; Zheng-An Liu (Euphytica, 2019)

The Tibetan Plateau Surface-Atmosphere Coupling System and Its Weather and Climate Effects: The Third Tibetan Plateau Atmospheric Science Experiment - Ping Zhao; Yueqing Li; Xueliang Guo; Xiangde Xu; Yimin Liu; Shihao Tang; Wenming Xiao; Chunxiang Shi; Yaoming Ma; Xing Yu; Huizhi Liu; La Jia; et al. (Journal of Meteorological Research, 2019)

Pseudofrancisella aestuarii gen. nov., sp. nov., a novel member of the family Francisellaceae isolated from estuarine seawater - Min-Ling Zheng; Jian-Yu Jiao; Lei Dong; Ming-Xian Han; Liang-Hui Li; Min Xiao; Cha Chen; Ping-Hua Qu; Wen-Jun Li (Antonie van Leeuwenhoek, 2019)

Expression of the intrarenal angiotensin receptor and the role of renin-angiotensin system inhibitors in IgA nephropathy - Zheng Zhang; Shi-min Jiang; Ye-ping Ma; Pei-lin Dai; Yi-ning Wang; Gu-ming Zou; Hong-mei Gao; Yue Yang; Wen-ge Li (Molecular and Cellular Biochemistry, 2019)

Effect of Chronic Exposure to Methomyl on Tissue Damage and Apoptosis in Testis of Tilapia (Oreochromis niloticus) and Recovery Pattern - Shun Long Meng; Tao Liu; Xi Chen; Li Ping Qiu; Geng Dong Hu; Chao Song; LiMin Fan; Yao Zheng; Jia Zhang Chen; Pao Xu (Bulletin of Environmental Contamination and Toxicology, 2019)

Synthesis and biological evaluation of novel SIPI-7623 derivatives as farnesoid X receptor (FXR) antagonists - Si-Yun Nian; Guo-Ping Wang; Zheng-Li Jiang; Ying Xiao; Mo-Han Huang; Yi-Huan Zhou; Xiang-Duan Tan (Molecular Diversity, 2019)

Daedaleanols A and B, two new sesquiterpenes from cultures of the basidiomycete Daedalea incana - Ying Huang; Shuai-Bing Zhang; He-Ping Chen; Zhen-Zhu Zhao; Zheng-Hui Li; Tao Feng; Ji-Kai Liu (Natural Product Research, 2019)

Macrolide sesquiterpene pyridine alkaloids from the stems of Tripterygium regelii - Dongsheng Fan; Ting Li; Zhiyuan Zheng; Guo-Yuan Zhu; Xiaojun Yao; Zhi-Hong Jiang; Li-Ping Bai (Journal of Natural Medicines, 2019)

Laminar Distribution of Neurochemically-Identified Interneurons and Cellular Co-expression of Molecular Markers in Epileptic Human Cortex - Qiyu Zhu; Wei Ke; Quansheng He; Xiongfei Wang; Rui Zheng; Tianfu Li; Guoming Luan; Yue-Sheng Long; Wei-Ping Liao; Yousheng Shu (Neuroscience Bulletin, 2018)

Lycium barbarum polysaccharide attenuates diabetic testicular dysfunction via inhibition of the PI3K/Akt pathway-mediated abnormal autophagy in male mice - Guang-Jiang Shi; Jie Zheng; Xiao-Xu Han; Ya-Ping Jiang; Zhi-Mei Li; Jing Wu; Qing Chang; Yang Niu; Tao Sun; Yu-Xiang Li; Zhen Chen; Jian-Qiang Yu (Cell and Tissue Research, 2018)

A new12-membered lactone from the stems of Ficus auriculata - Tai-Ming Shao; Cai-Juan Zheng; Xiao-Bao Li; Guang-Ying Chen; Xiao-Ping Song; Chang-Ri Han (Natural Product Research, 2018)

Comparison of gene co-networks reveals the molecular mechanisms of the rice (Oryza sativa L.) response to Rhizoctonia solani AG1 IA infection - Jinfeng Zhang; Wenjuan Zhao; Rong Fu; Chenglin Fu; Lingxia Wang; Huainian Liu; Shuangcheng Li; Qiming Deng; Shiquan Wang; Jun Zhu; Yueyang Liang; Ping Li; et al. (Functional & Integrative Genomics, 2018)

Repaglinide-irbesartan drug interaction: effects of SLCO1B1 polymorphism on repaglinide pharmacokinetics and pharmacodynamics in Chinese population - Qi Pei; Jun-Yan Liu; Ji-Ye Yin; Guo-Ping Yang; Shi-Kun Liu; Yi Zheng; Pan Xie; Cheng-Xian Guo; Mi Luo; Hong-Hao Zhou; Xi Li; Zhao-Qian Liu (European Journal of Clinical Pharmacology, 2018)

Species composition, functional and phylogenetic distances correlate with success of invasive Chromolaena odorata in an experimental test - Yu‐Long Zheng; Jean H. Burns; Zhi‐Yong Liao; Yang‐ping Li; Jie Yang; Ya‐jun Chen; Jiao‐lin Zhang; Yu‐guo Zheng (Ecology Letters, 2018)
Biotic resistance may influence invasion success; however, the relative roles of species richness, functional or phylogenetic distance in predicting invasion success are not fully understood. We used biomass fraction of Chromolaena odorata , an invasive species in tropical and subtropical areas, as a measure of ‘invasion success’ in a series of artificial communities varying in species richness. Communities were constructed using species from Mexico (native range) or China (non‐native range). We found strong evidence of biotic resistance: species richness and community biomass were negatively related with invasion success; invader biomass was greater in plant communities from China than from Mexico. Harvesting time had a greater effect on invasion success in plant communities from China than on those from Mexico. Functional and phylogenetic distances both correlated with invasion success and more functionally distant communities were more easily invaded. The effects of plant‐soil fungi and plant allelochemical interactions on invasion success were species‐specific.

Altered Profiles of Gut Microbiota in Klebsiella pneumoniae-Induced Pyogenic Liver Abscess - Nan Chen; Zong-Xin Ling; Tong-Tong Jin; Ming Li; Sheng Zhao; Li-Shuang Zheng; Xin Xi; Lin-Lin Wang; Ying-Ying Chen; Yue-Liang Shen; Li-Ping Zhang; Shao-cong Sun (Current Microbiology, 2018)

Risk factors, outcomes and genotypes of carbapenem-nonsusceptible Klebsiella pneumoniae bloodstream infection: a three-year retrospective study in a large tertiary hospital in Northern China - Si-Han Zheng; Sheng-Ji Cao; Hui Xu; Dan Feng; Li-Ping Wan; Guang-Jie Wang; Xiao-Guang Xiao (Infectious Diseases, 2018)

OsPKS2 is required for rice male fertility by participating in pollen wall formation - Ting Zou; Mingxing Liu; Qiao Xiao; Tao Wang; Dan Chen; Tao Luo; Guoqiang Yuan; Qiao Li; Jun Zhu; Yueyang Liang; Qiming Deng; Shiquan Wang; et al. (Plant Cell Reports, 2018)

Network analysis of microRNAs, transcription factors, and target genes involved in axon regeneration - Li-ning Su; Xiao-qing Song; Zhan-xia Xue; Chen-qing Zheng; Hai-feng Yin; Hui-ping Wei (Journal of Zhejiang University-SCIENCE B, 2018)

Physical and chemical characteristics of PM2.5 and its toxicity to human bronchial cells BEAS-2B in the winter and summer - Hui-hui Zhang; Zheng Li; Yu Liu; Ping Xinag; Xin-yi Cui; Hui Ye; Bao-lan Hu; Li-ping Lou (Journal of Zhejiang University-SCIENCE B, 2018)

Enhancement of the thermal and alkaline pH stability of Escherichia coli lysine decarboxylase for efficient cadaverine production - Fengyu Kou; Jing Zhao; Jiao Liu; Cunmin Sun; Yanmei Guo; Zijian Tan; Feng Cheng; Zhimin Li; Ping Zheng; Jibin Sun (Biotechnology Letters, 2018)

A study of variation characteristics of Gobi broadband emissivity based on field observational experiments in northwestern China - Zhi-yuan Zheng; Zhi-gang Wei; Zhi-ping Wen; Wen-jie Dong; Zhen-chao Li; Xiao-hang Wen; Xian Zhu; Chen Chen; Shan-shan Hu (Theoretical and Applied Climatology, 2018)

The Role of HINT1 in Methamphetamine-Induced Conditioned Place Preference - Ju-ping Li; Peng Liu; Gang Lei; Zheng Chu; Fei Liu; Chao-feng Shi; Yong-hui Dang; Teng Chen (Neurotoxicity Research, 2018)

Epidemiology and clinical characteristics of human coronaviruses OC43, 229E, NL63, and HKU1: a study of hospitalized children with acute respiratory tract infection in Guangzhou, China - Zhi-Qi Zeng; De-Hui Chen; Wei-Ping Tan; Shu-Yan Qiu; Duo Xu; Huan-Xi Liang; Mei-Xin Chen; Xiao Li; Zheng-Shi Lin; Wen-Kuan Liu; Rong Zhou (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

ALDH2 genes are negatively correlated with natural deastringency in Chinese PCNA persimmon (Diospyros kaki Thunb.) - Jun-Chi Xu; Jin-Ge Ding; Jian-Ping Gan; Rong-Li Mo; Li-Qing Xu; Qing-Lin Zhang; Zheng-Rong Luo (Tree Genetics & Genomes, 2017)

Cross-neutralization of SARS coronavirus-specific antibodies against bat SARS-like coronaviruses - Lei-Ping Zeng; Xing-Yi Ge; Cheng Peng; Wanbo Tai; Shibo Jiang; Lanying Du; Zheng-Li Shi (Science China Life Sciences, 2017)

RNA-seq analysis provides insight into reprogramming of culm development in Zizania latifolia induced by Ustilago esculenta - Zhi-Dan Wang; Ning Yan; Zheng-Hong Wang; Xiao-Huan Zhang; Jing-Ze Zhang; Hui-Min Xue; Li-Xia Wang; Qi Zhan; Ying-Ping Xu; De-Ping Guo (Plant Molecular Biology, 2017)

TQ-B3203, a potent proliferation inhibitor derived from camptothecin - Xiquan Zhang; Meng Cao; Jing Xing; Fei Liu; Ping Dong; Xin Tian; Hongjiang Xu; Laifang Zhang; Hongmei Gu; Ling Yang; Rui Li; Ming Zheng; et al. (Medicinal Chemistry Research, 2017)

QTL mapping of agronomically important traits in sorghum (Sorghum bicolor L.) - Chunming Bai; Chunyu Wang; Ping Wang; Zhenxing Zhu; Ling Cong; Dan Li; Yifei Liu; Wenjing Zheng; Xiaochun Lu (Euphytica, 2017)

Age, nature, and origin of early cretaceous plutons in the Dabie Mo Mineralization belt: the Xinxian example - Qing-quan Liu; Yu Zhang; Yong-jun Shao; Ke-Ping Zhou; Yong-feng Li; Zheng-zhuan Luo (International Geology Review, 2017)

Insights into deep‐sea adaptations and host–symbiont interactions: A comparative transcriptome study on Bathymodiolus mussels and their coastal relatives - Ping Zheng; Minxiao Wang; Chaolun Li; Xiaoqing Sun; Xiaocheng Wang; Yan Sun; Song Sun (Molecular Ecology, 2017)
Mussels (Bivalve: Mytilidae) have adapted to various habitats, from fresh water to the deep sea. To understand their adaptive characteristics in different habitats, particularly in the bathymodiolin mussels in deep‐sea chemosynthetic ecosystems, we conducted a comparative transcriptomic analysis between deep‐sea bathymodiolin mussels and their shallow‐water relatives. A number of gene families related to stress responses were shared across all mussels, without specific or significantly expanded families in deep‐sea species, indicating that all mussels are capable of adapting to diverse harsh environments, but that different members of the same gene family may be preferentially utilized by different species. One of the most extraordinary trait of bathymodiolin mussels is their endosymbiosis. Lineage‐specific and positively selected TLRs and highly expressed C1QDC proteins were identified in the gills of the bathymodiolins, suggesting their possible functions in symbiont recognition. However, pattern recognition receptors of the bathymodiolins were globally reduced, facilitating the invasion and maintenance of the symbionts obtained by either endocytosis or phagocytosis. Additionally, various transporters were positively selected or more highly expressed in the deep‐sea mussels, indicating a means by which necessary materials could be provided for the symbionts. Key genes supporting lysosomal activity were also positively selected or more highly expressed in the deep‐sea mussels, suggesting that nutrition fixed by the symbionts can be absorbed in a “farming” way wherein the symbionts are digested by lysosomes. Regulation of key physiological processes including lysosome activity, apoptosis and immune reactions is needed to maintain a stable host–symbiont relationship, but the mechanisms are still unclear.

The ArfGAP protein MoGlo3 regulates the development and pathogenicity of Magnaporthe oryzae - Shengpei Zhang; Xiu Liu; Lianwei Li; Rui Yu; Jialiang He; Haifeng Zhang; Xiaobo Zheng; Ping Wang; Zhengguang Zhang (Environmental Microbiology, 2017)
Summary The ADP ribosylation factor (Arf) and the coat protein complex I (COPI) are involved in vesicle transport. Together with GTPase‐activating proteins (ArfGAPs) and guanine exchange factors (ArfGEFs) that regulate the activity of Arf, they govern vesicle formation, COPI trafficking and the maintenance of the Golgi complex. In an ongoing effort to study the role of membrane trafficking in pathogenesis of the rice blast fungus Magnaporthe oryzae , we identified MoGlo3 as an ArfGAP protein that is homologous to Glo3p of the budding yeast Saccharomyces cerevisiae . As suspected, MoGlo3 partially complements the function of yeast Glo3p. Consistent with findings in S. cerevisiae , MoGlo3 is localized to the Golgi, and that the localization is dependent on the conserved BoCCS domain. We found that MoGlo3 is highly expressed during conidiation and early infection stages and is required for vegetative growth, conidial production and sexual development. We further found that the Δ Moglo3 mutant is defective in endocytosis, scavenging of the reactive oxygen species, and in the response to endoplasmic reticulum (ER) stress. The combined effects result in failed appressorium function and decreased pathogenicity. Moreover, we provided evidence showing that the domains including the GAP, BoCCS and GRM are all important for normal MoGlo3 functions. Our studies further illustrate the importance of normal membrane trafficking in the physiology and pathogenicity of the rice blast fungus.

Kinetics of Antioxidant-Producing Maillard Reaction in the Mixture of Ribose and Sea Cucumber ( Stichopus japonicus ) Gut Hydrolysates - Jia-Run Han; Zhi-Mo Zhu; Hai-Tao Wu; Na Sun; Yue Tang; Cui-Ping Yu; Chen-Chen Zhao; Zheng-Yu Zhang; Ao-Ting Li; Jia-Nan Yan (Journal of Aquatic Food Product Technology, 2017)

Long-term grazing affects relationships between nitrogen form uptake and biomass of alpine meadow plants - Yu Guo; Li-Ping Liu; Li-Li Zheng; Fei-Hai Yu; Ming-Hua Song; Xian-Zhou Zhang (Plant Ecology, 2017)

Light use efficiency of a warm-temperate mixed plantation in north China - Xiaojuan Tong; Jinsong Zhang; Ping Meng; Jun Li; Ning Zheng (International Journal of Biometeorology, 2017)

Potential hypoglycaemic activity phenolic glycosides from Moringa oleifera seeds - Fang Wang; Huan-Huan Zhong; Wei-Ke Chen; Qing-Pu Liu; Cun-Yu Li; Yun-Feng Zheng; Guo-Ping Peng (Natural Product Research, 2017)

Fluid inclusions and C-H-O-S isotope systematics of early Permian porphyry Mo mineralization of the West Junggar region, NW China: the Suyunhe example - Chong Cao; Ping Shen; Changhao Li; Guoping Zheng (International Geology Review, 2017)

One new lignan derivative from the Combretum alfredii Hance - Meng Bai; Li-Jun Wu; Yue Cai; Shou-Yuan Wu; Xiao-Ping Song; Guang-Ying Chen; Cai-Juan Zheng; Chang-Ri Han (Natural Product Research, 2017)

Source analysis of organic matter in swine wastewater after anaerobic digestion with EEM-PARAFAC - Zhuo Zeng; Ping Zheng; Aqiang Ding; Meng Zhang; Ghulam Abbas; Wei Li (Environmental Science and Pollution Research, 2017)

Environmental controls of evapotranspiration in a mixed plantation in North China - Xiaojuan Tong; Jinsong Zhang; Ping Meng; Jun Li; Ning Zheng (International Journal of Biometeorology, 2017)

The first successful report of the in vitro life cycle of Chinese Leishmania: the in vitro conversion of Leishmania amastigotes has been raised to 94% by testing 216 culture medium compound - Jiao Li; Zhi-Wan Zheng; Gayathri Natarajan; Qi-Wei Chen; Da-Li Chen; Jian-Ping Chen (Acta Parasitologica, 2017)
Chinese

The complete mitogenome of a jumping spider Carrhotus xanthogramma (Araneae: Salticidae) and comparative analysis in four salticid mitogenomes - Wen-Yuan Fang; Zheng-Liang Wang; Chao Li; Xiao-Qing Yang; Xiao-Ping Yu (Genetica, 2016)

Responses and recovery pattern of sex steroid hormones in testis of Nile tilapia (Oreochromis niloticus) exposed to sublethal concentration of methomyl - Shun Long Meng; Li Ping Qiu; Geng Dong Hu; Li Min Fan; Chao Song; Yao Zheng; Wei Wu; Jian Hong Qu; Dan Dan Li; Jia Zhang Chen; Pao Xu (Ecotoxicology, 2016)

Development of chloroplast genomic resources for Akebia quinata (Lardizabalaceae) - Bin Li; Yanda Li; Qifei Cai; Furong Lin; Ping Huang; Yongqi Zheng (Conservation Genetics Resources, 2016)

RhoB/ROCK mediates oxygen–glucose deprivation-stimulated syncytiotrophoblast microparticle shedding in preeclampsia - Jian Han; Bo-ping Yang; Yi-lin Li; Hong-mei Li; Xiu-hui Zheng; Li-li Yu; Qiong Zhang; Ying-ru Zheng; Ping Yi; Li Li; Jian-xin Guo; Yuan-guo Zhou (Cell and Tissue Research, 2016)

One new berberine from the branches and leaves of Polyalthia obliqua Hook.f. & Thomson - Li-Jun Wu; Cai-Juan Zheng; Liu-Kai Wang; Chang-Ri Han; Xiao-Ping Song; Guang-Ying Chen; Xue-ming Zhou; Shou-yuan Wu; Xiao-bao Li; Meng Bai; Chun-xin Liu; Jun Yao (Natural Product Research, 2016)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

Male-Biased Capture in Light Traps in Spodoptera exigua (Lepidoptera: Noctuidae): Results from the Studies of Reproductive Activities - Wen-Jie Cheng; Xia-Lin Zheng; Pan Wang; Li-Lin Zhou; Sheng-Yun Si; Xiao-Ping Wang (Journal of Insect Behavior, 2016)

High expression of growth factor receptor-bound protein 14 predicts poor prognosis for colorectal cancer patients - Ping Yang; Jianchang Wei; Wanglin Li; Feng He; Shanqi Zeng; Tong Zhang; Zheng Sun; Jie Cao (Biotechnology Letters, 2016)

Enhanced short-cut nitrification in an airlift reactor by CaCO3 attachment on biomass under high bicarbonate condition - Mohammad Ali; Li-Yuan Chai; Hai-Ying Wang; Chong-Jian Tang; Xiao-Bo Min; Xu Yan; Cong Peng; Yu-Xia Song; Ping Zheng (Biodegradation, 2016)

A new phenolic compound with antioxidant activity from the branches and leaves of Pyrus pashia - Zhen-Jie Li; Xi Zheng; Chun-Ping Wan; Le Cai; Ying Li; Lin Huang; Zhong-Tao Ding (Natural Product Research, 2016)

Increasing the immune activity of exosomes: the effect of miRNA-depleted exosome proteins on activating dendritic cell/cytokine-induced killer cells against pancreatic cancer - Ri-sheng Que; Cheng Lin; Guo-ping Ding; Zheng-rong Wu; Li-ping Cao (Journal of Zhejiang University-SCIENCE B, 2016)

Functional and structural responses of bacterial and fungal communities from paddy fields following long-term rice cultivation - Yalong Liu; Ping Wang; Genxing Pan; David Crowley; Lianqing Li; Jinwei Zheng; Xuhui Zhang; Jufeng Zheng (Journal of Soils and Sediments, 2016)

Evolution of the microbial community of the biofilm in a methane-based membrane biofilm reactor reducing multiple electron acceptors - Ran Chen; Yi-Hao Luo; Jia-Xian Chen; Yin Zhang; Li-Lian Wen; Ling-Dong Shi; Youneng Tang; Bruce E. Rittmann; Ping Zheng; He-Ping Zhao (Environmental Science and Pollution Research, 2016)

Follicle-stimulating hormone increases the intramuscular fat content and expression of lipid biosynthesis genes in chicken breast muscle - Xiao-yan Cui; Ying-ying Li; Ran-ran Liu; Gui-ping Zhao; Mai-qing Zheng; Qing-he Li; Jie Wen (Journal of Zhejiang University-SCIENCE B, 2016)

Ectomycorrhizae of Tuber huidongense and T. liyuanum with Castanea mollissima and Pinus armandii - Shan-Ping Wan; Fu-Qiang Yu; Li Tang; Ran Wang; Yun Wang; Pei-Gui Liu; Xiang-Hua Wang; Yi Zheng (Mycorrhiza, 2016)

Positive association of genetic variations in the phospholipase C-like 1 gene with dermatomyositis in Chinese Han - Qian Wang; Si Chen; Yuan Li; Ping Li; Chanyuan Wu; Ziyan Wu; Qingjun Wu; Fei Sun; Jing Li; Wenjie Zheng; Chuiwen Deng; Fengchun Zhang; et al. (Immunologic Research, 2016)

A new triterpenoid compound from stems and leaves of American ginseng - Liu Han; Zhuo Li; Qian Zheng; Jin-Ping Liu; Ping-Ya Li (Natural Product Research, 2016)

The isoforms generated by alternative translation initiation adopt similar conformation in the selectivity filter in TREK-2 - Ren-Gong Zhuo; Peng Peng; Xiao-Yan Liu; Shu-Zhuo Zhang; Jiang-Ping Xu; Jian-Quan Zheng; Xiao-Li Wei; Xiao-Yun Ma (Journal of Physiology and Biochemistry, 2015)

The roles of methanogens and acetogens in dechlorination of trichloroethene using different electron donors - Li-Lian Wen; Yin Zhang; Ya-Wei Pan; Wen-Qi Wu; Shao-Hua Meng; Chen Zhou; Youneng Tang; Ping Zheng; He-Ping Zhao (Environmental Science and Pollution Research, 2015)

Bioaccumulation and Elimination of the Herbicide Clomazone in the Earthworms Eisenia fetida - Jia Cao; Ping Li; Qing X. Li; Pengfei Zheng; Xiaoping Diao (Bulletin of Environmental Contamination and Toxicology, 2015)

Rice grassy stunt virus nonstructural protein p5 serves as a viral suppressor of RNA silencing and interacts with nonstructural protein p3 - Chao Zhang; Xiao-juan Liu; Kang-cheng Wu; Lu-Ping Zheng; Zuo-mei Ding; Fei Li; Peng Zou; Liang Yang; Jian-guo Wu; Zu-jian Wu (Archives of Virology, 2015)

The miR-573/apoM/Bcl2A1-dependent signal transduction pathway is essential for hepatocyte apoptosis and hepatocarcinogenesis - Yan-Wei Hu; Zhi-Ping Chen; Xiu-Mei Hu; Jia-Yi Zhao; Jin-Lan Huang; Xin Ma; Shu-Fen Li; Yu-Rong Qiu; Xiao-Juan Wu; Yan-Hua Sha; Ji-Juan Gao; Yan-Chao Wang; et al. (Apoptosis, 2015)

Identification of volatile and softening-related genes using digital gene expression profiles in melting peach - Xiong-wei Li; Jun Jiang; Li-ping Zhang; Yi Yu; Zheng-wen Ye; Xiu-min Wang; Jing-yi Zhou; Ming-liang Chai; Hui-qin Zhang; Pere Arús; Hui-juan Jia; Zhong-shan Gao (Tree Genetics & Genomes, 2015)

Screening for simple sequence repeat markers in Puccinia striiformis tritici based on genomic sequence - Gang-ming Zhan; Fu-ping Wang; Huai-yong Luo; Shu-chang Jiang; Wen-ming Zheng; Li-li Huang; Zhen-sheng Kang (Journal of Zhejiang University-SCIENCE B, 2015)

Kinetic changes of regulatory B10 cells in collagen-induced arthritis could be regulated by cytokines IFN-γ and TGF-β1 - Zhaohui Zheng; Tao Liu; Xueyi Li; Jin Ding; Yuan Feng; Jinlin Miao; Xing Luo; Zhenbiao Wu; Ping Zhu (Inflammation Research, 2015)

Protective Effect of Apigenin on Ischemia/Reperfusion Injury of the Isolated Rat Heart - Jing Hu; Zilin Li; Li-ting Xu; Ai-jun Sun; Xiao-yan Fu; Li Zhang; Lin-lin Jing; An-dong Lu; Yi-fei Dong; Zheng-ping Jia (Cardiovascular Toxicology, 2015)

The aflatoxin-detoxifizyme specific expression in mouse parotid gland - Li-zeng Guan; Yu-ping Sun; Jin-shun Cai; Han-dong Wu; Long-zheng Yu; Yong-liang Zhang; Qian-yun Xi (Transgenic Research, 2015)

Safety and efficacy study of lung cancer stem cell vaccine - Mao Lin; Shu-Ying Li; Ke-Cheng Xu; Zheng-Ping Liu; Feng Mu; Yuan-Ying Yuan; Xiao-Hua Wang; Ji-Bing Chen; Qiao Li (Immunologic Research, 2015)

FaesPI, a Fagopyrum esculentum PISTILLATA ortholog, is involved only in stamen development - Zheng-Wu Fang; Xue-Ping Li; Xiao-Fang Li; Zhi-Xiong Liu (Journal of Plant Biology, 2015)

System‐wide characterization of bZIP transcription factor proteins involved in infection‐related morphogenesis of M agnaporthe oryzae - Wei Tang; Yanyan Ru; Li Hong; Qian Zhu; Rongfang Zuo; Xianxian Guo; Jingzhen Wang; Haifeng Zhang; Xiaobo Zheng; Ping Wang; Zhengguang Zhang (Environmental Microbiology, 2015)
Summary The basic leucine zipper ( bZIP ) domain‐containing transcription factors ( TFs ) function as key regulators of cellular growth and differentiation in eukaryotic organisms including fungi. We have previously identified MoAp 1 and MoAtf 1 as bZIP TFs in M agnaporthe oryzae and demonstrated that they regulate the oxidative stress response and are critical in conidiogenesis and pathogenicity. Studies of bZIP proteins could provide a novel strategy for controlling rice blast, but a systematic examination of the bZIP proteins has not been carried out. Here, we identified 19 additional bZIP TFs and characterized their functions. We found that the majority of these TFs exhibit active functions, most notably, in conidiogenesis. We showed that MoHac 1 regulates the endoplasmic reticulum stress response through a conserved unfolded protein response pathway, MoMetR controls amino acid metabolism to govern growth and differentiation, and MoBzip 10 governs appressorium function and invasive hyphal growth. Moreover, MoBzip 5 participates in appressorium formation through a pathway distinct from that MoBzip 10, and MoMeaB appears to exert a regulatory role through nutrient uptake and nitrogen utilization. Collectively, our results provide insights into shared and specific functions associated with each of these TFs and link the regulatory roles to the fungal growth, conidiation, appressorium formation, host penetration and pathogenicity.

Anti-inflammatory Effects of Propofol on Lipopolysaccharides-Treated Rat Hepatic Kupffer Cells - Sen Li; Chun-xia Wang; Nai-zheng Liu; Ping Liu (Cell Biochemistry and Biophysics, 2015)

Lead accumulation and tolerance of Moso bamboo (Phyllostachys pubescens) seedlings: applications of phytoremediation - Dan Liu; Song Li; Ejazul Islam; Jun-ren Chen; Jia-sen Wu; Zheng-qian Ye; Dan-li Peng; Wen-bo Yan; Kou-ping Lu (Journal of Zhejiang University-SCIENCE B, 2015)

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

Distribution of plant species and species-soil relationship in the east central Gurbantunggut Desert, China - Ping An; Xiangjun Li; Yuanrun Zheng; A. Egrinya Eneji; Yunus Qiman; Mingqing Zheng; Shinobu Inanaga (Journal of Geographical Sciences, 2015)

Determination of multiple elements in samples of the medicinal plant Marsdenia tenacissima and estimation of geographic origin via pattern recognition techniques - Chao Li; Qiao-sheng Guo; Sheng-chao Yang; Kai-yan Zheng; Wang-ping Li; Zhen-gui Meng; Xiang-zeng Xu (Journal of Natural Medicines, 2015)

Influence of PTGS1, PTGFR, and MRP4 genetic variants on intraocular pressure response to latanoprost in Chinese primary open-angle glaucoma patients - Li-chen Gao; Di Wang; Fang-qun Liu; Zheng-yu Huang; Hong-guang Huang; Gui-hua Wang; Xi Chen; Qun-zhi Shi; Li Hong; Li-ping Wu; Jie Tang (European Journal of Clinical Pharmacology, 2015)

Induction of female 2n gametes and creation of tetraploids through sexual hybridization in cassava (Manihot esculenta) - Hang-Gui Lai; Xia Chen; Zheng Chen; Jian-Qiu Ye; Kai-Mian Li; Jin-Ping Liu (Euphytica, 2015)

Rapid development of proteomics in China: from the perspective of the Human Liver Proteome Project and technology development - Ning Li; ZhongWei Xu; LinHui Zhai; YanChang Li; FengXu Fan; JunJie Zheng; Ping Xu; FuChu He (Science China Life Sciences, 2014)

Analysis of small RNAs derived from Chinese wheat mosaic virus - Jian Yang; Shi-Ling Zheng; Heng-Mu Zhang; Xiao-Ya Liu; Jing Li; Jun-Min Li; Jian-Ping Chen (Archives of Virology, 2014)

IL-17A promotes ventricular remodeling after myocardial infarction - Su-Feng Zhou; Jing Yuan; Meng-Yang Liao; Ni Xia; Ting-Ting Tang; Jing-Jing Li; Jiao Jiao; Wen-Yong Dong; Shao-Fang Nie; Zheng-Feng Zhu; Wen-Cai Zhang; Bing-Jie Lv; et al. (Journal of Molecular Medicine, 2014)

Assessment of chlorpyrifos exposure and absorbed daily doses among infants living in an agricultural area of the Province of Jiangsu, China - Ping Liu; Chun-hua Wu; Xiu-li Chang; Xiao-juan Qi; Ming-lan Zheng; Zhi-jun Zhou (International Archives of Occupational and Environmental Health, 2014)

Recycling of sediment into the mantle source of K-rich mafic rocks: Sr–Nd–Hf–O isotopic evidence from the Fushui complex in the Qinling orogen - Hao Wang; Yuan-Bao Wu; Chao-Ran Li; Tian-Yu Zhao; Zheng-Wei Qin; Liu-Qin Zhu; Shan Gao; Jian-Ping Zheng; Xiao-Ming Liu; Lian Zhou; Yang Zhang; Sai-Hong Yang (Contributions to Mineralogy and Petrology, 2014)

Biofilm Formation of Streptococcus equi ssp. zooepidemicus and Comparative Proteomic Analysis of Biofilm and Planktonic Cells - Li Yi; Yang Wang; Zhe Ma; Hui Zhang; Yue Li; Jun-xi Zheng; Yong-chun Yang; Hong-jie Fan; Cheng-ping Lu (Current Microbiology, 2014)

Indian Ocean variability in the CMIP5 multi-model ensemble: the zonal dipole mode - Lin Liu; Shang-Ping Xie; Xiao-Tong Zheng; Tim Li; Yan Du; Gang Huang; Wei-Dong Yu (Climate Dynamics, 2014)

Hepatocellular Carcinoma in Budd-Chiari Syndrome: Enhancement Patterns at Dynamic Gadolinium-Enhanced T1-Weighted MR Imaging - Chun Yang; Kai Xu; Junnian Zheng; Ping Ma; Chunfeng Hu; Shaodong Li; Yutao Rong; Xin Lu; Qingqiao Zhang; Maoheng Zu; Rong Hua; Ling Zhang (Cell Biochemistry and Biophysics, 2014)

Promoters of HcTPS1 and HcTPS2 Genes from Hedychium coronarium Direct Floral-Specific, Developmental-Regulated and Stress-Inducible Gene Expression in Transgenic Tobacco - Xin-Yue Li; Shao-Yuan Zheng; Rang-Cai Yu; Yan-Ping Fan (Plant Molecular Biology Reporter, 2014)

A new epimer of ocotillol from stems and leaves of American ginseng - Liu Han; Mei-Yu Lin; Qian Zheng; Hai-Yu Liu; Hai-Yan Liu; Gang Dong; Jin-Ping Liu; Ping-Ya Li (Natural Product Research, 2014)

Bioactive Equivalence of Combinatorial Components Identified in Screening of an Herbal Medicine - Peng Liu; Hua Yang; Fang Long; Hai-Ping Hao; Xiaojun Xu; Ying Liu; Xiao-Wei Shi; Dan-Dan Zhang; Hao-Chuan Zheng; Qian-Ying Wen; Wen-Wen Li; Hui Ji; et al. (Pharmaceutical Research, 2014)

Glaucocalyxin A and B Regulate Growth and Induce Oxidative Stress in Lettuce (Lactuca sativa L.) Roots - Wen Hua Yang; Li Ping Zheng; Hui Yan Yuan; Jian Wen Wang (Journal of Plant Growth Regulation, 2014)

A dwarfing mutant caused by deactivation function of alpha subunit of the heterotrimeric G-protein in rice - De-wei Yang; Xiang-hua Zheng; Chao-ping Cheng; Wen-da Wang; Deng-hui Xing; Li-bin Lu; Chen-de Liu; Ning Ye; Mei-juan Zeng; Xin-fu Ye (Euphytica, 2014)

Bacillus thuringiensis subsp. sichuansis strain MC28 produces a novel crystal protein with activity against Culex quinquefasciatus larvae - Peng Guan; Xiaojuan Dai; Jun Zhu; Qiao Li; Shuangcheng Li; Shiquan Wang; Ping Li; Aiping Zheng (World Journal of Microbiology and Biotechnology, 2014)

VPA inhibits renal cancer cell migration by targeting HDAC2 and down-regulating HIF-1α - Feng-qiang Yang; Min Liu; Feng-ping Yang; Jianping Che; Wei Li; Wei Zhai; Guang-chun Wang; Jun-hua Zheng; Xi Li (Molecular Biology Reports, 2014)

Mas-related G protein-coupled receptor D is coupled to endogenous calcium-activated chloride channel in Xenopus oocytes - Ren-Gong Zhuo; Xiao-Yun Ma; Pei-Lan Zhou; Xiao-Yan Liu; Kang Zhang; Xiao-Li Wei; Hai-Tao Yan; Jiang-Ping Xu; Jian-Quan Zheng (Journal of Physiology and Biochemistry, 2014)

The TNF-alpha -308G/A polymorphism is associated with type 2 diabetes mellitus: an updated meta-analysis - Yuliang Zhao; Zheng Li; Ling Zhang; Yonggang Zhang; Yingying Yang; Yi Tang; Ping Fu (Molecular Biology Reports, 2014)

Sorption of ammonium and phosphate from aqueous solution by biochar derived from phytoremediation plants - Zheng Zeng; Song-da Zhang; Ting-qiang Li; Feng-liang Zhao; Zhen-li He; He-ping Zhao; Xiao-e Yang; Hai-long Wang; Jing Zhao; Muhammad Tariq Rafiq (Journal of Zhejiang University-SCIENCE B, 2013)

Radioactive Seed Implantation Combined with Prosthesis Denture in Treatment of Oral and Maxillofacial Malignancy - Jian Meng; Qing-fei Meng; Qian-ping Gu; Ya-meng Si; Hao Zheng; Jie Zhang; Zhi-ping Li; Qian-wei Zhuang (Cell Biochemistry and Biophysics, 2013)

Elevated Plasma Levels of Hypermethylated RASSF1A Gene Sequences in Pregnant Women with Intrahepatic Cholestasis - Ping Yi; Na Yin; Yingru Zheng; Hongmei Jiang; Xinmei Yu; Yaohua Yan; Qiang Liu; Fenglian Xiao; Li Li (Cell Biochemistry and Biophysics, 2013)

The HTLV-1 HBZ protein inhibits cyclin D1 expression through interacting with the cellular transcription factor CREB - Yunyun Ma; Shangen Zheng; Yuanyuan Wang; Wenqiao Zang; Min Li; Na Wang; Ping Li; Jing Jin; Ziming Dong; Guoqiang Zhao (Molecular Biology Reports, 2013)

Expression and redistribution of β-catenin in the cardiac myocytes of left ventricle of spontaneously hypertensive rat - Qiaoli Zheng; Ping Chen; Zeqing Xu; Faqian Li; Xian Ping Yi (Journal of Molecular Histology, 2013)

Cytochrome P450 2A6 deletion polymorphism and risk of lung cancer: a meta-analysis - Zheng-Bing Liu; Jun Shu; Li-Ping Wang; Cheng Jin; Zhi-Xia Lou (Molecular Biology Reports, 2013)

RNA interference mediated pten knock-down inhibit the formation of polycystic ovary - Jie-Xiu Ouyang; Tao Luo; Hui-Yun Sun; Jian Huang; Dan-Feng Tang; Lei Wu; Yue-Hui Zheng; Li-Ping Zheng (Molecular and Cellular Biochemistry, 2013)

β-Glucanase specific expression in the parotid gland of transgenic mice - Li-zheng Guan; Yu-ping Sun; Qian-yun Xi; Jing-lan Wang; Jun-yun Zhou; Gang Shu; Qing-yan Jiang; Yong-liang Zhang (Transgenic Research, 2013)

Continuous evolution of avian infectious bronchitis virus resulting in different variants co-circulating in southern China - Meng Li; Mei-Lan Mo; Bai-Cheng Huang; Wen-Sheng Fan; Zheng-Ji Wei; Tian-Chao Wei; Kang-Ran Li; Ping Wei (Archives of Virology, 2013)

DNA methylation alterations of upland cotton (Gossypium hirsutum) in response to cold stress - Hong Hong Fan; Jun Wei; Ting Chun Li; Zheng Peng Li; Ning Guo; Yong Ping Cai; Yi Lin (Acta Physiologiae Plantarum, 2013)

Finer resolution observation and monitoring of global land cover: first mapping results with Landsat TM and ETM+ data - Peng Gong; Jie Wang; Le Yu; Yongchao Zhao; Yuanyuan Zhao; Lu Liang; Zhenguo Niu; Xiaomeng Huang; Haohuan Fu; Shuang Liu; Congcong Li; Xueyan Li; et al. (International Journal of Remote Sensing, 2013)

Genetic structure and phylogeography of Pyrus pashia L. (Rosaceae) in Yunnan Province, China, revealed by chloroplast DNA analyses - Jing Liu; Ping Sun; Xiaoyan Zheng; Daniel Potter; Kunming Li; Chunyun Hu; Yuanwen Teng (Tree Genetics & Genomes, 2013)

Enhancing production of a 24-membered ring macrolide compound by a marine bacterium using response surface methodology - Hua Chen; Mian-bin Wu; Zheng-jie Chen; Ming-lu Wang; Jian-ping Lin; Li-rong Yang (Journal of Zhejiang University-SCIENCE B, 2013)

Drought stress induces oxidative stress and the antioxidant defense system in ascorbate-deficient vtc1 mutants of Arabidopsis thaliana - Yue Niu; Yuping Wang; Ping Li; Feng Zhang; Heng Liu; Guochang Zheng (Acta Physiologiae Plantarum, 2013)

Effects of glacier melting on socioeconomic development in the Manas River basin, China - Xiang-ling Tang; Li-Ping Xu; Zheng-Yong Zhang; Xin Lv (Natural Hazards, 2013)

Molecular epidemiology of hepatitis C virus among different groups of people in the province of Fujian, China - Ying Ye; Yan-sheng Yan; Ge Chen; Ping-ping Yan; Wu-xiong Zheng; Yan-qin Deng; Xiu-hui Yang; Shou-li Wu; Zhi-shan Zhang (Archives of Virology, 2013)

Involvement of large conductance Ca2+-activated K+ channel in laminar shear stress-induced inhibition of vascular smooth muscle cell proliferation - Xiaoling Jia; Jingyun Yang; Wei Song; Ping Li; Xia Wang; Changdong Guan; Liu Yang; Yan Huang; Xianghui Gong; Meili Liu; Lisha Zheng; Yubo Fan (Pflügers Archiv - European Journal of Physiology, 2013)

Tetramethylpyrazine induces G0/G1 cell cycle arrest and stimulates mitochondrial-mediated and caspase-dependent apoptosis through modulating ERK/p53 signaling in hepatic stellate cells in vitro - Feng Zhang; De-Song Kong; Zi-Li Zhang; Na Lei; Xiao-Jing Zhu; Xiao-Ping Zhang; Li Chen; Yin Lu; Shi-Zhong Zheng (Apoptosis, 2013)

Molecular diversity of restriction enzyme sites, Indels and upstream open reading frames (uORFs) of 5′ untransalted regions (UTRs) of Waxy genes in Triticum L. and Aegilops L. species - Wei Li; Zhen Gao; Wei Xiao; Yu-Ming Wei; Ya-Xi Liu; Guo-Yue Chen; Zhi-En Pu; Hua-Ping Chen; You-Liang Zheng (Genetic Resources and Crop Evolution, 2012)

Enhanced overall resistance to Fusarium seedling blight and Fusarium head blight in transgenic wheat by co-expression of anti-fungal peptides - Zheng-Wei Liu; He-Ping Li; Wei Cheng; Peng Yang; Jing-Bo Zhang; An-Dong Gong; Yan-Ni Feng; W. G. Dilantha Fernando; Yu-Cai Liao (European Journal of Plant Pathology, 2012)

Synthesis, crystal structure and biological activity of novel anthranilic diamide insecticide containing alkyl ether group - Yu Zhao; Li-ping Xu; Jun Tong; Yong-qiang Li; Li-xia Xiong; Fang Li; Li-na Peng; Zheng-ming Li (Molecular Diversity, 2012)

Gas Leakage Prediction Model of Large-Scale Explosions in Hard Rock Based on Quantification Theory - Xin-Zheng Wang; Jian-Jie Chen; Ping Li; Xiao She; Guan-Yi Niu (Transport in Porous Media, 2012)

Traditional Chinese medicines benefit to nonalcoholic fatty liver disease: a systematic review and meta-analysis - Ke-Qing Shi; Yu-Chen Fan; Wen-Yue Liu; Ling-Fei Li; Yong-Ping Chen; Ming-Hua Zheng (Molecular Biology Reports, 2012)

Renal insufficiency is an independent predictor of in-hospital mortality for patients with acute myocardial infarction receiving primary percutaneous coronary intervention - Jian-ping Li; Mohetaboer Momin; Yong Huo; Chun-yan Wang; Yan Zhang; Yan-jun Gong; Zhao-ping Liu; Xin-gang Wang; Bo Zheng (Journal of Zhejiang University-SCIENCE B, 2012)

Structural insights into a human anti-IFN antibody exerting therapeutic potential for systemic lupus erythematosus - Songying Ouyang; Bin Gong; Jin-Zhi Li; Li-Xia Zhao; Wei Wu; Fu-Shun Zhang; Lina Sun; Shu-Jun Wang; Meng Pan; Chuan Li; Wenguang Liang; Neil Shaw; et al. (Journal of Molecular Medicine, 2012)

Highly Sensitive Detection of Residual Chlorpromazine Hydrochloride with Solid Substrate Room Temperature Phosphorimetry - Jia-Ming Liu; Li-ping Lin; Xin-Xing Wang; Xuan Lin; Ping Zhou; Shao-Qin Lin; Zhi-Yong Zheng (Journal of Fluorescence, 2012)

Prevention and treatment of allergic inflammation by an Fcγ-Der f2 fusion protein in a murine model of dust mite-induced asthma - Li-hui Lin; Ping Zheng; John W. M. Yuen; Juan Wang; Juan Zhou; Cun-quan Kong; Xia Peng; Jia Li; Li Li (Immunologic Research, 2012)

Distribution and linkage disequilibrium analysis of polymorphisms of MC4R, LEP, H-FABP genes in the different populations of pigs, associated with economic traits in DIV2 line - Zhe Chao; Feng Wang; Chang-Yan Deng; Li-Min Wei; Rui-Ping Sun; Hai-Long Liu; Quan-Wei Liu; Xin-Li Zheng (Molecular Biology Reports, 2012)

Risk stratification of spontaneous bacterial peritonitis in cirrhosis with ascites based on classification and regression tree analysis - Ke-Qing Shi; Yu-Chen Fan; Li Ying; Xian-Feng Lin; Mei Song; Ling-Fei Li; Xie-Yan Yu; Yong-Ping Chen; Ming-Hua Zheng (Molecular Biology Reports, 2012)

Cloning and the expression pattern of Spätzle gene during embryonic development and bacterial challenge in Artemia sinica - Lu-ping Zheng; Lin Hou; Miao Yu; Xiang Li; Xiang-yang Zou (Molecular Biology Reports, 2012)

Spontaneous retroperitoneal hemorrhage after hemodialysis involving anticoagulant agents - Wen-xing Fan; Zheng-xu Deng; Fang Liu; Rong-bo Liu; Ling He; Bogati Amrit; Li Zang; Jing-wen Li; Xian-rong Liu; Song-min Huang; Ping Fu (Journal of Zhejiang University-SCIENCE B, 2012)

Identification of volatile components in yak butter using SAFE, SDE and HS-SPME-GC/MS - Ning Li; Bao-Guo Sun; Fu-Ping Zheng; Hai-Tao Chen; Si-Yuan Liu; Chen Gu; Zhen-Yang Song (Natural Product Research, 2012)

Hydrogen sulfide protects H9c2 cells against doxorubicin-induced cardiotoxicity through inhibition of endoplasmic reticulum stress - Xiu-Yu Wang; Chun-Tao Yang; Dong-Dan Zheng; Li-Qiu Mo; Ai-Ping Lan; Zhan-Li Yang; Fen Hu; Pei-Xi Chen; Xin-Xue Liao; Jian-Qiang Feng (Molecular and Cellular Biochemistry, 2012)

Co-expression and Synergism Analysis of Vip3Aa29 and Cyt2Aa3 Insecticidal Proteins from Bacillus thuringiensis - Xiumei Yu; Tao Liu; Zhiguang Sun; Peng Guan; Jun Zhu; Shiquan Wang; Shuangcheng Li; Qiming Deng; Lingxia Wang; Aiping Zheng; Ping Li (Current Microbiology, 2012)

Inhibition of ROS-activated ERK1/2 pathway contributes to the protection of H2S against chemical hypoxia-induced injury in H9c2 cells - Xiao-Bian Dong; Chun-Tao Yang; Dong-Dan Zheng; Li-Qiu Mo; Xiu-Yu Wang; Ai-Ping Lan; Fen Hu; Pei-Xi Chen; Jian-Qiang Feng; Mei-Fen Zhang; Xin-Xue Liao (Molecular and Cellular Biochemistry, 2012)

The −1123G>C Variant of PTPN22 Gene Promoter is Associated with Latent Autoimmune Diabetes in Adult Chinese Hans - Fang Liu; Jiang Liu; Tai-shan Zheng; Qing Li; Chen Wang; Xiao-ping Pan; Huijuan Lu; Yu-wu Zhao (Cell Biochemistry and Biophysics, 2012)

Serotype and genotype diversity of infectious bronchitis viruses isolated during 1985-2008 in Guangxi, China - Meng Li; Xiu-Ying Wang; Ping Wei; Qiu-Ying Chen; Zheng-Ji Wei; Mei-Lan Mo (Archives of Virology, 2012)

Protein sequence analysis based on hydropathy profile of amino acids - Xiao-li Xie; Li-fei Zheng; Ying Yu; Li-ping Liang; Man-cai Guo; John Song; Zhi-fa Yuan (Journal of Zhejiang University-SCIENCE B, 2012)

Association of type 2 diabetes susceptibility genes (TCF7L2, SLC30A8, PCSK1 and PCSK2) and proinsulin conversion in a Chinese population - Xiaoya Zheng; Wei Ren; Suhua Zhang; Jingjing Liu; Sufang Li; Jinchao Li; Ping Yang; Jun He; Shaochu Su; Ping Li (Molecular Biology Reports, 2012)

A New Genotyping Method for Detecting Low Abundance Single Nucleotide Mutations Based on Gap Ligase Chain Reaction and Quantitative PCR Assay - Ping Yi; Hongmei Jiang; Li Li; Faguo Dai; Yingru Zheng; Jian Han; Zhuqin Chen; Jianxin Guo (Cell Biochemistry and Biophysics, 2012)

Enhancement of succinic acid production by osmotic-tolerant mutant strain of Actinobacillus succinogenes - Xiaojiang Fang; Jian Li; Xiaoyu Zheng; Yonglan Xi; Kequan Chen; Ping Wei; PingKai Ouyang; Min Jiang (World Journal of Microbiology and Biotechnology, 2011)

Interleukin-6, but Not Soluble Adhesion Molecules, Predicts a Subsequent Mortality from Cardiovascular Disease in Patients with Acute ST-Segment Elevation Myocardial Infarction - Zhen-Xing Fan; Qi Hua; Yin-Ping Li; Rong-Kun Liu; Zheng Yang (Cell Biochemistry and Biophysics, 2011)

The difference of glutathione antioxidant system in newly weaned and young mice liver and its involvement in isoline-induced hepatotoxicity - Qing-Ning Liang; Yu-Chen Sheng; Ping Jiang; Li-Li Ji; Yu-Ye Xia; Yang Min; Zheng-Tao Wang (Archives of Toxicology, 2011)

M. tuberculosis H37Rv Infection of Chinese Rhesus Macaques - Jing Zhang; Yan-Qing Ye; Yong Wang; Ping-Zheng Mo; Qiao-Yang Xian; Yan Rao; Rong Bao; Ming Dai; Jun-Yan Liu; Ming Guo; Xin Wang; Zhi-Xiang Huang; et al. (Journal of Neuroimmune Pharmacology, 2011)

Tissue-specific and expression of porcine growth hormone gene in BAC transgenic mice - Jia Tong; Simon G. Lillico; Ming Jun Bi; Tong Qing; Xiao Fang Liu; YuanYuan Wang; Min Zheng; Meili Wang; Yun Ping Dai; C. Bruce A. Whitelaw; Ning Li (Transgenic Research, 2011)

Glycomyces halotolerans sp. nov., a novel actinomycete isolated from a hypersaline habitat in Xinjiang, China - Tong-Wei Guan; Zhan-Feng Xia; Jing Xiao; Nan Wu; Zheng-Jun Chen; Li-Li Zhang; Xiao-Ping Zhang (Antonie van Leeuwenhoek, 2011)

Pseudonocardia bannaensis sp. nov., a novel actinomycete isolated from the surface-sterilized roots of Artemisia annua L. - Guo-Zhen Zhao; Jie Li; Wen-Yong Zhu; Xiu-Ping Li; Shou-Zheng Tian; Li-Xing Zhao; Li-Hua Xu; Wen-Jun Li (Antonie van Leeuwenhoek, 2011)

Gα13 is closely related to hematopoiesis in zebrafish - Ding Ye; Qiwen Yang; Yang Li; Xinyun Huang; Jiarui Hu; Shiguang Qian; Zheng Tan; Ping Song (Molecular Biology Reports, 2011)

Trichodermanin A, a novel diterpenoid from endophytic fungus culture - Pei-Xin Sun; Cheng-Jian Zheng; Wen-Chao Li; Gui-Lin Jin; Fang Huang; Lu-Ping Qin (Journal of Natural Medicines, 2011)

Characterization of Vegetative Insecticidal Protein vip Genes of Bacillus thuringiensis from Sichuan Basin in China - Xiumei Yu; Aiping Zheng; Jun Zhu; Shiquan Wang; Lingxia Wang; Qiming Deng; Shuangcheng Li; Huainian Liu; Ping Li (Current Microbiology, 2011)

Catastrophic landslides associated with the M8.0 Wenchuan earthquake - Yueping Yin; Wanmo Zheng; Xiaochun Li; Ping Sun; Bin Li (Bulletin of Engineering Geology and the Environment, 2011)

High-mobility group box 1 exacerbates concanavalin A-induced hepatic injury in mice - Quan Gong; Hui Zhang; Jun-hua Li; Li-hua Duan; Shan Zhong; Xiao-ling Kong; Fang Zheng; Zheng Tan; Ping Xiong; Gang Chen; Min Fang; Fei-li Gong (Journal of Molecular Medicine, 2010)

Effects of missing marker and segregation distortion on QTL mapping in F2 populations - Luyan Zhang; Shiquan Wang; Huihui Li; Qiming Deng; Aiping Zheng; Shuangcheng Li; Ping Li; Zhonglai Li; Jiankang Wang (Theoretical and Applied Genetics, 2010)

A new species of the genus Triplophysa (Nemacheilinae: Balitoridae), Triplophysa jianchuanensis sp. nov, from Yunnan, China - Lan-Ping Zheng; Li-Na Du; Xiao-Yong Chen; Jun-Xing Yang (Environmental Biology of Fishes, 2010)

A Comprehensive Study of Deep Catalytic Oxidation of Benzene, Toluene, Ethyl Acetate, and their Mixtures over Pd/ZSM-5 Catalyst: Mutual Effects and Kinetics - Chi He; Peng Li; Jie Cheng; Zheng-Ping Hao; Zhi-Ping Xu (Water, Air, & Soil Pollution, 2010)

Quantitative prediction of channel sand bodies based on seismic peak attributes in the frequency domain and its application - Lu-Ping Sun; Xiao-Dong Zheng; Hao Shou; Jing-Song Li; Yan-Dong Li (Applied Geophysics, 2010)

Enhanced salt tolerance of transgenic poplar plants expressing a manganese superoxide dismutase from Tamarix androssowii - Yu Cheng Wang; Guan Zheng Qu; Hong Yan Li; Ying Jie Wu; Chao Wang; Gui Feng Liu; Chuan Ping Yang (Molecular Biology Reports, 2010)

Enhancing viability of two biocontrol yeasts in liquid formulation by applying sugar protectant combined with antioxidant - Jia Liu; Shi-Ping Tian; Bo-Qiang Li; Guo-Zheng Qin (BioControl, 2009)

The effect of root exudates from two transgenic insect-resistant cotton lines on the growth of Fusarium oxysporum - Xiao-gang Li; Biao Liu; Sondre Heia; Dou-dou Liu; Zheng-min Han; Ke-xin Zhou; Jin-jie Cui; Jun-yu Luo; Yang-ping Zheng (Transgenic Research, 2009)

A new species of Genus Triplophysa (Nemacheilinae: Balitoridae), Triplophysa longipectoralis sp. nov, from Guangxi, China - Lan-Ping Zheng; Li-Na Du; Xiao-Yong Chen; Jun-Xing Yang (Environmental Biology of Fishes, 2009)

Cloning and Characterization of Two Novel Crystal Protein Genes, cry54Aa1 and cry30Fa1, from Bacillus thuringiensis Strain BtMC28 - Furong Tan; Jun Zhu; Jie Tang; Xueming Tang; Shiquan Wang; Aiping Zheng; Ping Li (Current Microbiology, 2009)

A value chain approach to crisis response system: the case of Qingdao - Jian Hua Li; Zheng Ping Zhang; Rui Huan Jing; Chong Fu Huang (Stochastic Environmental Research and Risk Assessment, 2009)

Molecular cytogenetic characterization of wheat–Secale africanum amphiploids and derived introgression lines with stripe rust resistance - Zu-Jun Yang; Guang-Rong Li; Ju-Qing Jia; Xue Zeng; Meng-Ping Lei; Zi-Xian Zeng; Tao Zhang; Zheng-Long Ren (Euphytica, 2009)

Gastric carcinoma with osteoclast-like giant cells: a case report and review of the literature - Li-duan Zheng; Xiu-ping Yang; Hua-xiong Pan; Xiu Nie; Jun He; Qing Lv; Qiang-song Tong (Journal of Zhejiang University-SCIENCE B, 2009)

Identification of α-gliadin genes in Dasypyrum in relation to evolution and breeding - Guang-Rong Li; Cheng Liu; Zi-Xian Zeng; Ju-Qing Jia; Tao Zhang; Jian-Ping Zhou; Zheng-Long Ren; Zu-Jun Yang (Euphytica, 2009)

Distribution, sources, and potential risk of polycyclic aromatic hydrocarbons (PAHs) in drinking water resources from Henan Province in middle of China - Ying-ge Ma; Jin-ping Cheng; Fei Jiao; Ke-xin Duo; Zheng Rong; Ming Li; Wen-hua Wang (Environmental Monitoring and Assessment, 2008)

Involvement of ERK and AKT signaling in the growth effect of arginine vasopressin on adult rat cardiac fibroblast and the modulation by simvastatin - Yan-Ping He; Lian-You Zhao; Qiang-Sun Zheng; Shao-Wei Liu; Xiao-Yan Zhao; Xiao-Long Lu; Xiao-Lin Niu; Xia Li (Molecular and Cellular Biochemistry, 2008)

Responses to air temperature and soil moisture of growth of four dominant species on sand dunes of central Inner Mongolia - Yuanrun Zheng; Glyn M. Rimmington; Zhixiao Xie; Lei Zhang; Ping An; Guangsheng Zhou; Xiangjun Li; Yunjiang Yu; Lijun Chen; Hideyuki Shimizu (Journal of Plant Research, 2008)

Proteiomic patterns for endometrial cancer using SELDI-TOF-MS - Li-rong Zhu; Wen-ying Zhang; Li Yu; Yan-hua Zheng; Jun Hu; Qin-ping LIAO (Journal of Zhejiang University-SCIENCE B, 2008)

Isolation of a new repetitive DNA sequence from Secale africanum enables targeting of Secale chromatin in wheat background - Cheng Liu; Zu-Jun Yang; Guang-Rong Li; Zi-Xian Zeng; Yong Zhang; Jian-Ping Zhou; Zhao-Hui Liu; Zheng-Long Ren (Euphytica, 2008)

Notch activation promotes cell proliferation and the formation of neural stem cell-like colonies in human glioma cells - Xue-Ping Zhang; Gang Zheng; Lian Zou; Hui-Ling Liu; Li-Hong Hou; Peng Zhou; Dan-Dan Yin; Qi-Jun Zheng; Liang Liang; Su-Zhen Zhang; Lei Feng; Li-Bo Yao; et al. (Molecular and Cellular Biochemistry, 2007)

Preoperative localization and minimally invasive management of primary hyperparathyroidism concomitant with thyroid disease - Yi-xiong Zheng; Shao-ming Xu; Ping Wang; Li Chen (Journal of Zhejiang University-SCIENCE B, 2007)

Establishment, Characterization, and Virus Susceptibility of a New Marine Cell Line from Red Spotted Grouper (Epinephelus akaara) - Guang-Zhou Zhou; Zheng-Qiu Li; Xiu-Ping Yuan; Qi-Ya Zhang (Marine Biotechnology, 2007)

Assignment of CCR7 gene to chicken chromosome 27 by radiation hybrid panel mapping - Yong Tian; Li-zhi Lu; Yan Fu; Zheng-rong Tao; Jun-da Shen; De-qian Wang; Ai-ping Yuan; Zhao-zheng Yin (Journal of Zhejiang University-SCIENCE B, 2007)

Pathogenesis of Parkinson’s disease: oxidative stress, environmental impact factors and inflammatory processes - Hong Yuan; Jing-Chen Zheng; Ping Liu; Shao-Feng Zhang; Jian-Yang Xu; Li-Min Bai (Neuroscience Bulletin, 2007)

Determination of Trace Mercury by Solid Substrate-Room Temperature Phosphorimetry Quenching Method Based on Catalytic Effect of Hg2+on Formation of the Ion Association Complex [Sn(XO)6]4+·[(Fin)4] - Jia-Ming Liu; Ruo-Hong Wu; De-Chang Li; Ping Zhou; Min-Min Zheng; Xiao-Yi Zeng; Dong-Xia Liu; Xiao-Mei Huang; Guo-Hui Zhu (Journal of Fluorescence, 2006)

Nitrogen response efficiency increased monotonically with decreasing soil resource availability: a case study from a semiarid grassland in northern China - Zhi-You Yuan; Ling-Hao Li; Xing-Guo Han; Shi-Ping Chen; Zheng-Wen Wang; Quan-Sheng Chen; Wen-Ming Bai (Oecologia, 2006)

Seasonal Variation of Virioplankton in a Eutrophic Shallow Lake - Yan-Ming Liu; Qi-Ya Zhang; Xiu-Ping Yuan; Zheng-Qiu Li; Jian-Fang Gui (Hydrobiologia, 2006)

Characterization of a partial amphiploid between Triticum aestivum cv. Chinese Spring and Thinopyrum intermedium ssp. trichophorum - Yang Zu-Jun; Li Guang-Rong; Chang Zhi-Jian; Zhou Jian-Ping; Ren Zheng-Long (Euphytica, 2006)

SYNTHESIS BIODISTRIBUTION AND QSAR STUDIES OF FIVE Tc-99M LABELED NOVEL N3S PSEUDO-PEPTIDE COMPLEXES - Hua-bei Zhang; Hai-hong Ye; Ya-ling Zhang; Xuefang Zheng; Jian-sheng Han; Hua Li; Chun-ping Liu (Medicinal Chemistry Research, 2005)

Low-T eclogite in the Dabie terrane of China: petrological and isotopic constraints on fluid activity and radiometric dating - Xu-Ping Li; Yong-Fei Zheng; Yuan-Bao Wu; Fukun Chen; Bing Gong; Yi-Liang Li (Contributions to Mineralogy and Petrology, 2004)

Two novel engineered bacteria for secretory expression of glutaryl 7-amino-cephalosporanic acid acylase - Yong-Gang Zheng; Yong Li; Jian-Feng Chen; Wei-Hong Jiang; Guo-Ping Zhao; En-Duo Wang (Biotechnology Letters, 2001)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)